Exome sequencing of pashtun familial epilepsy in Pakistan reveals novel variants in LAMA5, KCNQ2 and GNAO1 - Qaisar Ali; Sadiq Azam; Jamila Javed; Muhammad Zaheer; Saqib Ullah; Aqib Iqbal; Ibrar Khan; Shoaib Ur Rehman (Molecular Biology Reports, 2026)

Phytochemical Analysis, Antioxidant and Pharmacological Evaluation of Antidiabetic Activity of Methanolic Extract of Geranium wallichianum D. Don ex Sweet in Alloxan-Induced Diabetic Rats - Fatima Afzal; Abdul Aleem; Javed Iqbal; Fahad Asim; Irfan Anjum; Muhammad Naveed Mushtaq (Journal of Pharmaceutical Innovation, 2026)

Screening of bacteriophages for subsequent treatment of resistant Escherichia coli infections transmitted through poultry - Mobeen ur Rashid; Saeed Ahmed; Javed Muhammad; Muhammad Tariq Navid; Waseem Safdar; Aman Karim; Ijaz Ahmad; Haider Ali; Kashif Abdaal (Brazilian Journal of Microbiology, 2026)

Seasonal fluctuation of airborne bacterial dynamics and disinfectant resistance in hospital environment - Shabana Bano; Imran Hashmi; Muhammad Akhtar Khan; Aiza Javed; Nazish Iftikhar (Aerobiologia, 2026)

Molecular epidemiology and resistance modulation of Streptococcus spp. in subclinical goat mastitis in Pakistan - Ashraf Ali; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Hamza Rasheed; Maria Batool; Kehkshan Shahid; Gulbaz Anwar; Mahpara Safdar (Small Ruminant Research, 2026)

Exogenous dopamine alleviates chilling injury of sapodilla (Manilkara zapota) fruit by modulating reactive oxygen species and ascorbate-glutathione cycle activities - Sajid Ali; Syed Muhammad Kashan Haider; Safina Naz; Hafiz Umer Javed; Aamir Nawaz; Shaghef Ejaz; Muhammad Shahzad Saleem (Postharvest Biology and Technology, 2026)

Genomic characterization of genes controlling stay-green trait in bread wheat - Alia Anwar; Xingguo Ye; Hafiz Sabah-Ud-Din Mazhar; Muhammad Waleed Meeran; Ralf Müller-Xing; Muhammad Ashfaq; Muhammad Arshad Javed; Javaria Tabassum; Umar Masood Quraishi; Farheen Solangi; Shajiha Naeem (Euphytica, 2026)

Nanoplastic removal from water using metal–organic framework-based adsorbents and membrane systems: Mechanisms, performance, and practical perspectives - Muhammad Fahad Tariq; I. Ihsanullah; Farhan Javed; Ismail W. Almanassra; Muataz Ali Atieh (Journal of Water Process Engineering, 2026)

Decoupling methanogenesis to boost hydrogen production via microalgae–wastewater co-digestion in a continuous stirred reactor - Muhammad Asad Javed; Ashraf Aly Hassan (Fuel, 2026)

Engineering of novel N-TiO2/P-doped graphene oxide nanocomposite: Mechanistic insights into the photocatalytic removal of benzophenone-3 and H2 production - Wisal Ahmad; Suyeon Jeon; Roman Shah; Dilaram Khan; Syed Izaz Ali Shah; Muhammad Anwar; Raed Al-Juboori; Asad Ali; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Enhanced biomethane production associated with olivine-stimulated CO2 reduction in petroleum reservoir production water - Muhammad Javed; Muhammad Irfan; Le-Gang Chen; Bo Fang; Bo-Wen Wang; Ghulam Dastgir; Muhammad Kashif Javed; Lei Zhou; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2026)

Adsorption-desorption nexus of biowaste-derived biochars towards potentially toxic elements: Unveiling challenges and paving paths for the large-scale mining and industrial soil applications - Javed Nawab; Ruby; Amir Hamza; Muhammad Waqas; Cosimo Magazzino; Matthias Kleinke; Irfan Ullah (Biomass and Bioenergy, 2026)

Molecular insights, resistance profiling, and in silico structural modeling of extended-spectrum beta-lactamase-producing E. coli in camels - Mahpara Safdar; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Kehkshan Shahid; Maria Batool; Gulbaz Anwar; Hamza Rasheed; Ashraf Ali (Veterinary Research Communications, 2026)

Development and Characterization of Exosomes Mediated Transdermal Gel for Enhanced Delivery of Hydroxyurea - Wajeeha Khalid; Rabia Gul; Muhammad Sarfraz; Hamid Bashir; Nadeem Ahmad; Nayab Tahir; Aneela Javed; Muhammad Asad; Ahsan Ibrahim; Aamra Imtiaz; Imran Nazir; Muhammad Imran Amirzada (Journal of Pharmaceutical Innovation, 2026)

Corrigendum to “Green-synthesized silver nanoparticles from Moringa oleifera for eco-friendly management of citrus blast caused by Pseudomonas syringae” [South African Journal of Botany 196 (2026) 715–723] - Servish Munir; Javed Iqbal Wattoo; Muhammad Asim; Hotaf Hassan Makki (South African Journal of Botany, 2026)

Green-synthesized silver nanoparticles from Moringa oleifera for eco-friendly management of citrus blast caused by Pseudomonas syringae - Servish Munir; Javed Iqbal Wattoo; Muhammad Asim; Hotaf Hassan Makki (South African Journal of Botany, 2026)

Physiological and molecular mechanisms underlying crop responses to pest attack and their implications for sustainable management - Waseem Ahmed Khattak; Minhas Elahi; Muhammad Anas; Fatima Ijaz; Sania Noor; Javed Iqbal (Physiological and Molecular Plant Pathology, 2026)

A spare-share scenario framework for exploring biodiversity - onshore wind trade-offs in electricity system planning - Muhammad Shahzad Javed; Dafna Gilad; Roel May; Thomas Kvalnes; Marianne Zeyringer (Journal of Cleaner Production, 2026)

Linking microbial community dynamics to electrochemical corrosion behaviour of copper-nickel and titanium in simulated marine flow conditions - Kiran Kumar Vadde; Luis Perdomo-Hurtado; Jorge Escribano; Alejandro Morales Betancourt; Oladis Troconis de Rincón; Muhammad Awais Javed; Scott Wade; Jason S. Lee; Brendy Rincón Troconis; Vikram Kapoor (International Biodeterioration & Biodegradation, 2026)

Food waste derived biochar via pyrolysis: Properties, contaminant sequestration mechanisms, and environmental applications - Muhammad Waqas; Abdul-Sattar Nizami; Osman Atilla Arikan; Dilek Beyazli; Ali Temiz; Javed Nawab; Muhammad Naqvi; Mohammad Rehan (Environmental Research, 2026)

Retraction notice to ‘Hydrogeochemical properties, source provenance, distribution, and health risk of high fluoride groundwater: Geochemical control, and source apportionment’ [Environ. Pollut. 362, (2024) 125000] - Muhammad Ayub; Hira Javed; Abdur Rashid; Wardah Hayat Khan; Asif Javed; Tariq Sardar; Ghulam Mujtaba Shah; Ajaz Ahmad; Jörg Rinklebe; Parvaiz Ahmad (Environmental Pollution, 2026)

Engineering abiotic stress tolerance in cereal crops: current advances and future directions - Baber Ali; Abdul Rehman; Arafat Abdel Hamed Abdel Latef; Muhammad Imran; Muhammad Ammar Javed; Nathan Wise; Nijat Imin (Cereal Research Communications, 2026)

Growth dynamics and disease resistance of cluster beans were associated with antioxidant enzymes feedback against soil rhizospheric pathogens - Muhammad Waseem Abbasi; Sabina Parveen; Ishrat Jahan; Qu Wei; Marium Tariq; Muhammad Azeem; Mubashar Raza; Muhammad Javed Zaki; Majid Sharifi-Rad (Acta Physiologiae Plantarum, 2026)

Breakthrough advances in plant stress physiology: Acinetobacter schindleri SR-5–1 mitigates wastewater-induced nutrient imbalances in linseed plants - Sherjeel Hashmat; Umer Farooq; Muhammad Tariq Javed; Anni Maryam Afzal; Mohsin Raza Bukhari (Biologia, 2026)

Artificial intelligence integrated in non-destructive technologies for monitoring food freshness: A review of next generation approach - Muhammad Waseem; Muhammad Rizwan Javed; Muhammad Faisal Manzoor; Xiuqi Xia; Yilei Huang; Xiaomei Chen (Food Research International, 2026)

MOF-based composite catalysts for CO2 reduction: Recent advances and perspectives - Asad Ur Rehman; Syed Shoaib Ahmad Shah; Sami Ullah; Arooj Fatima; Ibrahim A. Shaaban; Muhammad Sufyan Javed; Awais Ahmad; Muhammad Altaf Nazir (Environmental Research, 2026)

Smart Wastewater Management: Data-Driven Prediction of Wastewater Using Optimized Learning Techniques - Ali Aldrees; Mohammad Jameel; Bilal Siddiq; Muhammad Hussain; Muhammad Faisal Javed; Furqan Ahmad (Water Conservation Science and Engineering, 2026)

Integrating geostatistics and landsat-8 OLI imagery for regional-scale spatial mapping and remote assessment of soil and foliar nitrogen status in citrus agroecosystem - Humair Ahmed; Muhammad Asad Hameed; Nabeeha Javed; Munazza Yousra; Maria Niaz; Bushra Baloch; Muydinjon Muminov; Sarah Abdul Razak; Shaimaa A. M. Abdelmohsen; Muhammad Tahir Naseem (Environmental Geochemistry and Health, 2026)

Analyzing Household Biological Waste for Energy Efficiency: Advancement Towards Sustainable Energy - Dhaif Allah Ahmed Hadi; Jicheng Liu; Javed Akram; Shahid Ali; Song Yanan; Kathih Ahmed Ali Hadi; Muhammad Sajjad Hussain (Circular Economy and Sustainability, 2026)

Comparative genome-wide analysis and characterization of galactinol synthase (GolS) gene family in diploid and tetraploid cotton species - Umm e Abaida Noor; Muhammad Shaban; Muhammad Abubakkar Azmat; Saman Arshad; Abdul Hafeez; Kamran Javed (Biologia, 2026)

Soil Applied Tartaric Acid Mitigates Lead-Induced Toxicity in Chickpea By Modulating Morphophysiological, Biochemical and Genetic Responses - Farwa Tariq; Muhammad Javed; Muhammad Yaqoob; Habib Ali; Muhammad Khubaib Ijaz; Muydin M. Muminov; Muhayyo O. Buranova; Hossam S. El-Beltagi; Sadam Hussain (Journal of Soil Science and Plant Nutrition, 2026)

Antimicrobial Plant Protein Patatin: Identification and In-Silico Analysis Through Phylogenetics and Molecular Docking - Sarah Tariq; Binish Khaliq; Hina Shaheen; Ahmad Riaz; Sumaira Rubbani; Muhammad Sajid Hamid Akash; Amjad Hussain; Muhammad Imran; Muhammad Arslan Javed; Ahmed Akrem; Sohaib Mehmood; Sajjad Azam (Agricultural Research, 2026)

Food security dynamics in South Asia: a multi-method analysis using Random Forest and Error Trend Seasonal models - Muhammad Atiq-ur-Rehman; Sadia Mustafa; Ayesha Hussain; Irfan Hussain Khan; Fatima Akhtar; Sadaf Javed; Azma Batool (Environment, Development and Sustainability, 2026)

Heat-Wave Prediction via Joint Regression and Classification with a Bayesian Deep Bidirectional LSTM Model - Iqra Sardar; Farzana Noor; Muhammad Javed Iqbal; Ishfaq Ahmad; Muhammad Azeem Akbar (Environmental Modelling & Software, 2026)

Assessment of Fine Particulate Matter (PM2.5) Induced Cyto-Genotoxicity in a Highly Polluted Urban Environment: Evidence from Lahore, Pakistan - Meerub Shazad; Muhammad Muddassir Ali; Syed Aziz ur Rehman; Maryam Javed; Jabir Hussain Syed; Asad Ullah (Water, Air, & Soil Pollution, 2026)

Performance evaluation of sustainable concrete incorporating mineral fillers: experimental insights and predictive modeling using advanced machine learning - Maaz Khan; Muhammad Faisal Javed; Usama Asif; Hisham Alabduljabbar (Innovative Infrastructure Solutions, 2026)

Roadside dust as a vector of potentially toxic metals: an ecological and human health risk assessment in urban areas of semi-arid climatic regions - Namoos Khan; Kainat Zarin; Muhammad Adnan; Seemab Akhtar; Irfan Ullah; Javed Nawab; Nadeem Ali (Environmental Monitoring and Assessment, 2026)

Synergistic Effects of Biochar with Phosphorus Fertilization on soil Biochemical Properties and Wheat Productivity - Nighet Musa; Khalid Saifullah Khan; Muhammad Azeem; Mah-Noor Azad; Mehnoor Khan; Nabeeha Javed; Tajwar Alam (Journal of Soil Science and Plant Nutrition, 2026)

Thermophoretic heat and mass transfer in magnetohydrodynamic transport of a yeleswarapu fluid driven by metachronal cilia - Muhammad Asif Gondal; Zeeshan Asghar; Muhammad Asif Javed; Muhammad Waris Saeed Khan (Dynamics of Atmospheres and Oceans, 2026)

Photocatalytic CO2 reduction: Fundamental principles, mechanistic pathways and material-specific kinetic insights - Syed Izaz Ali Shah; Muhammad Anwar; Wisal Ahmad; Muhammad Ateeq; Amir Zada; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Bridging Lab to Land: Field Validation of Acinetobacter schindleri SR-5–1 for Nutrient Acquisition and Oxidative Stress Mitigation in Wastewater-Irrigated Pea (Pisum sativum L.) Plants - Sherjeel Hashmat; Muhammad Arslan Ashraf; Muhammad Tariq Javed; Umer Farooq; Mobeen Umer (Water, Air, & Soil Pollution, 2026)

Soil-mediated Rhizobacteria Modulate SA-JA Transcriptional Antagonism in Tomato to Enhance Systemic Resistance Against a Specialist and a Generalist Herbivore - Muhammad Wajid Javed; Jam Nazeer Ahmad; Samina Tanwir; Ahmad Nawaz (Journal of Soil Science and Plant Nutrition, 2026)
Salicylic (SA) and jasmonic acid (JA) defense pathways antagonize each other to compromise host plant defense. Modulation of SA-JA transcriptional antagonism could enhance plant resistance against herbivores. Tomato, Solanum lycopersicum , was treated with phytohormonal inducers BTH (Benzothiadiazole-SA synthetic analogue) and MeJA (Methyl jasmonate-JA analogue) through foliar applications at 0, 0.5, and 1 mM, while PGP rhizobacteria ( Bacillus sp. Mb01 and Pseudomonas sp. Mb05) were applied through roots using a randomized block design having three replications. RNA transcripts of SA responsive genes ( PR1a and PAL ) and JA eliciting genes ( PIN2 and LOX ) were studied. Individual application of SA/JA synthetic analogues improved the levels of their respective marker genes but generated an antagonism by masking each other’s expression. Conversely, individual and combined treatment with rhizobacteria modulates SA/JA antagonism to enhance the expression of SA marker genes under MeJA treatment and of JA marker genes under BTH treatment. This improvement was tested against a specialist (whitefly, Bemisia tabaci ) and a generalist herbivore (tomato fruit borer, Helicoverpa armigera ) to assess enhanced pest resistance. Although SA and MeJA reduced the mean larval weight, larval survival, and adult emergence of H. armigera along with the mean nymph population of B. tabaci , the results were more pronounced when inducers were applied along with rhizobacteria. Instead of separate applications of BTH/MeJA, their combined application with PGPR is recommended to improve hostplant resistance against phytophagous pests. However, investigations on other SA and JA eliciting genes, PGPR species, and pests are required to implement these findings in a broader crop -pest spectrum.

Dry Matter Partitioning and Yield in Brassica Napus: Insights from ¹³C Isotopes Labeling Across Growth Stages - Hafiz Hassan Javed; Yue Hu; Ali Raza; Muhammad Ahsan Asghar; Xiao Peng; Abd Ullah; Yong-Cheng Wu (Journal of Soil Science and Plant Nutrition, 2026)

Role of rituximab in treatment of patients with primary central nervous system lymphoma: An updated systematic review and meta-analysis - Kumail Mustafa Ali; Muhammad Farhan Ashraf; Zain Ul Abideen; Armish Rehman; Rumman Javed; Ayena Ghulam Mujtaba; Touba Diwan; Ukasha Khalid; Laiba Ikram (Acta Neurologica Belgica, 2026)

Radiological contamination in soils near the world's largest rare earth minerals producing region and their impacts on human health: A summary analysis - Amir Hamza; Faisal Khan; Javed Nawab; Junaid Ghani; Sajid Ali; Yaseen Laghari; Luo Xin; Niaz Muhammad; Jing Cui; Zhenggui Wei (Journal of Environmental Radioactivity, 2026)

Optimum N Fertilization Enhances Salinity Tolerance and N use Efficiency in Maize through Modulation of Antioxidant Defense and Biochemical Pathways - Syed Ayyaz Javed; Muhammad Tauseef Jaffar; Muhammad Ashraf; Muhammad Ahmed; Ali Raza Siddiqui; Hafiz Muhammad Bilal; Jawad Amin; Sanaullah Sattar (Journal of Plant Growth Regulation, 2026)

Valorization of recycled concrete fine aggregates in gypsum mortars for developing eco-friendly false ceiling plates - Rashid Latif; Muhammad Rizwan Riaz; Anam Fatima; Rizwan Azam; Muhammad Hassan Javed (Innovative Infrastructure Solutions, 2026)

Molecular insights into HPV-16 L2 capsid protein and inhibitor screening study - Saima Younas; Atiqa Nosheen; Muhammad Abdul Qayyum; Hafiza Ayesha Malik; Sadia Manzoor; Rabia Arooj; Nazim Hussain; Qurban Ali; Muhammad Arshad Javed; Daoud Ali; Adnan Iqbal (In Silico Pharmacology, 2026)

Vernalization responses in Brassica: An insight into key regulatory genes, long non-coding RNAs, associated co-regulatory networks, and their epigenetics - Aftab Ahmad; Afrasyab Khan; Muhammad Ahmad Hassan; Javed Iqbal; Na Liao; Zainab Ghazala; Wenjie Wang; Lingyun Yuan; Chenggang Wang; Guohu Chen (Plant Science, 2026)

Immobilization and stabilization nexus of bio-waste derived biochar towards potentially toxic elements in vegetables: A deterministic and probabilistic human health risk assessment - Irfan Ullah; Seemab Akhtar; Muhammad Adnan; Javed Nawab (Biomass and Bioenergy, 2026)

Role of Nano-Silicon, Nano-Biochar, and Irrigation Strategies in Managing Tellurium Toxicity: Implications for Soil Microbiota, Wheat Yield, and Food Safety - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Zeeshan Ahmed; Rehman Habib; Javed Iqbal; Gamal Awad El-Shaboury; Sajad Ali; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Comparative insights into molecular characterization and resistance profiling of methicillin-resistant Staphylococcus aureus across dairy livestock in Pakistan - Muhammad Ijaz; Maria Batool; Muhammad Umar Javed; Hamza Rasheed; Arslan Ahmed; Ali Abdullah Jabir; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2026)

Seismotectonic Analysis of Pabbi Blind-Thrust in the NW Himalayan Foreland: Evidence from the 2024 Kharian Earthquake - Mohammad Tahir; Bilal Saif; Raja Adnan Habib; Farhan Javed; Muhammad Zafar Iqbal; Talat Iqbal; Nasir Mahmood; Najeeb Ahmed (Pure and Applied Geophysics, 2026)

Effect of environmental variables on the bionomics of Telenomus remus (Hymenoptera: Scelionidae) against Spodoptera frugiperda (Lepidoptera: Noctuidae) - Kinza Qadeer; Muhammad Asif Gondal; Javed Khan (Phytoparasitica, 2026)

The ameliorative effects of glutamic acid-capped hydroxyapatite nanoparticles on the physio-chemical parameters of sunflower (Helianthus annuus L.) under induced salt stress - Seemab Akhtar; Irfan Ullah; Muhammad Adnan; Javed Nawab; Rehman Ullah (Journal of Crop Science and Biotechnology, 2026)

Retraction Note: Unveiling the genetic diversity and host specificities of rust: morphological and molecular characterization of Berberis species - Siraj Uddin; Javed Iqbal; Banzeer Ahsan Abbasi; Shumaila Ijaz; Ghulam Murtaza; Muhammad Waseem; Umar Masood Quraishi; Atman Adiba; Reem M. Aljowaie; Saeedah Musaed Almutairi; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Genetic characterization of selected species of family Solanaceae based on chloroplast rps14 gene - Sitara Bibi; Javed Iqbal; Banzeer Ahsan Abbasi; Sobia Kanwal; Tariq Mahmood; Muhammad Waseem; Dunia A. Al Farraj; Mohamed S. Elshikh; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Morphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Myoinositol-mediated regulation of leaf physiology, biochemistry, and water relations confers heat stress tolerance in Quinoa - Rashid Iqbal; Muhammad Sarwar; Basharat Ali; Muhammad Farrukh Saleem; Hassaan Ahmad; Muhammad Shahid; Javed Iqbal; Khairiah Mubarak Alwutayd; Dilfuza Jabborova; Sajad Ali; Ghulam Murtaza (Plant Biosystems, 2026)

Exploring the potential of indigenous coal mine isolates Pseudomonas aeruginosa (PM55) and Enterobacter cloacae (PM56) for Cr(VI) bioremediation and plant growth promotion - Nida Zainab; Fazal ur Rehman; Amna Amna; Iftikhar Ahmad; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Biodegradation, 2026)

Soil amendments enhance phenolic defense in canola, suppressing cabbage aphid population and improving yield performance - Muhammad Wajid Javed; Mansoor–ul Hasan; Muhammad Sagheer; Shahbaz Talib Sahi (International Journal of Tropical Insect Science, 2026)

Retraction notice to ‘Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward’ [Chemosphere 325 (2023) 138367] - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2026)

Evaluation of Genetic Diversity, Yield, and Its Associated Traits in Rice (Oryza Sativa L.) Genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Abdul Rehman; Shabir Ahmad; Khairiah Mubarak Alwutayd; Fatmah Ahmed Safhi; Javed Iqbal; Rashid Iqbal (Plant Molecular Biology Reporter, 2026)

Efficacy and safety of lorundrostat in uncontrolled hypertension: A GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Umama Alam; Shree Rath; Javeria Javed; Akif Shahid Khan; Abdul Moiz; Muhammad Ansab; Alishba Hameed; Zaryab Bacha; Zarar Ahmad Khan Afridi; Khushal Khan; Raheel Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Bio-Elicitors Could Perform Better Over Synthetic Insecticides in Promoting Plant Growth, Nutrient Acquisition, and Aphid Resistance in Canola Through Phenolic Enhancement - Muhammad Wajid Javed; Muhammad Sagheer (Journal of Soil Science and Plant Nutrition, 2026)

Co-application Impacts of Silicon and Potassium Fertilizers on Wheat (Triticum Aestivum L.) Growth and Nutritional Attributes in Cadmium-contaminated Soil Under Two Irrigation Regimes - Ghulam Murtaza; Najmaldin Ezaldin Hassan; Muhammad Rizwan; Qamar uz Zaman; Gang Deng; Zeeshan Ahmed; Javed Iqbal; Mohamed S. Elshikh; Humaira Rizwana; Shabir Ahmad; Lala Gurbanova; Rashid Iqbal (Journal of Soil Science and Plant Nutrition, 2026)

Synergistic Effect of Biochar and Bacillus Subtilis on the Development of Colletotrichum Graminicola in Maize - Nimra Nadeem; Adnan Akhter; Waheed Anwar; Tehmina Anjum; Muhammad Khurshid; Nasir Ali; Sana Javed; Hibba Arshad (Journal of Soil Science and Plant Nutrition, 2026)

Nitrogen Addition Optimizes Root-Leaf Coordination of Carbon-Nitrogen Metabolism and Osmolytes to Improve Drought Tolerance in Alhagi Sparsifolia - Abd Ullah; Akash Tariq; Fanjiang Zeng; Muhammad Ahsan Asghar; Javaria Noor; Hafiz Hassan Javed; Abeer Kazmi; Jordi Sardans; Josep Peñuelas (Journal of Soil Science and Plant Nutrition, 2026)

Alleviation of Lead Stress in Maize Plants Through the Application of Green-Synthesized Zinc Oxide Nanoparticles - Haseeba Maryam; Nasir Masood; Muhammad Waseem; Temoor Ahmed; Muhammad Zia-ur-Rehman; Muhammad Atif Irshad; Saher Javed; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2026)

Bisphenol S-induced endocrine disruption and reproductive anomalies - Benish Nawaz; Zaira Ahmad; Hanan Afzal; Kaleem Maqsood; Abdul Manan Khan; Zoya Asif; Sabahat Javed; Ali Afzal; Afzal Nimra; Muhammad Babar Khawar (Toxicology and Environmental Health Sciences, 2026)

Molecular Detection and Phylogenetic Characterization of Avian Infectious Bronchitis Virus (IBV) in Vaccinated Commercial Chicken Flocks Experiencing Outbreaks in Faisalabad, Pakistan - Muhammad Mubeen Ahmad; Muhammad Wasif Gulzar; Muhammad Wasif Azeem; Muhammad Musa Mubashar; Rida Fatima; Muhammad Tayyab Naveed; Muhammad Taha; Sana Riaz; Asad Javed; Mudasser Habib; Rizwan Aslam (Archives of Virology, 2026)

Evaluation of leaf extracts of Moringa oleifera Lam. On testosterone enanthate-induced polycystic ovary syndrome (PCOS) in mice - Shakeela Khalid; Muhammad Arshad; Farzana Siddque; Muhammad Sajid Arshad; Marina Sajid; Waseem Khalid; Zaira Aziz; Muhammad Zubair Khalid; Sulaiman Ali Alharbi; Mohammad Javed Ansari; Abdellah Zinedine; Elena Bartkiene; et al. (Advances in Traditional Medicine, 2026)
Polycystic ovary syndrome (PCOS) is a multifactorial endocrinological and metabolic disorder that affects women of reproductive age. It is often associated with hyperandrogenism, obesity, anovulation, infertility and insulin resistance. In this study, the imminent efficacy of MoLP ( Moringa oleifera leaf powder) and MoLE ( M. oleifera leaf extract) in treating PCOS in female albino mice was explored. Female albino mice were injected with testosterone enanthate [1.0 mg/100 g body weight (b.w.)] for 35-days to induce PCOS. For the treatment, mice were administered with M. oleifera leaf powder (250 and 500 mg/kg b.w.), M. oleifera leaf extract (250 and 500 mg/kg b.w.), and metformin (250 mg/kg b.w.) for 14 days. Following the intervention, body weight, blood glucose, c-peptide, testosterone, follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels and stages of the estrus cycle were measured at 0, 7 and 14 days. The ovaries were examined stereologically to determine the number and diameter of follicles. Results indicated that MoLP, MoLE (500 mg/kg b.w.) and metformin (250 mg/kg b.w.) significantly decreased body weight, blood glucose, c-peptide, testosterone and LH levels while increasing FSH levels and ovary weight over time compared to PCOS-induced mice. Additionally, regulation of the estrus cycle and folliculogenesis in PCOS-induced mice was observed. Overall, the present study revealed that M. oleifera may have the potential as a therapeutic intervention for PCOS. Graphical Abstract

Timing of India-Asia diachronous collision: A view from the westernmost Indian margin, Pakistan - Muhammad Qasim; Owais Tayyab; Lin Ding; Javed Iqbal Tanoli; Muhammad Awais; Kamran Tabassum; Fulong Cai; Zhang Dingding; Ishtiaq A.K. Jadoon (Tectonophysics, 2026)

Corrigendum to “Enhanced persulfate activation via FeS/FeS2 and boron synergized Fe(II)/Fe(III) cycling for trichloroethylene degradation: Experimental and theoretical insights” [Chem. Eng. J. 527 (2026) 172147] - Mudassir Habib; Tehreem Ayaz; Meesam Ali; Muhammad Rizwan; Xianxian Sheng; Muhammad Kashif Javed; Rongbing Fu; Shuguang Lyu (Chemical Engineering Journal, 2026)

Remediation of Water Contaminated by Toxic Metals with Multi-metal/Co-doped Modified Biochars - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Muhammad Qasim; Javed Iqbal; Shabir Ahmad; Rashid Iqbal; Lala Gurbanova; Mehdi Rahimi (Water, Air, & Soil Pollution, 2026)

Overexpression of rapeseed BnaLhcb5.3 mediates cellular metabolism and antioxidant defense under chromium stress - Iram Batool; Tongjun Qin; Ahsan Ayyaz; Fakhir Hannan; Muhammad Javed; Weiqi Chen; Zafar Ullah Zafar; Muhammad Shahbaz Naeem; Muhammad Ahsan Farooq; Weijun Zhou (Physiology and Molecular Biology of Plants, 2026)

Precision Rewiring of Stress-Responsive Gene Networks Via CRISPR: Mechanistic Pathways Toward Climate-Smart Agriculture - Burhan Khalid; Muhammad Umer Javed; Muhammad Ikram; Muhammad Ateeq; Muhammad Atiq Ashraf; Talha Riaz; Shumaila Nawaz; Rizwan Maqbool (Journal of Crop Health, 2026)

Sodium carbonate and sodium chloride as elicitors of secondary metabolite production in callus cultures of Fagonia indica - Muhammad Uzair Javed; Muhammad Asad Ullah; Tehreem Mahmood; Taimoor Khan; Iva Viehmannova; Anmol Akbar; Yasir Khan; Tariq Khan; Bilal Haider Abbasi; Christophe Hano; Nathalie Giglioli-Guivarc’h (Plant Biosystems, 2026)

Marine Drug Design for Epitheliocytis Rendering AI ‐Assisted Bioisosteric Replacement of Salicin - Muhammad Naveed; Khushbakht Javed; Tariq Aziz; Rahmana Wazir; Imran Ali; Ayaz Ali Khan; Ashwag Shami; Maher S. Alwethaynani; Fahad Al‐Asmari; Fakhria A. Al‐Joufi (Journal of Fish Diseases, 2026)
Epitheliocystis is a distinctive and relatively understudied bacterial infection of finfish skin and gill epithelia that occurs intracellularly and results in the enlargement of the host cells. The Candidatus Syngnamydia salmonis is a bacterial pathogen that affects fish, especially salmon species like trout and salmon. The production of Epitheliocystis by Candidatus Syngnamydia salmonis poses several challenges to the aquaculture industry. Currently, limited drugs and therapies are available to effectively manage and cease the spread of this disease. The goal of this study was to develop a potential drug target for the treatment of epitheliocystis. Salicin, an organic glucoside widely known for its anti‐inflammatory characteristics, was chosen as the initial compound because of its pharmacological significance and confirmed as a bioisostere (a compound with identical biological activities but a different structure). The Xundrug MolOpt AI generative model of bioisosteric replacement tool was chosen as the optimisation technique in a cognitive exertion to improve the novel drug candidate salicin by its AI‐assisted bioisosteric replacement. To retrieve the docking results, the top three ligands from Xundrug and the cell division protein of Candidatus Syngnamydia salmonis were uploaded to the HDOCK web server, which utilises a hybrid docking technique combining template‐based modelling for docking. The target drug candidate was selected based on model 17's highest docking score of 135.6 kcal/mol. Furthermore, the Lipinski rule of five and the ADMET properties of the Bioisosteric Replaced Salicin model 17 (BRS‐17) were carefully explored. The results showed that BRS‐17 fulfilled the pharmacophore characteristics criteria, hence making it an ideal target candidate for Candidatus Syngnamydia salmonis' cell division protein. Additionally, the results are supported by −6.735Kcal/mol docking score predicted by DockThor. With the help of the supporting information from this study, the proposed drug design can close the gap in earlier studies for resistance to antibiotic treatments. It is suggested that in vitro tests be performed on this drug to show the effectiveness of the suggested design.

Status of insecticide resistance in Spodoptera litura (Lepidoptera: Noctuidae) on cauliflower, Punjab, Pakistan - Dilbar Hussain; Muhammad Sohail Qadir; Muhammad Asrar; Muhammad Saleem; Usama Saleem; Zeeshan Javed; Kanwal Hanif; Arshed Makhdoom Sabir; Ijaz Haider; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal (International Journal of Tropical Insect Science, 2026)

Synergistic effects of biochar and silicon dioxide nanoparticles abate cadmium uptake and oxidative stress in tomato: Achieving crop resilience and environmental sustainability - Muhammad Kashif Irshad; Muhammad Waseem; Saba Saleem; Jamilur R. Ansari; Sana Ashraf; Wasim Javed; Ali Noman; Muhammad Aqeel; Muhammad Rizwan; Afrah E. Mohammed; Modhi O. Alotaibi; Muhammad Rizwan; et al. (Plant Science, 2026)

Geochemical modeling, evaluation of contaminants and impacts of land use, land cover patterns on groundwater quality in Khushab, Pakistan - Hasnain Abbas; Javed Iqbal; Syed Madhi Haider Kazmi; Maqsood Ahmed; Muhammad Ismail; Wajid Hussain (Journal of Contaminant Hydrology, 2026)

Fate and transport of viruses in the subsurface environment: A systematic review of pollution pathways in saturated and unsaturated porous media - Muhammad Yousuf Jat Baloch; Purnima Baidya; Manita Aryal; Muhammad Moeen-ud-din; Liu Yang; Javed Iqbal; Mariusz Ptak; Predrag llić; Chunguang Liu (Environmental Research, 2026)

Enhanced persulfate activation via FeS/FeS2 and boron synergized Fe(II)/Fe(III) cycling for trichloroethylene degradation: Experimental and theoretical insights - Mudassir Habib; Tehreem Ayaz; Meesam Ali; Muhammad Rizwan; Xianxian Sheng; Muhammad Kashif Javed; Rongbing Fu; Shuguang Lyu (Chemical Engineering Journal, 2026)

Synergistic Ni single-atom–nanoparticle interfaces for poison-resistant CO₂ electroreduction - Syed Shoaib Ahmad Shah; Jamal Kazmi; Muhammad Altaf Nazir; Manzar Sohail; Muhammad Sufyan Javed; Tayyaba Najam; Lishan Peng; Ramón A. Alvarez-Puebla (Chemical Engineering Journal, 2026)

Holistic review on Paenibacillus: The multifunctional genus in heavy metal detoxification, pesticide degradation, and abiotic stress mitigation for Sustainable Agriculture - Izhar Khan; Nadeem Ullah; Haris Maqbool; Adnan Hashmi; Basit Khan; Afnan Khalid; Iffat Naz; Najeeba Parre Paker; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Plant and Soil, 2026)

A GIS-based technique for estimation of economic losses from riverine flood in the lower Indus basin - Javeria Sarwar; Saud Ahmed Khan; Muhammad Azmat; Faridoon Khan; Swera Javed (Natural Hazards, 2026)

Unravelling the Mechanistic Role of Soil Microbial Interactions in the Suppression of Phytopathogens in Vegetable Agroecosystems of Pakistan - Basit Khan; Nadeem Ullah; Haris Maqbool; Faria Khan; Izhar Khan; Afnan Khalid; Maryam Arshad; Najeeba Parre Paker; Iffat Naz; Muhammad Akmal; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Current Microbiology, 2026)

Future of PARP inhibitors in cancer treatment: overcoming resistance and enhancing efficacy with combination therapies - Muhammad Shoaib; Zeeshan Ahmad Bhutta; Ahsan Javed; Muhammad Nabeel Amjad; Wenzhu Li; Kyung-Chul Choi; Wanxia Pu (Journal of Zhejiang University-SCIENCE B, 2025)

Climate-responsive cropland dynamics in Indus Basin: A comprehensive SDM assessment with intra-seasonal variability - Fatima Ilyas; Muhammad Azmat; Swera Javed; Shakil Ahmad; Muhammad Arshad; Muhammad Usman Rashid; Saeed Ahmad Asad (Science of The Total Environment, 2025)

First-principles study on structural, elastic, acoustic and optoelectronic properties of hexagonal magnesium oxide (MgO) - Maryam Tariq; Tariq Mahmood; Robina Ashraf; Imran Aslam; Muhammad Rizwan; Arbab Arif; Ch. Omer Javed; Afshan Urooj (Next Research, 2025)

Solubility measurements of R143a, R23 and R116 with [HMIM][TF2N] and [BMIM][BF4] - Nimra Javed; Muhammad Salman; Yiran Wang; Peiji Wang; Asim Shakeel; Xiangyang Liu; Maogang He (International Journal of Refrigeration, 2025)

Effect of dietary proteins on mayonnaise techno-functionality and rheology: A review - Wahab Ali Khan; Muhammad Waseem; Iqra Yasmin; Syed Abdul Wadood; Aiza Qamar; Muhammad Rizwan Javed; Muhammad Saleem; Crossby Osei Tutu (Food and Humanity, 2025)

Advances in Microbial Bioremediation of Microplastics in Mangrove Sediments: a Comprehensive Review - Muhammad Sheeraz Javed; Muhammad Adil; Jiliang Zhang; Isma Gul; Muhammad Rauf; Saeed Ahmad; Bushra Moon; Siqi Lu; Heli Lu; Ali Haidar Gormani; Younas Iqbal; Hassan Mahmood (Water, Air, & Soil Pollution, 2025)

Predicting rice yield and impact of climate change on rice production using machine learning models - Khawaja T. Tasneem; Muhammad Umair Shahzad; Javed Rashid; Kamal M. Othman; Tania Zafar; Muhammad Faheem (Theoretical and Applied Climatology, 2025)
Climate change poses a critical threat to agricultural sustainability, with direct implications for the global food supply. Rice, a staple crop throughout Asia, is particularly vulnerable to variations in temperature and rainfall, making it essential to understand how it responds to changing climatic conditions. This study integrates historical climate records, rice yield data, and projections from Global Climate Models (GCMs; CMIP3) to assess the potential effects of climate change on rice production in Punjab, Pakistan. We employed multiple machine learning approaches, including Multiple Linear Regression (MLR), Boosted Tree Regression (BTR), Probabilistic Neural Network (PNN), Generalized Feed-Forward (GFF) Neural Network, Linear Regression (LR), and a Multilayer Perceptron (MLP) Artificial Neural Network. The models were trained and validated using observed climate and yield data from 1990 to 2020. Future yields were projected under three IPCC emission scenarios (SR-A2, SR-A1B, SR-B1) through the year 2050. Model evaluation showed that the Multilayer Perceptron (MLP) achieved the highest predictive performance ( $$R^2$$ = 0.791, R = 0.868, MAE = 0.215, MSE = 0.0869, NMSE = 0.3681), followed by Boosted Tree Regression (BTR; $$R^2$$ = 0.779, R = 0.845, MAE = 0.334, MSE = 0.1308). The Probabilistic Neural Network (PNN) and Generalized Feed-Forward (GFF) model also performed respectably ( $$R^2$$ = 0.745, R = 0.811, MAE = 0.176, MSE = 0.380 and $$R^2$$ = 0.643, R = 0.825, MAE = 0.398, MSE = 0.178, respectively). In contrast, Multiple Linear Regression (MLR) and Linear Regression (LR) performed poorly, with low $$R^2$$ values (0.535), underscoring their inability to capture the non-linear relationships between climate variables and yield. Our analysis identifies maximum temperature as the primary climatic driver of yield loss. Based on the projections, we estimate an average yield decline of 0.12% by 2050. This study demonstrates that non-linear machine learning models, particularly the MLP, are essential for reliable agricultural forecasting under climate change. The results highlight the growing vulnerability of rice production to rising temperatures and provide a robust evidence base for designing adaptation strategies, such as developing heat-tolerant rice varieties, to enhance food security in vulnerable regions.

Functional insights into drought-tolerant PGPR: impacts on physiological responses and yield performance of direct-seeded rice under water stress - Faiza Javed; Sumera Iqbal; Muhammad Shahbaz Farooq; Khajista Jabeen; Noshin Ilyas; Abid Majeed (The Science of Nature, 2025)

Whitefly-Resistant Population Development Source Selection Among Cotton Germplasms of Pakistan Through Multivariate Tools - Obad Ul Rahman; Syed Bilal Hussain; Muhammad Javed (Plant Molecular Biology Reporter, 2025)

Green nanomaterials for soil fertility; A promising approach to combat world’s hunger - Muhammad Irfan; Aqsa Javed; Abeer Zafar (Nanotechnology for Environmental Engineering, 2025)

Circular RNAs MTO1 and ZNF292 as potential diagnostic biomarkers in HIV patients treated with antiretroviral therapy - Mahnoor Fatima; Muhammad Shahid; Iram Amin; Hasnain Javed (Molecular Biology Reports, 2025)

Nitrogen Addition Improved Drought Tolerance in Calligonum Mongolicum Via Coordinated Regulation of Osmolytes and Carbon/Nitrogen Metabolism in Leaves and Roots - Abd Ullah; Akash Tariq; Fanjiang Zeng; Javaria Noor; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Abeer Kazmi; Jordi Sardans; Josep Peñuelas (Journal of Soil Science and Plant Nutrition, 2025)

Flavones-Fortified Biochar Enhances Barley (Hordeum Vulgare L.) Growth and Productivity by Ameliorating Cadmium and Copper Toxicity - Ghulam Murtaza; Muhammad Bilawal Junaid; Faisal Mahmood; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Alanoud T. Alfagham; Javed Iqbal; Gang Deng; Zeeshan Ahmed; Trobjon Makhkamov; Lala Gurbanova; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Endophyte Bacterial Metabolites: An Active Syrup for Improvement of Growth, Biomass, and Antioxidant System of Zea mays L. in Drought Condition - Mahwish Salman; Muhammad Rizwan Javed; Anam Tariq; Muhammad Usama; Hafiza Iqra Hanif; Bushra Sadia; Shazia Naheed (Journal of Plant Growth Regulation, 2025)

Halotolerant Bacillus Aryabhattai Strain PM34 Mitigates Salinity Stress and Enhances the Physiology and Growth of Maize - Muhammad Atif Azeem; Salman Khan; Fawad Ali; Sajjad Ahmad; Gul Rahim; Muhammad Iftikhar; Majid Iqbal; Rawa Saad Aljaloud; Khaloud Mohammed Alarjani; Hassan Javed Chaudhary (Journal of Plant Growth Regulation, 2025)

CRISPR-Cas9 based editing of the susceptibility allele TaLr34 enhances leaf rust resistance in bread wheat without yield penalty - Muhammad Makky Javaid; Javed Ahmed; Moddassir Ahmed; Muhammad Jawad Akbar Awan; Muhammad Abu Bakar Waqas; Zahir Ali; Nasir A. Saeed (Functional & Integrative Genomics, 2025)

Physio-biochemical alterations and phytoremediation potential of hemp cultivated in ciprofloxacin (CIP)-contaminated soil: groundbreaking and enduring solution - Ghulam Murtaza; Muhammad Usman; Muhammad Rizwan; Javed Iqbal; Hassan Mehmood; Hossam S. El-Beltagi; Khairiah Mubarak Alwutayd; Gamal Awad El-Shaboury; Rashid Iqbal (Biodegradation, 2025)

Mindsets matter: Reimagining the destination brand experience-environmental behaviour link through a cognitive lens - Muhammad I. Hossain; Arnold Japutra; Nurnobi Islam; Ammar Javed (Journal of Environmental Management, 2025)

Response of invasive Solidago canadensis to foliar application of natural herbicide and glyphosate - Muhammad Anas; Zhi-Yun Huang; HuAnHe Xiong; Muhammad Imran; Meng-Ting Yan; Qaiser Javed; Guang-Qian Ren; Shan-Shan Qi; Jian Li; Zhi-Cong Dai; Dao-Lin Du (Journal of Environmental Management, 2025)

Unveiling divergent crop signals in the face of climate variability and ensemble climate projections using CMIP6 data in the South-West of Pakistan - Beenish Javed; Firdos Khan; Muhammad Abbas; Shaukat Ali (Stochastic Environmental Research and Risk Assessment, 2025)

Wooden ash based nylon fiber reinforced concrete: experimental study on concrete strength properties - Muhammad Sheraz; Qiang Yuan; Muhammad Alam; Muhammad Faisal Javed (Innovative Infrastructure Solutions, 2025)

Assessment of microbial remediation potential of indigenous bacterial and fungal communities for toxic heavy metal sequestration - Afnan Khalid; Haris Maqbool; Izhar Khan; Basit Khan; Iffat Naz; Shanza Abdul Qayyum; Javed Ali; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Geochemistry and Health, 2025)

Potential of Organic Amendments as a Sustainable Strategy to Enhance Rice Yield by Improving Nutrient Use Efficiency and Physiological Performance in Alkaline Soil - Muhammad Ahmed; Muhammad Tauseef Jaffar; Zulfiqar Ahmad; Muhammad Naveed; Syed Ayyaz Javed; Muhammad Shoaib Asad; Ali Raza; Awais Shakoor; Jianguo Zhang (Journal of Plant Growth Regulation, 2025)

Optimizing Charge Transport Properties of Dithieno[3,2-b:2′,3′-d] Pyrrole-Based Hole Transport Materials for Perovskite Solar Cells: a DFT Study - Nabeel Shahzad; Muhammad Ishaq; Aqsa Laraib; Tazeem Fatima; Rida Fatima; Waqas Akram; Javed Iqbal (Journal of Fluorescence, 2025)

Pinobanksin ameliorates perfluorooctane sulfonate-evoked cardiotoxicity via targeting Nrf-2/Keap-1, oxidative damage and inflammation in Sprague Dawley rats - Maryam Javed; Quratulann Sattar; Muhammad Faisal Hayat; Hamida Hamdi; Muhammad Zaid Salar (Tissue and Cell, 2025)

Distinct gonadotropin receptor profiles across follicle sizes reveal potential mechanism for follicular co-dominance in goats - Waqas Ahmad; Muhammad Suleman; Jawad Akhtar; Amjad Riaz; Khalid Javed; Muhammad Imran Rashid; Muhammad Irfan-ur-Rehman Khan (Theriogenology, 2025)

Xanthan gum coating delays ripening of harvested mango (Mangifera indica L.) fruit by suppressing chlorophyll catabolism and cell wall polysaccharides degradation - Maimona Qasim; Sajid Ali; Hafiz Umer Javed; Safina Naz; Ahmad Sattar Khan; Muhammad Hassan; Rana Naveed Ur Rehman (Postharvest Biology and Technology, 2025)

Optimizing the anticancer action and toxicity evaluation of cobalt ferrite nanoparticles by different polyethylene glycol concentrations - Kanwal Akhtar; Muhammad Khawar Abbas; Nida Muzammil; Naveed Akhtar Shad; Qaisar Iqbal; Wasim Abbas; Faqir Muhammad; Bushra Akhtar; Yasir Javed; Habiba Khadim; Anam Munawar (Journal of Trace Elements in Medicine and Biology, 2025)

From shadow to sustainability: How informality, environmental taxes, and green innovation reshape carbon and biodiversity futures in the G7 countries - Sami Ur Rahman; Imran Ali Khan; Fariha Sami; Javed Hussain; Muhammad Ibrahim Khan (Journal of Environmental Management, 2025)

Corrigendum to “Designing highly potential photocatalytic comprising silver deposited ZnO NPs with sulfurized graphitic carbon nitride (Ag/ZnO/S-g-C3N4) ternary composite” [J. Environ. Chem. Eng. 9 (2021) 104919] - Shahid Iqbal; Naveed Ahmad; Mohsin Javed; Muhammad Azam Qamar; Ali Bahadur; Shahid Ali; Zahoor Ahmad; Rana Muhammad Irfan; Guocong Liu; Muhammad Bilal Akbar; Muhammad Abdul Qayyum (Journal of Environmental Chemical Engineering, 2025)

Ru-atom clusters embedded in Ti3C2Tx lattice for enhanced ammonium ion storage - Xiaofeng Zhang; Muhammad Sufyan Javed; Salamat Ali; Wei Xu; Peiao Lu; Awais Ahmad; Ammar M. Tighezza; Weihua Han; Kui-Qing Peng (Chemical Engineering Journal, 2025)

Remarkable energy storage performance in lead-free tungsten bronze ferroelectrics for high temperature applications - Muhammad Fahad Riaz; Fayaz Hussain; Ali Dad Chandio; Zeshan Javed; Wenfeng Yue; Zhenhao Fan; Yuxiao Du; Bingsen Wang; Mohammad Abu Abdeen; Gulmurza Abdurakhmanov; Adil Alshoaibi; Yasemin Tabak; et al. (Chemical Engineering Journal, 2025)

Upcycling waste PET into benzoxazines with simultaneously low curing temperatures and high thermal stability - Dula Daksa Ejeta; Meng-Xuan Li; Yu-Kuan Hsu; Muhammad Javed Iqbal; Ching-Hsuan Lin (Chemical Engineering Journal, 2025)

Interactions between micro(nano)plastics and natural organic matter: implications for toxicity mitigation in aquatic species - Naima Hamid; Marriya Sultan; Muhammad Junaid; Stuart Cairns; Iain Robertson; Houda Javed; De-Sheng Pei (Aquatic Toxicology, 2025)

The generative adversarial neural network with multi-layers stack ensemble hybrid model for landslide prediction in case of training sample imbalance - Wajid Hussain; Hong Shu; Hasnain Abbas; Sajid Hussain; Isma Kulsoom; Saqib Hussain; Hajra Mustafa; Aftab Ahmed Khan; Muhammad Ismail; Javed Iqbal (Stochastic Environmental Research and Risk Assessment, 2025)

Effect of pollen sources on biochemical indices and hybrid authentication in date palm (Phoenix dactylifera L.) cv. Khadrawy - Maryam; Ishtiaq Ahmad; Muhammad Nafees; Muhammad Saqib; Mona S. Alwhibi; Mohamed S. Elshikh; Mehmet Ramazan Bozhuyuk; Javed Iqbal; Shabir Ahmad; Trobjon Makhkamov; Ghulam Murtaza; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Levilactobacillus brevis MW362790 and Pediococcus pentosaceus MT323062 Alleviate Cadmium-Induced Oxidative Stress and Hepato-renal Toxicity - Mamoona Hameed; Saman Javed; Najma Arshad; Zaman Gul; Maria Mushtaq; Aneela Munir; Kiran Shazadi; Muhammad Arshad; Saleha Noureen (Current Microbiology, 2025)

From metabolic dysregulation to neurodegenerative pathology: the role of hyperglycemia, oxidative stress, and blood-brain barrier breakdown in T2D-driven Alzheimer’s disease - Ahmad Raza; Shafaq Saleem; Samar Imran; Sarah Rahman; Muhammad Haroon; Azeen Razzaq; Ahmad Hussain; Javed Iqbal; Brijesh Sathian (Metabolic Brain Disease, 2025)
Type 2 Diabetes (T2D) and Alzheimer’s Disease (AD) share common risk factors that can be seen through T2D nearly doubling an individual’s likelihood of developing AD. Some AD patients show signs of metabolic dysfunction as well. This review focuses on the potential mechanisms associated with these two diseases, like insulin resistance, inflammation, oxidative damage, mitochondrial injury, and cell death. One of the notable elements in this connection is the “brain insulin resistance,” most frequently named as “type 3 diabetes,” which impairs glucose metabolism and facilitates amyloid beta (Aβ) plaque synthesis while reducing the action of insulin-degrading enzyme (IDE). Moreover, the overactivity of glycogen synthase kinase-3 beta (GSK-3β) also triggers taurine protein pathology. Raised concentrations of glucose in blood can produce advanced glycation end products (AGEs), which further exacerbate neuroinflammation in tandem with the mitigation of neurotoxic Aβ oligomers. Inflammation and subsequent damage to mitochondria lead to the dissolution of synapses. Current vascular insults include the breakdown of the blood-brain barrier (BBB) and decreased brain perfusion, along with other contributory factors to conditions conducive to neurotoxicity. Recently, novel therapies are emerging, including GLP-1 agonists, intranasal insulin, and mitochondrial antioxidants, that show surprising results for treating both conditions, but on the contrary, bioavailability and the timing of interventions remain a big challenge in the management of these diseases. Eventually, further research should center on understanding the mechanisms of integration along with the development of molecular biology, neuroimaging, and outcome-driven treatment strategies. Comprehensive strategies that exist between T2D-AD for integration and preservation of brain and metabolic health are addressed in this review. Graphical abstract

Sulphur Nutrition Improves Plant Growth Performance Against a Specialist Herbivore by Eliciting Phenolic Defense and Nutrient Induction in Rapeseed - Muhammad Wajid Javed; Dilbar Hussain; Muhammad Hasnain; Mubshar Hussain; Imran Ali (Journal of Plant Growth Regulation, 2025)

Prevalence and integrated risk assessment of antibiotics from River Chenab Pakistan; human and ecotoxicological prospectives - Aqeel Mahmood; Hafiz Muhammad Irfan; Alamgeer; Zeeshan Javed; Adeel Mahmood (Science of The Total Environment, 2025)

Sustainable kaolin-crosslinked kappa-carrageenan hydrogel as an efficient adsorbent for cationic dye removal from wastewater - Fekri Abdulraqeb Ahmed Ali; Javed Alam; Ahmed S. Al-Fatesh; Farid Fadhillah; Badr M. Thamer; Muhammad Ali Shar; Mansour Alhoshan (Journal of Water Process Engineering, 2025)

Predicting Wheat Grain Yield Through Morphometric Analysis of Seed Dimensions Using Computational Imaging Techniques - Mahnoor; Muhammad Jamil; Aamir Ali; Tauseef Anwar; Huma Qureshi; Muhammad Tahir Naseem; Gadah Albasher; Mohammad Javed Ansari (Plant Molecular Biology Reporter, 2025)

The Role of Silver Nanoparticles and Bacillus subtilis in Modulating Morpho–Physio–Biochemical Responses in Wheat (Triticum aestivum L.) Under Arsenic Stress - Mohammad K. Okla; Sadia Javed; Muhammad Faran Tahir; Ibrahim A. Saleh; Muhammad Anas; Muhammad Hamzah Saleem; Temoor Ahmed; Abdulrahman Abdullah Alatar; Bandar M. AlMunqedhi; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)
Soil contamination with toxic heavy metals [such as arsenic (As)] is becoming a serious global problem because of the rapid development of the social economy. Although plant growth-promoting rhizo-bacteria (PGPR) and nanoparticles (NPs) are the major protectants to alleviate metal toxicity, the study of these chemicals in combination to ameliorate the toxic effects of As is limited. Therefore, the present study was conducted to investigate the effects of different levels of Bacillus subtilis (5 and 10 mg L –1 ) and silver (Ag)–NPs (10 and 20 mg kg –1 ) on morpho-physiological and antioxidative defense attributes, which was spiked with different levels of As [0 mM (i.e., no As), 100, and 200 mg kg –1 ] in wheat ( Triticum aestivum L.) seedlings. Results from the present study showed that the increasing levels of As in the soil significantly ( P < 0.05) decreased plant growth and biomass, photosynthetic pigments, gas exchange attributes, sugars, and nutritional contents from the roots and shoots of the plants. In contrast, increasing levels of As in the soil significantly ( P < 0.05) increased oxidative stress indicators in term of malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), and electrolyte leakage (EL), and also increased organic acid exudation patter in the roots of T. aestivum . The negative impact of As toxicity can overcome the application of B . subtilis and Ag − NPs, which ultimately increased plant growth and biomass by capturing the reactive oxygen species (ROS), and decreased oxidative stress in T. aestivum by decreasing the As contents in the roots and shoots of the plants. Research findings, therefore, suggest that the combined application of B . subtilis and Ag − NPs can ameliorate As toxicity in T. aestivum , resulting in improved plant growth and composition under metal stress, as depicted by balanced exudation of organic acids. Graphical Abstract

The Effect of Native Plant Diversity on the Success of Invasive Species in Polluted Soils - Qaiser Javed; Jianfan Sun; Marko Černe; Babar Iqbal; Mohammed Bouhadi; David John Heath; Feng He; Muhammad Saif Ullah; Rasheed Akbar; Daolin Du (Ecotoxicology, 2025)

Metabolic Heat Output of Chondrocytes: Implications for Joint Degeneration in Osteoarthritis - Ayesha Parvaiz Malik; Amna Pervez Malik; Javed Iqbal; Brijesh Sathian; Syed Muhammad Ali (Annals of Biomedical Engineering, 2025)

Organic solvent assisted hydrothermal processing of cooked rice to get insights into the evolution of chemical structure of hydrochar - Sobia Kousar; Kanwal Javed; Bushra Begum; Muhammad Mahboob Naeem; Shu Zhang; Xun Hu (Waste Management, 2025)

Machine learning-driven prediction of Visual Range under changing climate conditions over complex terrain using AOD and CMIP6 climate simulations - Sadaf Javed; Muhammad Imran Shahzad; Muhammad Zeeshaan Shahid; Jun Wang; Imran Shahid (Remote Sensing Applications: Society and Environment, 2025)

Boosted wound healing and anticancer potential of polymer functionalized cerium oxide nanomaterials - Muhammad Khawar Abbas; Yasir Javed; Naveed Akhtar Shad; Azhar Rasul; Amna Bashir; Syed Fazil Bin Farukh; Heba Taha Abdulghani; Wasim Abbas; Aisha Sethi; Muhammad Ramzan Khawar; Dongwhi Choi (Journal of Trace Elements in Medicine and Biology, 2025)

Occurrence, Distribution and Ecological Health Risk Assessment of Heavy Metals Through Consumption of Drinking Water in Urban, Industrial, and Mining Areas of Semi − Arid to Humid Subtropical Areas - Irfan Ullah; Muhammad Adnan; Javed Nawab; Irfan Safi; Sardar Khan (Journal of Geochemical Exploration, 2025)

Impact of environmental awareness due to the COVID-19 pandemic on consumers’ intention to purchase electric vehicles: the mediating roles of rational and non-rational factors - Muhammad Kashif Javed; Antonio Capaldo; Talat Qadeer; Aqsa Manzoor (Journal of Cleaner Production, 2025)

OhmNet: Advanced neural network-based viscosity prediction of sauces for efficient Ohmic heating processing - Tasmiyah Javed; Muhammad Akmal; Timofei Breikin; Caroline Millman; Hongwei Zhang (Innovative Food Science & Emerging Technologies, 2025)

Flower-like nanoscale Ni(OH)2/MnCO3 electrocatalyst for efficient hydrogen evolution reaction in wide pH range - Zobia Siddique; Salman Noshear Arshad; Muhammad Ali Ehsan; Faryal Aftab; Akhtar Munir; Suryyia Manzoor; Sadia Fatima; Farah Sajjad; Javed Ahmad; Hatice Duran; Senem Çitoğlu (Fuel, 2025)

Effect of MXenes, nZVI and Acacia-wood Biochar Treatments on Bioavailability Pb and Fractions in Calcareous-polluted Soils - Ghulam Murtaza; Najmaldin Ezaldin Hassan; Muhammad Usman; Gang Deng; Zeeshan Ahmed; Javed Iqbal; Mohamed S. Elshikh; Humaira Rizwana; Rashid Iqbal (Water, Air, & Soil Pollution, 2025)

Exploring evolutionary perspectives and antibiogram analysis of biofilm-forming Staphylococcus aureus in goat mastitis - Muhammad Umar Javed; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Ali Abdullah Jabir; Maria Batool; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2025)

Synergistic inoculation of diazotrophic Pseudomonas and Bacillus spp. in mitigating salt-drought stress in Cicer Arietinum L. via phytohormonal modulation and antioxidant pathways - Najeeba Parre Pakar; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Plant and Soil, 2025)

Adsorptive Remediation of Cadmium Ions with Modified Plant Straw Using Response Surface Methodology - Aanisa Manzoor Shah; Inayat Mustafa Khan; Rehana Rasool; Tahir A. Sheikh; Muhammad Athar Khaliq; Shaista Nazir; Javid A. Bhat; Yasir Hanif Mir; Rifat un Nissa; Sami Al Obaid; Mohammad Javed Ansari; Shafeeq Ur Rahman (International Journal of Environmental Research, 2025)

Cyto-genotoxic assessment of bisphenol P through expression of DNA damage/repair genes in MDBK cell line - Muhammad Muddassir Ali; Samra Afzal; Maryam Javed; Imran Rashid; Furqan Awan; Asad Ullah; Tanveer Majeed; Hadeer Darwish; Ahmed Noureldeen; Jawaher Albaqami; Khalid Mehmood (In Vitro Cellular & Developmental Biology - Animal, 2025)

Phytoremediation potential of native medicinal plant species in mining degraded soil of Mohmand Northwest Pakistan - Irfan Ullah; Seemab Akhtar; Muhammad Adnan; Javed Nawab (Environmental Monitoring and Assessment, 2025)

Adaptive responses of trees to industrial pollution: modulation of leaf anatomical, physio-biochemical, and heavy metal accumulation traits in urban biotopes - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Mansoor Javaid; Usman Zulfiqar; Nafosat Djonibekova; Anarjan Matkarimova; Hesham S. Almoallim; Mohammad Javed; Shafeeq Ur Rahman (Environmental Monitoring and Assessment, 2025)

Radon measurements in soils and building materials of Kashmir - Sobia Riaz; Misbah Javed; Muhammad Rashad Khan; Muhammad Khawaja Rafique Mir; Carlo Sabbarese (Isotopes in Environmental and Health Studies, 2025)

Advancements in the production methods and recycling of multilayer plastics with sustainable applications: A comprehensive review - Maha Awjan Alreshidi; Krishna Kumar Yadav; G. Shoba; Amel Gacem; S. Padmanabhan; T. Vinod Kumar; Ahmed M. Fallatah; Javed Khan Bhutto; Fahad M. Aldosari; Manawwer Alam; Muhammad A. Abo El-Khair; P. Tamizhdurai; et al. (Chemical Engineering Journal, 2025)

Seismic evaluation and strengthening of an RC building using different retrofit techniques in earthquake-prone region of Pakistan - Obaidullah Khan; Muhammad Faisal Javed; Adeel Zafar; Sanaullah Khan (Innovative Infrastructure Solutions, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Sustainable development at the crossroads: Navigating eco-humanism and eco-modernism - Muhammad Hassan Javed; Anees Ahmad; Abdul-Sattar Nizami; Massimo Gastaldi; Idiano D'Adamo (Current Opinion in Green and Sustainable Chemistry, 2025)

Recent advances in synthesis and modulation of 2D heterostructures for sensing and detection applications - Rumaisa Tariq; Waseem Raza; Karma M. Albalawi; Arshad Hussain; Munir Ahmad; Muhammad Asim Mushtaq; Mohamed H. Helal; Ibrahim A. Shaaban; Shaukat Khan; Muhammad Sufyan Javed (Chemical Engineering Journal, 2025)

Interesterification of waste cooking oil via microwave irradiation for glycerol-free biodiesel production - Muhammad Umer Qadeer; Muhammad Ayoub; Muhammad Hamza Nazir; Muhammad Asad Javed; Zulqarnain; Imtisal Zahid; Mariam Ameen; Farooq Sher; Alhassan Ibrahim (Biomass and Bioenergy, 2025)

Exploring the Role of Plant Growth-Promoting Bacteria in Biodegradation of Plastic: A Review - Haris Maqbool; Fazal Ur Rehman; Izhar Khan; Nadeem Ullah; Muhammad Anwar Sajad; Nazir Mohammad; Maria Kalsoom; Shafiq Ur Rehman; Muhammad Farooq Hussain Munis; Malka Saba; Hassan Javed Chaudhary (Water, Air, & Soil Pollution, 2025)

Development and in vitro tuning of empagliflozin-containing dissolvable microneedle patch for enhanced transdermal delivery - Aqib Javed; Rai Muhammad Sarfraz; Asif Mahmood; Zulcaif Ahmad; Muhammad Rouf Akram; Hira Ijaz; Shammas Ali; Anam Shahzadi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Characteristics of aerosols and planetary boundary layer dynamics during biomass burning season - Muhammad Zeeshaan Shahid; Muhammad Imran Shahzad; Sundas Jaweria; Sadaf Javed; Shah Zaib; Imran Shahid (Natural Hazards, 2025)
The northeastern region of Pakistan (NEP) has experienced increased haze episodes over the past decade, primarily due to enhanced biomass burning activities during the post-monsoon season. Economic growth, urbanization and industrial development also controbuted to high pollutants levels that leads to decline in air quality and visibility. These elevated pollution levels over NEP (69–75.5°E, 27.4–34°N) are influenced by both meteorological conditions and anthropogenic activities. This study investigates aerosol concentrations before, during, and after the haze episode during November 2021 using model simulations and remote sensing data. The Modern-Era Retrospective Analysis for Research and Applications, version 2 (MERRA-2), along with satellite observations from the Moderate Resolution Imaging Spectroradiometer (MODIS), are used for validation and analysis of this haze episode. The results illustrate the key contributors to this haze event and showed the there is significant increases in aerosol components such as sulfate, black carbon, organic carbon, dust and aerosol optical depth (AOD). The planetary boundary layer (PBL) height, measured with Ceilometer LIDAR, showed decreasing trend in height from October to December that support aerosol accumulation near the surface during the the month of November. This month is also biomass burning, crop residue burning, season in the region. These haze episodes also impacts the atmospheric visibility that dropped below 2 km in November. These findings provide key insights into the complex interactions between meteorology, emissions, and haze formation in NEP region, and will provide policy makers to design effective mittigation strategies.

Silicon-mediated Nutrient Deterrence Could Reduce Aphid (Brevicoryne brassicae L.) Abundance and Improve Crop Yield by Eliciting Phenolic Defense in Canola (Brassica napus L.) - Muhammad Wajid Javed; Mansoor-ul -Hasan; Muhammad Sagheer; Shahbaz Talib Sahi (Journal of Soil Science and Plant Nutrition, 2025)

Synergistic Application of Biochar and Bio-Organic Phosphate Enhances Drought Tolerance in Maize by Modulating Antioxidant Defense and Reducing Oxidative Stress - Ghulam Sarwar; Zainab Zahra; Tauseef Anwar; Huma Qureshi; Faizan Khalid; Muhammad Waqar Hassan; Muhammad Younus; Muhammad Sajid-ur-Rehman; Huma Rao; Faisal Shahzad; Wajid Zaman; Mansour Shrahili; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Combined Impact of Waste Water and Farm Yard Manure on Growth of Tomato (Solanum lycopersicum L.) and Soil Health: A Sustainable Agriculture Approach - Arsalan Saghir; Muhammad Sohail Akram; Shahzad Ali; Shahla Rashid; Muhammad Ajmal Farhad; Hafiz Muhammad Tayyab Khan; Syed Ayyaz javed; Mohammad Raish; Muhammad Khubaib (Journal of Soil Science and Plant Nutrition, 2025)

Individual and Combinatorial Applications of Arbuscular Mycorrhizal Fungi and Plant Growth-Promoting Rhizobacteria Increase Morpho-Physio-Biochemical Responses in Rice (Oryza sativa L.) under Cadmium Stress - Arwa Abdulkreem AL-Huqail; Aishah Alatawi; Sadia Javed; Muhammad Faran Tahir; Muhammad Anas; Muhammad Hamzah Saleem; Temoor Ahmed; Mohammed O. Alshaharni; Eman Fayad; Khalid Ali Khan; Awais Khalid; Shafaqat Ali; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Biochar and Pseudomonas aeruginosa M2 Co-Application: A Sustainable Strategy for Enhancing Growth and Heavy Metal Tolerance in Brassica campestris - Muhammad Muzammil Mukhtar; Qasim Ali; Muhaimen Ayyub; Muhammad Aon; Hayssam M. Ali; Sadaf Oranab; Iftikhar Ahmad; Ghulam Abbas; Behzad Murtaza; Waqas Mohy-Ud-Din; Usman Zulfiqar; Muhammad Faisal Maqsood; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Fe-Modified Biochar Improves Tobacco Productivity by Promoting Root Growth, Plant Biochemical Traits and Nicotine Level: A Three Years Field Study - Ghulam Murtaza; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Mona S Alwahibi; Humaira Rizwana; Javed Iqbal; Muhammad Qasim; Rashid Iqbal; Gang Deng (Journal of Soil Science and Plant Nutrition, 2025)

Exploring the hidden world of muskmelon miRNAs: experimental hunts of computational predicted miRNAs and their protein targets - Abdul Ghaffar; Naqeebullah Khan; Irshad Ali; Attiq ur Rehman; Samiullah; Waheed Ahmed Shah; Muhammad Javed Khan (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Genetic characterization of selected species of family Solanaceae based on chloroplast rps14 gene - Sitara Bibi; Javed Iqbal; Banzeer Ahsan Abbasi; Sobia Kanwal; Tariq Mahmood; Muhammad Waseem; Dunia A. Al Farraj; Mohamed S. Elshikh; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Molecular characterization and drug resistance pattern in pol gene of HIV-1 sub-subtypes circulating in Lahore, Pakistan - Akmal Zubair; Adnan Zeb; Syed Ahsan Shahid; Hasnain Javed; Muhammad Ali (Virus Genes, 2025)

Induced resistance and nutrient deterrence reduce aphid reproduction and improve crop yield, phenolic defense, and economic benefits of canola (Brassica napus L.) in the field - Muhammad Wajid Javed; Mansoor-Ul-Hasan; Muhammad Sagheer; Shahbaz Talib Sahi (Arthropod-Plant Interactions, 2025)

Optimizing modified ecological compositions enables eco-friendly control of Tribolium castaneum in grain storage - Muhammad Mohsan; Zahid Mahmood Sarwar; Habib Ali; Inzamam Ul Haq; Ammara Riaz; Rashid Iqbal; Gadah Albasher; Mohammad Javed Ansari (International Journal of Tropical Insect Science, 2025)

Transgenerational Impact of nicotiana tabacum extract on musca domestica (diptera: muscidae) - Muhammad Jamshed Iqbal; Zhihang Zhuo; Inzamam Ul Haq; Yasir Niaz; Basharat Ali; Ammara Riaz; Habib Ali; Rashid Iqbal; Gadah Albasher; Mohammad Javed Ansari (International Journal of Tropical Insect Science, 2025)

Exogenous applications of humic acid and salicylic acid differentially affect biomass accumulation and production of rare pharmacologically active withanolides in in vitro cultures of Withania coagulans - Mehnaz Khanum; Muhammad Uzair Javed; Sannia Batool; Gouhar Zaman; Muhammad Naeem Bajwa; Anisa Andleeb; Laurine Garros; Samantha Drouet; Duangjai Tungmunnithum; Christophe Hano; Bilal Haider Abbasi; Nathalie Giglioli-Guivarc’h (Plant Biosystems, 2025)

Shaping sustainable tourism: the influence of norms and social media rumors on tourist behavior - Muhammad Kashif Javed; Muhammad Sohail Tahir; Antonio Capaldo; Jamil Ahmad; Allah Wasaya; Affan Uddin Ahmed; Muhammad Irfan Chani (Environment, Development and Sustainability, 2025)

Carrageenan based edible coating modulates oxidative stress and delays cell wall polysaccharides disassembly in harvested grapefruit - Sajid Ali; Sidra Riaz; Hafiz Umer Javed; Ahmad Sattar Khan; Maratab Ali; Safina Naz; Hasan Sardar; Muhammad Shahzad Saleem (Journal of Stored Products Research, 2025)

Unpacking organizational capabilities and green Innovation for sustainable Performance: The role of environmental regulations in manufacturing industry - Hasnain Javed; Jianguo Du; Muhammad Farooq Islam (Journal of Cleaner Production, 2025)

Uncertainty quantification for variational Bayesian dropout based deep bidirectional LSTM networks - Iqra Sardar; Farzana Noor; Muhammad Javed Iqbal; Ahmed Alsanad; Muhammad Azeem Akbar (Stochastic Environmental Research and Risk Assessment, 2025)

Exploring melatonin’s influence on secondary metabolism of Echinacea purpurea callus cultures - Tehreem Mahmood; Muhammad Uzair Javed; Gouhar Zaman; Bushra Khan; Negin Zarei; Cécile Abdallah; Christophe Hano; Johan-Owen De Craene; Arnaud Lanoue; Bilal Haider Abbasi; Nathalie Giglioli-Guivarc’h (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Correction: Development of prediction models for strength properties of concrete using gene expression programming - Asad Ullah Khan; Muhammad Faisal Javed; Majid Khan (Innovative Infrastructure Solutions, 2025)

Rhizospheric bacterial strain Pseudomonas putida and fungal strain Penicillium chrysogenum alleviate Fusarium wilt of tomato by improving key growth attributes - Hassaan Ateeb Ahmad; LNU Farhana; Urooj Haroon; Hira Saleem; Maryam Anar; Mahnoor Akbar; Kanwal Abbasi; Abdul Rehman; Mohammad Sameer Zubair; Asif Kamal; Hassan Javed Chaudhary; Rattandeep Singh; et al. (European Journal of Plant Pathology, 2025)

Weissella confusa MW051433 Mitigates Hypercholesterolemia by Biliary Cholesterol Excretion: The In Vivo Evidence - Saman Javed; Zakia Latif; Ghulam Ayesha Javed; Aneela Munir; Maria Mushtaq; Mamoona Hameed; Muhammad Arshad; Najma Arshad (Current Microbiology, 2025)

Impact of End-capped Acceptor Modification in Anthanthrone-Based D-π-A Type Donor Materials for Organic and as Hole Transporting Materials for Perovskite Solar Cells - Nabeel Shahzad; Shahzad Ali Shahid Chatha; Riaz Hussain; Shahid Hussain; Javed Iqbal; Muhammad Adnan (Journal of Fluorescence, 2025)

Assessment of water quality and occurrence of multidrug-resistant clinically relevant bacteria in drinking water in the twin cities of Pakistan - Nudrat Nadeem; Muhammad Nadeem; Nazish Bostan; Sadia Sattar; Roger Simm; Sundus Javed (Environmental Monitoring and Assessment, 2025)
Water filtration plants are a main source of drinking water for local populations in almost all big cities of Pakistan but these filtration plants are ineffective in eliminating contaminants from water. This study was conducted to evaluate water quality with specific focus on physicochemical parameters and bacterial contamination including occurrence of multidrug-resistant bacteria in drinking water collected from filtration plants ( N = 64) of the twin cities of Pakistan. Physicochemical parameters were analyzed following American Public Health Association standard guidelines and total coliform count was determined using membrane filtration method. Gram-negative bacteria were isolated and characterized in terms of species and antibiotic susceptibility. Elevated levels of total dissolved solids, nitrates, total coliforms, lead and copper were found in several samples. Multivariate correlation coefficient revealed significant positive correlation between nitrate levels and total coliform count in bacteriologically contaminated samples. Antibiotic resistance patterns revealed multidrug-resistant and extensively drug-resistant bacteria with high resistance against third generation cephalosporins. Our results highlight the urgent need for improved water filtration processes and regular monitoring to provide safe drinking water to the local community.

Heavy metal contamination in some commercial marine fishes of Pakistan - Sania Riaz; Muhammad Javed Khan; Iqra Rani; Asad Ali; Muhammad Asghar Qazi; Mehnoor Sameer; Khadija; Nimra Hussain; Shahid Sherzada (Food Additives & Contaminants Part B-Surveillance, 2025)

First report of Botryosphaeria wangensis, Colletotrichum nymphaeae, Diaporthe eres, and Geotrichum candidum causing postharvest fruit rot of plums (Prunus salicina) in China - Yu-Ru Wang; Bo-Ying Huang; Hafiz Muhammad Usman; Khadija Javed; Fatimah Al-Otibi; Kevin D. Hyde; Yong Wang (Crop Protection, 2025)

Ethylene precursor, 1-amino cyclopropane-1-carboxylic acid, induced distinct morpho-physio-biochemical improvements to cadmium-stressed mungbean (Vigna radiata L.) - Aneeqa Munawar; Muhammad Tariq Javed; Nudrat Aisha Akram; Sadia Zafar; Muhammad Sohail Akram (South African Journal of Botany, 2025)

Prediction of nitrate concentration and the impact of land use types on groundwater in the Nansi Lake Basin - Javed Iqbal; Chunli Su; Hasnain Abbas; Jiaqi Jiang; Zhantao Han; Muhammad Yousuf Jat Baloch; Xianjun Xie (Journal of Hazardous Materials, 2025)

Textile wastewater treatment by heterogeneous catalytic ozonation using microcellulose loaded ZIF 67 catalyst - Muhammad Fahad Tariq; Farhan Javed; Luigi Rizzo; Muhammad Wasim Tahir; Amir Ikhlaq (Journal of Environmental Management, 2025)

Effect of GnRH administration on follicular development and ovulation during the early luteal phase in subtropical goats - Waqas Ahmad; Muhammad Irfan-ur-Rehman Khan; Amjad Riaz; Khalid Javed (Domestic Animal Endocrinology, 2025)

Arsenic speciation in soil from urban recreational parks and human health risk assessment - Muhammad Amjad Khan; Javed Nawab; Tasneem Sarwar; Anwarzeb Khan; Iqbal Ahmad; Muhammad Waqas; Shah Nawaz Khan; Mehboob Alam; Kalsoom Kalsoom; Muhammad Ziad; Sardar Khan (Urban Ecosystems, 2025)

Biotechnological techniques for sugarcane crop improvement, applications and challenges - Tayyba Batool; Rana Waqar Ali; Muhammad Nawaz; Shahbaz Khan; Kashf Mehmood; Ahmad Hassan; Makky Javed; Waqas Jamil (Journal of Crop Science and Biotechnology, 2025)

Biological Approaches to Sustainable Management of Fusarium Wilt in Cotton - Iqra Javed; Muhammad Arslan Khan; Hasan Riaz; Shafqat Saeed; Muhammad Sajid; Muhammad Bashair; Zulqarnain Abbas; Haider Ali; Munirah Abdullah Al-Dosary; Muhammad Bilawal Junaid (Journal of Crop Health, 2025)

Protective Effects of Multiple-Chemical Engineered Biochar On Hormonal Signalling, Antioxidant Pathways and Secondary Metabolites in Lavender Exposed to Chromium and Fluoride Toxicity - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Qamar uz Zaman; Gang Deng; Suiyun Chen; Mona S. Alwahibi; Humaira Rizwana; Javed Iqbal; Shabir Ahmad; Rashid Iqbal (Journal of Crop Health, 2025)

Heavy Metal Concentrations in Water, Sediment, and Fish Species in Chashma Barrage, Indus River: A Comprehensive Health Risk Assessment - Khalid Hussain Rind; Sonia Aslam; Nazakat Hussain Memon; Asif Raza; Muhammad Qamar Saeed; Alia Mushtaq; Javed Ahmed Ujan; Syed Fahad Habib; Salim S. Al-Rejaie; Mohamed Mohany (Biological Trace Element Research, 2025)

Spatiotemporal patterns of pesticide residues in intensive agricultural soil and water bodies in Shaheed Benazirabad, Pakistan - Najeeba Parre Pakar; Kelly Redeker; Muhammad Farooq Husain Munis; Hassan Javed Chaudhary (Environmental Monitoring and Assessment, 2025)

Immunoprotective potential of egg yolk antibodies (IgYs) in controlling necrotic enteritis in broiler chickens - Zain Ul Abadeen; Muhammad Tariq Javed; Tariq Jamil; Syed Muhammad Faizan (Veterinary Immunology and Immunopathology, 2025)

Synthetic bacterial communities regulate polyamine metabolism and genes encoding antioxidant defense system to enhance arsenic tolerance of rice - Hamad Khan; Zeeshan Khan; Ishmal Eman; Ijaz Ahmad; Tariq Shah; Guoping Wang; Lu Feng; Abdullah A. Alarfaj; Sulaiman Ali Alharbi; Muhammad Javed Ansari (South African Journal of Botany, 2025)

Biocatalytic application of chitosan-silver nanocomposite (Ch-AgNP) to reduce vascular colonization and induce wilt resistance in Brassica napus L. against both Fusarium oxysporum and Verticillium dahliae - Rabia Nawab; Mahnoor Akbar; Maryam Anar; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Physiological and Molecular Plant Pathology, 2025)

Visible light active CdS/CuO nanocomposites for photocatalytic degradation of ciprofloxacin, H2 production and antimicrobial activity - Naveed Akhtar; Chaejin Choi; Muhammad Ateeq; Perveen Fazil; Noor S. Shah; Javed Ali Khan; Abdullah G. Al-Sehemi; Amir Zada; Muhammad Ishaq Ali Shah; Rabia Ikram; Changseok Han (Chemical Engineering Journal, 2025)

Simultaneous generation of micropores and macropores via synergistic activation of peach wood with K2C2O4 and sodium salts for enlarging pore diameters - Sobia Kousar; Kanwal Javed; Bushra Begum; Muhammad Mahboob Naeem; Shu Zhang; Xun Hu (Biomass and Bioenergy, 2025)

Scenario-based HEC-RAS 2D unsteady flow analysis of Shisper Lake for GLOF risk assessment - Junaid Aziz Khan; Muhammad Qamar Javed Pirzada; Muhammad Fahim Khokhar (Natural Hazards, 2025)

Increasing Salinity and Cadmium Enhanced Leaf Membrane Damage and H2O2 Production Irrespective of Reduced Sodium and Cadmium Accumulation in Wheat (Triticum aestivum L.) - Sajid Masood; Muhammad Ashraf; Mubshar Hussain; M. Farooq Azhar; M. Zafar-ul-Hye; Omer Farooq; Muhammad Aon; M. Tariq Javed (Journal of Soil Science and Plant Nutrition, 2025)

Combating Mercury Stress in Spinach (Spinacia oleracea L.) with Zinc Oxide and Providencia Vermicola, Assessing Changes in Defense Mechanism and Organic Acid Exudation Patterns - Arwa Abdulkreem AL-Huqail; Aishah Alatawi; Sadia Javed; Muhammad Anas; Muhammad Hamzah Saleem; Awais Khalid; Khalid Ali Khan; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)

Development of prediction models for strength properties of concrete using gene expression programming - Asad Ullah Khan; Muhammad Faisal Javed; Majid Khan (Innovative Infrastructure Solutions, 2025)

RETRACTED ARTICLE: ArticleNoteMorphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Unveiling the genetic diversity and host specificities of rust: morphological and molecular characterization of Berberis species - Siraj Uddin; Javed Iqbal; Banzeer Ahsan Abbasi; Shumaila Ijaz; Ghulam Murtaza; Muhammad Waseem; Umar Masood Quraishi; Atman Adiba; Reem M. Aljowaie; Saeedah Musaed Almutairi; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Seismic behavior of RC frames with Choh-kat openings: a novel strut model approach - Shujaat Hussain Buch; Javed Ahmad Bhat; Muhammad Dilawar Bhat; Mohammad Iqbal Mirza (Bulletin of Earthquake Engineering, 2025)

Citrus phytochemicals as potential therapeutics against asiatic citrus psyllid and Candidatus Liberibacter asiaticus: targeting the tripartite interaction - Muhammad Awais; Muhammad Ali; Mohsin Javed; Faisal Hanif; Muhammad Nouman; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Ibrahim Jafri (Journal of Plant Pathology, 2025)

Unfolding the role of silicon dioxide nanoparticles (SiO2NPs) in inducing drought stress tolerance in Hordeum vulgare through modulation of root metabolic, nutritional, and hormonal profiles - Nadiyah M. Alabdallah; Khansa Saleem; Aisha Saud Al-Shammari; Saleha S. AlZahrani; Ali Raza; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Jean Wan Hong Yong (South African Journal of Botany, 2025)

Mycorrhizopshere bacteria alleviated arsenic toxicity by regulating organic acids, glyoxalase defense system, and metal transporters in soybean plants - Zeeshan Khan; Shahrukh Khan; Mansour I. Almansour; Muhammad Asad; Mohammad Javed Ansari; Hamad Khan; Ijaz Ahmad (South African Journal of Botany, 2025)

Carbon dioxide, global boiling, and climate carnage, from generation to assimilation, photocatalytic conversion to renewable fuels, and mechanism - Muhammad Khan; Xiaohui Sun; Amir Zada; Shohreh Azizi; Muhammad Ishaq Ali Shah; Javed Ali Khan; Ahmed H. Ragab; Mostafa A. Taher; Qumber Abbas; Changseok Han (Science of The Total Environment, 2025)

Retraction notice to Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review [FUEL][340][2023][127399] - Awais Ahmad; Shumila Shaheen; Saadat Majeed; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Sufyan Javed; Rafael Luque; Lalitha Gnanasekaran (Fuel, 2025)

Buckling behavior of orthotropic thin plates using analytical and machine learning methods - Salamat Ullah; Jincheng Zhang; Hu Bo; Jinghui Zhang; Muhammad Faisal Javed; Weiqiu Chen (Engineering Structures, 2025)

Unveiling the potential of Loigolactobacillus coryniformis BCH-4 to ameliorate drought stress in Zea mays L. - Anam Tariq; Mahwish Salman; Muhammad Arslan Ashraf; Muhammad Rizwan Javed; Abdul Tawab (World Journal of Microbiology and Biotechnology, 2025)

Implications of Heavy Metal Accumulation in Fish Feed, Water, Sediment, and Different Fish Species in a Polyculture System - Allah Bachayo Rajar; Zainab Malik; Javed Ahmed Ujan; Khalid Hussian Rind; Raqeeb Ullah; Saira Naz; Mujeeb Ullah; Muhammad Zahid; Khalid Khan; Khayyam Khayyam; Salim S. Al-Rejaie; Mohamed Mohany (Biological Trace Element Research, 2025)

Stripe rust resistance in historical wheat cultivars at seedling and adult plant stages and tagging effective resistance genes using molecular markers - Khawar Majeed; Muhammad Sufyan; Kainat Abbasi; Rafia Ahsan; Hadi Bux; Muhammad Zakria; Muhammad Fayyaz; Javed Iqbal Mirza; Mohsin Ali; Awais Rasheed; Zhonghu He (Journal of Plant Pathology, 2025)

Changing pattern of urban landscape and its impact on thermal environment of Lahore; Implications for climate change and sustainable development - Tahir Sattar; Nigar Fatima Mirza; Muhammad Asif Javed; Muhammad Nasar-u-Minallah; Shahid Malik (Environmental Monitoring and Assessment, 2025)

Remediation of textile wastewater by hybrid technique using ZIF-67 catalyzed ozonation coupled with electrocoagulation - Farhan Javed; Muhammad Fahad Tariq; Amir Ikhlaq; Hafiz Muhammad Shahzad Munir; Ali Altaee (Journal of Water Process Engineering, 2025)

Predictive modeling of emulsion stability and drop characteristics using machine learning: A study on surfactant influence and time dynamics - Hasnain Ahmad Saddiqi; Asmat Ullah; Zainab Javed; Qazi Muhammad Ali; Muhammad Bilal Jan; Iftikhar Ahmad; Farooq Ahmad (Food and Bioproducts Processing, 2025)

Optimization of Ti3C2T performance through synergistic enhancement of GeO /Ti3C2T heterostructures for ammonium-ion storage - Xinze Zhang; Muhammad Sufyan Javed; Hongjia Ren; Saima Batool; Awais Ahmad; Renqian Tao; Munirah D. Albaqami; Shaukat Khan; Xin Wang; Weihua Han (Chemical Engineering Journal, 2025)

The Impact of Acid Strength and Mineral Composition on Spontaneous Imbibition with Reactive Fluids - Muhammad Andiva Pratama; Hasan Javed Khan (Transport in Porous Media, 2025)
Capillary rise experiments are conducted in a set of calcareous and siliceous rocks with varying mineralogy and petrophysical properties to understand the coupled impact of reactivity and spontaneous imbibition. A capillary rise experiment is performed in each sample: first with deionized water, then with a dilute acidic solution, and finally again with deionized water, and the capillary rise profile for each is recorded. Pre- and post-acid petrophysical properties such as porosity, permeability, pore size distribution, and contact angle are measured for each sample. The mineral makeup of the rocks significantly influences how the acidic fluids penetrate the samples. The primary reactions are the dissolution of Ca- and Mg-rich minerals which alter the pore network. The higher acid strength results in higher capillary rise in calcareous rocks and results in an increase in the average pore size. The same pH acid results in lower capillary rise in the siliceous rocks, and a general decrease in the average pore size is observed. Changes in contact angle indicate increased water affinity in carbonate and reduced affinity in sandstone. The link between capillary interactions and fluid reactivity is often overlooked in fluid flow studies, and this research sheds light on the importance of reactivity during spontaneous imbibition, offering insights into dissolution and precipitation processes during capillary flow.

Probing the Complex Interaction of Makran Subduction Zone with Regional Tectonic Features: Insights from Gravity and Seismic Source Parameters - Raja Adnan Habib; Muhammad Tahir Iqbal; Mohammad Salam; Mohammad Tahir; Javed Iqbal; Talat Iqbal (Pure and Applied Geophysics, 2025)

Spore morphometric analysis in Sino-Himalayan and W-Himalayan Athyriaceae taxa: taxonomic insights and molecular phylogenetic comparison - Syed Nasar Shah; Mushtaq Ahmad; Mohammad Javed Ansari; Muhammad Nauman Khan; Majid Iqbal; Baber Ali; Sami Al Obaid (Genetic Resources and Crop Evolution, 2025)

An in-depth investigation of the nutraceutical value and medicinal perspectives of wild medicinal plants in Ojhor Valley, Hindukush Range, Chitral, Pakistan - Muhammad Nauman Khan; Barkat Ullah; Alevcan Kaplan; Sana Wahab; Baber Ali; Sami Al Obaid; Mohammad Javed Ansari (Genetic Resources and Crop Evolution, 2025)

Sublethal Concentrations of Cadmium and Lead: Effects on Hemato-Biochemical Parameters and Tissue Accumulation in Wallagu attu - Rim EL Amouri; Javed Ahmed Ujan; Asif Raza; Alia Mushtaq; Muhammad Qamar Saeed; Samrah Masud; Syed Sikandar Habib; Marija Milošević; Salim S. Al-Rejaie; Mohamed Mohany (Biological Trace Element Research, 2025)

Zinc-lysine and iron-lysine mitigate chromium toxicity in pearl millet (Pennisetum glaucum) through modulating photosynthetic and antioxidant system and inhibiting chromium uptake and translocation - Zaryab Ali Abbass; Maryam Zahra; Habib Ali; Muhammad Javed; Imran Mahmood; Mavadat Hussain Alvi; Alishba Waheed; Sadam Hussain; Sachin Kumar (Environmental Science and Pollution Research, 2024)

Revolutionizing Fingerprint Detection: Ce3+ Doped SiO2-Zr2O3:Sr2+ Nanocomposites with Enhanced Luminescence and Selectivity - Momna Qayyum; Sammia Shahid; Sana Mansoor; Muhammad Faizan; Mohsin Javed; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Salman Aloufi (Journal of Fluorescence, 2024)
Even though fingerprints remain one of the most reliable methods of identification, they are often lost during the recovery process. Accurate fingerprint recognition depends on the contrast between the ridges and substrate. On tough surfaces, such as glossy, colorful, and patterned materials, the contrast is harder to establish. Photoluminescent materials play a crucial role in forensic investigations as they enable the development of procedures that enhance image quality and increase the accuracy of findings from security institutions. Due to the strong emission in the red area at 620 nm, the use of trivalent Rare Earth ions (RE 3+ ) doped materials in this work is notable. Because of the unique properties and abundance of cerium, luminous materials based on SiO 2 -Zr 2 O 3 : Ce 3+ , Sr 2+ prepared via sol-gel technique present a more practical alternative for use in criminal investigations compared to current photonic materials. The sample was further co-doped with synthetic (Safranin-O and crystal violet) as well as organic (curcumin and lycopene) photoluminescent dyes. The nanocomposites were examined using X-ray diffraction analysis (XRD), energy-dispersive X-ray analysis (EDX), dynamic light scattering (DLS), scanning electron microscopy (SEM), and photoluminescence spectroscopy (PL). In conclusion, this work highlights the qualities critical to obtaining higher-resolution latent fingerprint images for potential forensic applications.

Optimization of hydrogen production using a coculture of Chlamydomonas reinhardtii and activated sludge bacteria - Abdelsalam Zidan; Muhammad Asad Javed; Ashraf Aly Hassan (Chemosphere, 2024)

Effect of differential exposure of UV-C and melatonin stress on the therapeutic potential of bioactive compounds in Moringa oleifera - Muhammad Naeem Bajwa; Gouhar Zaman; Muhammad Asad Ullah; Muhammad Uzair Javed; Anisa Andleeb; Christophe Hano; Bilal Haider Abbasi (South African Journal of Botany, 2024)

The role of selenium and biochar nanoparticles in alleviating cadmium stress in wheat (Triticum aestivum L.) examined via morphophysiological traits and organic acid exudation patterns - Mohammad K. Okla; Sahar Mumtaz; Sadia Javed; Muhammad Hamzah Saleem; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; Muhammad Adnan; Shafaqat Ali (South African Journal of Botany, 2024)

Potential of iron oxide-modified biochar in simultaneous mitigation of lead and nickel toxicity in wheat (Triticum aestivum L.) - Tufail Shah; Muhammad Kashif Irshad; Wasim Javed; Mahshab Sheraz; Atif Muhmood; Ali Noman; Maryam M. Alomran; Sang Soo Lee; Jianying Shang (South African Journal of Botany, 2024)

Mechanistic insight into interactive effect of microplastics and arsenic on growth of rice (Oryza sativa L.) and soil health indicators - Muhammad Kashif Irshad; Muhammad Aqeel; Saba Saleem; Wasim Javed; Ali Noman; Min Woo Kang; Noreen Khalid; Sang Soo Lee (Science of The Total Environment, 2024)

Changes monitoring in Hongjiannao Lake from 1987 to 2023 using Google Earth Engine and analysis of climatic and anthropogenic forces - Md. Enamul Huq; Xijun Wu; Akib Javed; Ying Dong; Bingbing Li; David Lopez-Carr; Jiang Wu; Jing Liu; Yaning Zhang; Fanping Zhang; Muhammad Riaz; Md. Nazirul Islam Sarker; et al. (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Leveraging machine learning to model salinity and water flux for improved insights into forward osmosis membrane bioreactors - Ali Aldrees; Bilal Siddiq; Wael S. Al-Rashed; Muhammad Faisal Javed; Majid Khan (Journal of Water Process Engineering, 2024)

Two-dimensional MXene based innovative electrode materials for supercapacitors: Recent advances and prospects - Salamat Ali; Muhammad Ahsan Farooq Qaisar; Muhammad Sufyan Javed; Khalid Umer; Saleh S. Alarfaji; Muhammad Mateen; Muhammad Chhattal; Shafqat Ali; Anand Parkash; Tensangmu Lama Tamang; Jing Qi (Fuel, 2024)

Soy protein-polyphenols conjugates interaction mechanism, characterization, techno-functional and biological properties: An updated review - Muhammad Faisal Manzoor; Xin-An Zeng; Muhammad Waseem; Rabia Siddique; Muhammad Rizwan Javed; Deepak Kumar Verma; Murtaza Ali (Food Chemistry, 2024)

Fabrication and characterization of bioactive curdlan and sodium alginate films for enhancing the shelf life of Volvariella volvacea - Asif Ali Khan; Feng-Jie Cui; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Syed Asim Shah Bacha; Zheng-Zi Ying; Ismail Khan; Umar Zeb; Abdullah A. Alarfaj; Mohammad Javed Ansari; Yan Yang; et al. (Food Bioscience, 2024)

RETRACTED: Hydrogeochemical properties, source provenance, distribution, and health risk of high fluoride groundwater: Geochemical control, and source apportionment - Muhammad Ayub; Hira Javed; Abdur Rashid; Wardah Hayat Khan; Asif Javed; Tariq Sardar; Ghulam Mujtaba Shah; Ajaz Ahmad; Jörg Rinklebe; Parvaiz Ahmad (Environmental Pollution, 2024)

Interactive effects of melatonin and salicylic acid on Brassica napus under drought condition - Noman Rafique; Noshin Ilyas; Muhammad Aqeel; Naveed Iqbal Raja; Ghulam Shabbir; Muhammad Ajaib; R. Z. Sayyed; Sulaiman Ali Alharbi; Mohammad Javed Ansari (Plant and Soil, 2024)

Biomass and polyphenolic enhancement in date palm (Phoenix dactylifera L.) callus cultures through Fusarium oxysporum elicitation - Huda Enaya Mahood; Virginia Sarropoulou; Thiresia-Teresa Tzatzani; Muhammad Uzair Javed; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Zebrafish as an innovative model for exploring cardiovascular disease induction mechanisms and novel therapeutic interventions: a molecular insight - Shaukat Ali; Maryam Zulfiqar; Muhammad Summer; Mahnoor Arshad; Shehzeen Noor; Laiba Nazakat; Abdullah Javed (Molecular Biology Reports, 2024)

Breeding for water-use efficiency in wheat: progress, challenges and prospects - Aqsa Hafeez; Shehzad Ali; Muhammad Ammar Javed; Rashid Iqbal; Muhammad Nauman Khan; Fatih ÇIĞ; Ayman EL Sabagh; Turki Abujamel; Steve Harakeh; Sezai Ercisli; Baber Ali (Molecular Biology Reports, 2024)

Nitrogen and carbohydrate metabolisms are key factors in maize (Zea mays L.) germination under chromium-induced ROS - Muhammad Imran Atta; Syeda Sadaf Zehra; Zhihang Zhuo; Habib Ali; Malik Waseem Abbas; Syed Naveed Abbas; Sadia Sarwar; Fatima Muneer; Irfan Ahmad; Danpping Xu; Hasham S. Almoallim; Mohammad Javed Ansari (Journal of Plant Diseases and Protection, 2024)

Phosphorus sources enhance barley growth and mitigate lead stress via antioxidant responses, proline metabolism, and gene expression - Manar Fawzi Bani Mfarrej; Sadia Javed; Rafa Almeer; Rawidh Alsaidalani; Mohamed Kamel; Muhammad Hamzah Saleem; Shafaqat Ali (South African Journal of Botany, 2024)

Optimizing plastic waste inclusion in paver blocks: Balancing performance, environmental impact, and cost through LCA and economic analysis - Usama Asif; Muhammad Faisal Javed (Journal of Cleaner Production, 2024)

Integrated assessment of groundwater quality dynamics and Land use/land cover changes in rapidly urbanizing semi-arid region - Arif ullah; Sajjad Hussain; Yicheng Wang; Muhammad Awais; Meer Muhammad Sajjad; Nuaman Ejaz; Umar Javed; Muhammad Waqas; Xiao Zhe; Javed Iqbal (Environmental Research, 2024)

Extraction of bioactive components from date palm waste, various extraction processes and their applications: A review - Imtisal Zahid; Muhammad Hamza Nazir; Muhammad Asad Javed (Biomass and Bioenergy, 2024)

Assessing the physicochemical properties of surface/groundwater of Sudhnoti district, Azad Jammu and Kashmir: Impacts on lindane degradation by photocatalysis - Taj Ur Rahman; Lubna Saba; Ashraf Ali; Wajiha Liaqat; Sanaullah Khan; Javed Ali Khan; Muhammad Aurang Zeb; Sajjad Hussain; Eman Y. Santali; Changseok Han (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

A comprehensive review of plant-based mucilages as promising candidates for water remediation - Sehar Javed; Zarfishan Zulfiqar; Zain Fatima; Gulzar Muhammad; Muhammad Ajaz Hussain; Muhammad Mushtaq; Muhammad Tahir Haseeb (Journal of Environmental Chemical Engineering, 2024)

MoS2@Ti3C2T Heterostructure: A new negative electrode material for Li-Ion hybrid supercapacitors - Salamat Ali; Muhammad Sufyan Javed; Khalid Umer; Jiatai Wang; Yujun Fu; Shunlian Kong; Shaukat Khan; Awais Ahmad; Anand Parkash; Munirah D. Albaqami; Annu; Jing Qi; et al. (Chemical Engineering Journal, 2024)

Harnessing Bacillus safensis as biofertilizer for sustainable drought alleviation in Brassica juncea L - Nizakat Bibi; Mohsin Khan; Fazal ur Rehman; Mahrukh; Shah Room; Muhammad Ansar Ahmad; Muhammad Iftikhar; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Biocatalysis and Agricultural Biotechnology, 2024)

Production and optimization of biofuels from locally isolated algal biomass: Strategies for circular economy integration - Muhammad Uzair Javed; Iqra Nazeer; Hamid Mukhtar; Umer Rashid; Maria J. Sabater; Fahad A. Alharthi (Biocatalysis and Agricultural Biotechnology, 2024)

Feasible biosynthesis of biologically active metabolites in in vitro culture of Macrotyloma uniflorum - Sannia Batool; Mehnaz Khanum; Hasnat Tariq; Gouhar Zaman; Muhammad Uzair Javed; Bilal Haider Abbasi; Christophe Hano; Nathalie Giglioli-Guivarc'h (Biocatalysis and Agricultural Biotechnology, 2024)

Low doses of entomopathogens matter hugely, gateway to resistance development and retarded growth in Helicoverpa armigera - Mirza Abdul Qayyum; Zhuo Zhihang; Waqas Wakil; Habib Ali; Abid Ali; Muhammad Usman Ghazanfar; Muhammad Yasin; Xu Danping; Hasham S. Almoallim; Mohammad Javed Ansari; Muhammad Tahir; Kashif Ali; et al. (Journal of Plant Diseases and Protection, 2024)

Investigation of drying shrinkage response in fibrillated microfiber reinforced preplaced concrete: experimental analysis and prediction models - Muhammad Saqib; Muhammad Faisal Javed; M. Ijaz Khan (Innovative Infrastructure Solutions, 2024)

Efficacy of Fe-Mg-bimetallic biochar in stabilization of multiple heavy metals-contaminated soil and attenuation of toxicity in spinach (Spinacia oleracea L.) - Muhammad Kashif Irshad; Jong Cheol Lee; Muhammad Aqeel; Wasim Javed; Ali Noman; Su Shiung Lam; Ali El Naggar; Nabeel Khan Niazi; Hun Ho Lee; Muhammad Ibrahim; Sang Soo Lee (Chemosphere, 2024)

Microplastic and cadmium contamination: Impact on the soil by inhibiting the growth of pak choi (Brassica rapa subsp. chinensis) - Guanlin Li; Xinran Cui; Muhammad Tariq; Ismail Khan; Ali Raza Khan; Sami Al Obaid; Mohammad Javed Ansari; Huan Zhou; Babar Iqbal; Xin Zhao (Process Safety and Environmental Protection, 2024)

Modelling and predicting lift force and trans-membrane pressure using linear, KNN, ANN and response surface models during the separation of oil drops from produced water - Hasnain Ahmad Saddiqi; Zainab Javed; Qazi Muhammad Ali; Asmat Ullah; Iftikhar Ahmad (Journal of Water Process Engineering, 2024)

Optimized prediction modeling of micropollutant removal efficiency in forward osmosis membrane systems using explainable machine learning algorithms - Ali Aldrees; Muhammad Faisal Javed; Majid Khan; Bilal Siddiq (Journal of Water Process Engineering, 2024)

Biosafety measures for Alicyclobacillus spp. strains across various levels of biohazard - Marina Sajid; Sajid Mehmood; Yahong Yuan; Tianli Yue; Muhammad Zubair Khalid; Ahmad Mujtaba; Sulaiman Ali Alharbi; Mohammad Javed Ansari; Abdellah Zinedine; João Miguel Rocha (Food and Chemical Toxicology, 2024)

Unveiling the nexus between atmospheric visibility, remotely sensed pollutants, and climatic variables across diverse topographies: A data-driven exploration empowered by artificial intelligence - Sadaf Javed; Muhammad Imran Shahzad; Imran Shahid (Atmospheric Pollution Research, 2024)

Alleviating Drought Stress in Strawberry Plants: Unraveling the Role of Paclobutrazol as a Growth Regulator and Reducer of Oxidative Stress Induced by Reactive Oxygen and Carbonyl Species - Khansa Saleem; Muhammad Ahsan Asghar; Ali Raza; Kaiwen Pan; Abd Ullah; Hafiz Hassan Javed; Mahmoud F. Seleiman; Shakeel Imran; Sajid Mehmood Nadeem; Khurram Shehzad Khan; Junbo Du; Fei Xu; et al. (Journal of Plant Growth Regulation, 2024)

Tailoring structural and optical properties of Cu(II)-induced MgAl2O4 nanoparticles and their response to toxic dyes under solar illumination - Muhammad Javed; Naeem Akbar; Ayaz Arif Khan; Asad Masood; Naeem Ahmed; Muhammad Junaid Khan; Nisar Ahmed; Said Nasir Khisro; Muhammed Ali Shaikh Abdul Hameed (Environmental Science and Pollution Research, 2024)

Biochemical and nutritional analysis of seaweed (Iyengaria stellata) and its therapeutic significance, using antioxidant, antimicrobial, and hypoglycemic activities - Muhammad Imran; Arshad Iqbal; Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Syed Lal Badshah; Saad Alghamdi; Mazen Almehmadi; Uthman Balgith Algopishi; Baber Ali; Saima Sohni; Muhammad Ammar Javed; Doaa Bahaa Eldin Darwish (South African Journal of Botany, 2024)

Biogenic iron oxide nanoparticles (Fe2O3 NPs) adeptly diminish leaf blight of Rosa chinensis by exhibiting higher expression of RcWRKY29 and increasing antioxidant enzymatic activities - Hira Saleem; Mahnoor Akbar; Maryam Anar; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (South African Journal of Botany, 2024)

Hydrothermal carbonization of fruit peels of varied origin forms hydrochar of distinct capability for adsorption of methylene blue - Sobia Kousar; Mengjiao Fan; Kanwal Javed; Muhammad Rashid; Shu Zhang; Xun Hu (Journal of Water Process Engineering, 2024)

Phenotypic and Molecular Profiling of Vitis Vinifera L. Genotypes Against Anthracnose Through SCAR Markers - Qandeela Nigar; Mahmood ul Hassan; Rashid Mehmood Rana; Sadia Mehmood Satti; Summaira Ali; Muhammad Farhan Khan Pasha; Irfan Ali; Hafiz Muhamamd Ahmad; Sami Al Obaid; Mohammad Javed Ansari; Sajid Fiaz (Journal of Crop Health, 2024)

Efficacy of activated carbon using Salvadora persica stem for remediation of potentially toxic dyes from aqueous solution - Muhammad Bilal; Wahid Ullah; Tahir Abbas; Javed Ali; Syed Shah Hassan; Esraa M. Bakhsh; Kalsoom Akhtar; Sher Bahadar Khan (Environmental Monitoring and Assessment, 2024)

Assessment of heavy metal levels in polyculture fish farms and their aquatic ecosystems: an integrative study addressing environmental and human health risks associated with dam water usage - Syed Sikandar Habib; Saira Naz; Muhammad Qamar Saeed; Javed Ahmed Ujan; Samrah Masud; Alia Mushtaq; Mujeeb Ullah; Khalid Khan; Muhammad Zahid; Salim S. Al-Rejaie; Mohamed Mohany (Environmental Geochemistry and Health, 2024)

In vitro exploration of Acinetobacter strain (SG-5) for antioxidative potential and phytohormone biosynthesis in maize (Zea mays L.) cultivars differing in cadmium tolerance - Saghir Abbas; Kashif Tanwir; Muhammad Hussaan; Sajid Masood; Qasim Ali; Ali Raza; Muhammad Shahid; Hassan Javed Chaudhary; Saba Mushtaq; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2024)

Improving the efficiency of photovoltaic-thermoelectric generator system using novel flying squirrel search optimization algorithm: Hybrid renewable and thermal energy system (RTES) for electricity generation - Muhammad Yaqoob Javed; Aamer Bilal Asghar; Khazina Naveed; Ali Nasir; Basem Alamri; Muhammad Aslam; Essam A. Al-Ammar; Zsolt Conka (Process Safety and Environmental Protection, 2024)

Assessment of the impacts of climate change on the construction of homogeneous climatic regions and ensemble climate projections using CMIP6 data over Pakistan - Muhammad Abbas; Firdos Khan; Yuei-An Liou; Hamd Ullah; Beenish Javed; Shaukat Ali (Atmospheric Research, 2024)

Bacteria-Based MnO Nanoparticles Alleviate Lead Toxicity in Tomato Seedling Through Improving Growth Attributes and Enhanced Gene Expression of Candidate Genes - Maryam Anar; Urooj Haroon; Asif Kamal; Kinza Tahir; Mahnoor Akbar; Farhana; Hira Saleem; Abdul Rehman; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Journal of Plant Growth Regulation, 2024)

Microbial detoxification of chlorpyrifos, profenofos, monocrotophos, and dimethoate by a multifaceted rhizospheric Bacillus cereus strain PM38 and its potential for the growth promotion in cotton - Najeeba Parre Pakar; Fazal ur Rehman; Shehzad Mehmood; Sarfaraz Ali; Nida Zainab; Muhammad Farooq Husain Munis; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2024)

Land banking, land price and Ghana’s informal land markets: A relational complexity approach - Alexander Sasu; Arshad Javed; Muhammad Imran; Graham Squires (Land Use Policy, 2024)

Photocatalytic and biological efficacy of Carissa macrocarpa fruit extract-mediated one-pot synthesized ternary metal oxide dual S-scheme heterojunction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Akbar Ali; Muhammad Naeem-ul-Hassan; Javed Iqbal (Journal of Environmental Chemical Engineering, 2024)

Comparative Effects of Straw and Biochar on N2O Emissions from Acidic Soils - Feier Wang; Zhilong He; Xiuling Zhang; Javed Iqbal; Muhammad Shaaban; Ronggui Hu; Shan Lin; Ziwei Yan (Journal of Soil Science and Plant Nutrition, 2024)

Physico-mechanical characterization of eco-friendly gypsum composites incorporating shredded surgical face masks - Muhammad Hassan Javed; Muhammad Rizwan Riaz; Rizwan Azam; Muhammad Kashif; Anam Fatima (Innovative Infrastructure Solutions, 2024)

Analyzing the impact of pesticides on the indus river: contamination levels in water, sediment, fish, and associated human health risks - Syed Sikandar Habib; Francesco Fazio; Samrah Masud; Javed Ahmed Ujan; Muhammad Qamar Saeed; Mujeeb Ullah; Khalid Khan; Khayyam Khayyam; Mohamed Mohany; Marija Milošević; Salim S. Al-Rejaie; Cristina Cravana (Environmental Geochemistry and Health, 2024)

Application of Synthetic Iron Oxyhydroxide with Influencing Factors for Removal of As(V) and As(III) from Groundwater - Shakeel Ahmed Talpur; Muhammad Yousuf Jat Baloch; Chunli Su; Javed Iqbal; Aziz Ahmed; Hafeez Ahmed Talpur (Journal of Earth Science, 2024)

Greening the future: assessing the influence of technological innovation, energy transition and financial globalization on ecological footprint in selected emerging countries - Muhammad Sibt-e-Ali; Xia Xiqiang; Kashif Javed; Muhammad Qasim Javaid; László Vasa (Environment, Development and Sustainability, 2024)

Pyridine-2,6-Dicarboxylic Acid As a Facile and Highly Selective “Turn-Off” Fluorimetric Chemosensor for Detection of Cu (II) Ions in Aqueous Media - Javed Hussain Shah; Shahzad Sharif; Muhammad Shahbaz; Bilal Riaz; Sundas Shahzad; Onur Şahin; Khurram Shahzad Munawar; Hijaz Ahmad; Essam A. Al-Ammar (Journal of Fluorescence, 2024)

Integrated Approach to Hydrogeochemical Assessment of Groundwater Quality in Major Industrial Zone of Punjab, Pakistan - Asmat Ali; Zahid Ullah; Nayab Ismaeel; Abdur Rashid; Warda Khalid; Maria Siddique; Javed Iqbal; Anwarzeb Khan; Muhammad Waqas; Junaid Ghani (Environmental Science and Pollution Research, 2024)

Unveiling the detrimental effects of polylactic acid microplastics on rice seedlings and soil health - Muhammad Kashif Irshad; Min Woo Kang; Muhammad Aqeel; Wasim Javed; Ali Noman; Noreen Khalid; Sang Soo Lee (Chemosphere, 2024)

Green synthesis of ZnO nanocubes from Ceropegia omissa H. Huber extract for photocatalytic degradation of bisphenol An under visible light to mitigate water pollution - Awais Ahmad; Muhammad Ramzan Khawar; Ikram Ahmad; Muhammad Hassan Javed; Anees Ahmad; Abdul Rauf; Umer Younas; Arif Nazir; Dongwhi Choi; Abdulnasser M. Karami (Environmental Research, 2024)

Comparative study of light-emitting cement and polymer mortars for sustainable building applications: performance evaluation and analysis - Muhammad Ali Sikandar; Zeeshan Khan; Muhammad Haris Javed; Muhammad Tariq Bashir; Easa Khan; Md. Munir Hayet Khan; Azhar Qazi (Innovative Infrastructure Solutions, 2024)

Appraisal of the health hazards associated with the ingestion of vegetables contaminated with potentially toxic elements - Ali Afzal; Atif Muhmood; Syed Ayyaz Javed; Arslan Nazarat; Muhammad Rashid; Asrar Hussain Shah; Farhana Siddique (Arabian Journal of Geosciences, 2024)

Spatiotemporal investigation of near-surface CH4 and factors influencing CH4 over South, East, and Southeast Asia - Muhammad Athar Khaliq; Farhan Mustafa; Shafeeq Ur Rehman; Muhammad Shahzaman; Zeeshan Javed; Muhammad Sagir; Safdar Bashir; Hongchao Zuo (Science of The Total Environment, 2024)

Structural and thermal investigation of lignocellulosic biomass conversion for enhancing sustainable imperative in progressive organic refinery paradigm for waste-to-energy applications - Tayyab Qureshi; Muhammad Farooq; Shahid Imran; Muhammad Adeel Munir; Muhammad Asad Javed; Ihsanullah Sohoo; Muhammad Sultan; Ateekh Ur Rehman; Muhammad Farhan; Muhammad Asim; John M. Andresen (Environmental Research, 2024)

Sustainability assessment of biofuel and value-added product from organic fraction of municipal solid waste - Farayi Musharavati; Anees Ahmad; Muhammad Hassan Javed; Khadija Sajid; Muhammad Naqvi (Environmental Research, 2024)

Benign-by-design plant extract-mediated preparation of copper oxide nanoparticles for environmentally related applications - Awais Ahmad; Mariam Khan; Sameh M. Osman; Ahmad M. Haassan; Muhammad Hassan Javed; Anees Ahmad; Abdul Rauf; Rafael Luque (Environmental Research, 2024)

Brown macro-seaweeds derived agro-biostimulant for Zea mays farming in saline conditions: Growth enhancement and optimum biochemical and ion feedback - Sadaf Gul; Muhammad Farrakh Nawaz; Muhammad Talha Bin Yousaf; Muhammad Haroon U Rashid; Muhammad Yousuf Adnan; Shamama Tausif; Arooj Javed; Zainul Abideen; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2024)

Bacillus safensis filtrate-based ZnO nanoparticles control black heart rot disease of apricot fruits by maintaining its soluble sugars and carotenoids - Farhana; Abu Bakr Umer Farooq; Urooj Haroon; Hira Saleem; Mahnoor Akbar; Maryam Anar; Muhammad Nawaz; Hassaan Ateeb Ahmad; Junaid Ahmed; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (World Journal of Microbiology and Biotechnology, 2024)

Genetics aspect of vitamin C (Ascorbic Acid) biosynthesis and signaling pathways in fruits and vegetables crops - Adnan Sami; Shiming Han; Muhammad Zeshan Haider; Rameen Khizar; Qurban Ali; Muhammad Shafiq; Javaria Tabassum; Muhammad Nouman Khalid; Muhammad Arshad Javed; Mateen Sajid; Muhammad Aamir Manzoor; Irfan Ali Sabir (Functional & Integrative Genomics, 2024)

Correction to: Mycorrhizosphere bacteria inhibit chromium uptake and phytotoxicity by regulating proline metabolism, antioxidant defense system, and aquaporin gene expression in tomato - Tariq Shah; Zeeshan Khan; Tahani Awad Alahmadi; Ayesha Imran; Muhammad Asad; Shah Rukh Khan; Mohammad Javed Ansari (Environmental Science and Pollution Research, 2024)

Mycorrhizosphere bacteria inhibit chromium uptake and phytotoxicity by regulating proline metabolism, antioxidant defense system, and aquaporin gene expression in tomato - Tariq Shah; Zeeshan Khan; Tahani Awad Alahmadi; Ayesha Imran; Muhammad Asad; Shah Rukh Khan; Mohammad Javed Ansari (Environmental Science and Pollution Research, 2024)

The impact of mineral resource abundance on environmental degradation in ten mineral- rich countries: Do the green innovation and financial technology matter? - Hasnain Javed; Jianguo Du; Shuja Iqbal; Abdelmohsen A. Nassani; Muhammad Farhan Basheer (Resources Policy, 2024)

Empirical analysis of cost-effective and equitable solid waste management systems: Environmental and economic perspectives - Asif Iqbal; Abdullah Yasar; Abdul-Sattar Nizami; Rafia Haider; Imran Ali Sultan; Aman Anwer Kedwaii; Muhammad Murtaza Chaudhary; Muhammad Hassan Javed; Anees Ahmad; Khadija Sajid; Muhammad Naqvi; Muhammad Usman Ghori (Environmental Research, 2024)

Spatio-temporal variations in dissolved trace elements in peat bog porewaters impacted by dust inputs from open-pit mining activities in the Athabasca Bituminous Sands (ABS) region - Sundas Arooj Butt; Fiorella Barraza; Kevin Devito; Lukas Frost; Muhammad Babar Javed; Tommy Noernberg; Andrii Oleksandrenko; William Shotyk (Environmental Pollution, 2024)

Transcriptomics, proteomics, and metabolomics interventions prompt crop improvement against metal(loid) toxicity - Ali Raza; Hajar Salehi; Shanza Bashir; Javaria Tabassum; Monica Jamla; Sidra Charagh; Rutwik Barmukh; Rakeeb Ahmad Mir; Basharat Ahmad Bhat; Muhammad Arshad Javed; Dong-Xing Guan; Reyazul Rouf Mir; et al. (Plant Cell Reports, 2024)
The escalating challenges posed by metal(loid) toxicity in agricultural ecosystems, exacerbated by rapid climate change and anthropogenic pressures, demand urgent attention. Soil contamination is a critical issue because it significantly impacts crop productivity. The widespread threat of metal(loid) toxicity can jeopardize global food security due to contaminated food supplies and pose environmental risks, contributing to soil and water pollution and thus impacting the whole ecosystem. In this context, plants have evolved complex mechanisms to combat metal(loid) stress. Amid the array of innovative approaches, omics, notably transcriptomics, proteomics, and metabolomics, have emerged as transformative tools, shedding light on the genes, proteins, and key metabolites involved in metal(loid) stress responses and tolerance mechanisms. These identified candidates hold promise for developing high-yielding crops with desirable agronomic traits. Computational biology tools like bioinformatics, biological databases, and analytical pipelines support these omics approaches by harnessing diverse information and facilitating the mapping of genotype-to-phenotype relationships under stress conditions. This review explores: (1) the multifaceted strategies that plants use to adapt to metal(loid) toxicity in their environment; (2) the latest findings in metal(loid)-mediated transcriptomics, proteomics, and metabolomics studies across various plant species; (3) the integration of omics data with artificial intelligence and high-throughput phenotyping; (4) the latest bioinformatics databases, tools and pipelines for single and/or multi-omics data integration; (5) the latest insights into stress adaptations and tolerance mechanisms for future outlooks; and (6) the capacity of omics advances for creating sustainable and resilient crop plants that can thrive in metal(loid)-contaminated environments.

Ethnobotanical, ecological and health risk assessment of some selected wild medicinal plants collected along mafic and Ultra Mafic rocks of Northwest Pakistan - Irfan Ullah; Muhammad Adnan; Javed Nawab; Sardar Khan (Environmental Monitoring and Assessment, 2024)

Spatial variation and chemical reactivity of dusts from open-pit bitumen mining using trace elements in snow - Fiorella Barraza; Muhammad Babar Javed; Tommy Noernberg; Judy Schultz; William Shotyk (Chemosphere, 2024)

Recent trends in wastewater treatment by using metal-organic frameworks (MOFs) and their composites: A critical view-point - Syed Shoaib Ahmad Shah; Manzar Sohail; Ghulam Murtza; Amir Waseem; Aziz ur Rehman; Iftikhar Hussain; Muhammad Sohail Bashir; Saleh S. Alarfaji; Ahmed M. Hassan; Muhammad Altaf Nazir; Muhammad Sufyan Javed; Tayyaba Najam (Chemosphere, 2024)

Ecofriendly process optimization of natural dye extraction from clove (Syzygium aromaticum L.) using response surface methodology and artificial neural network modeling - Muhammad Aftab; Tanvir Ahmad; Shahid Adeel; Maria Javed (Sustainable Chemistry and Pharmacy, 2024)

Risk surveillance with spatial distribution of Organochlorine Pesticides (OCPs) from sedimentary samples of Chenab River - Sidra Siddique; M. Nawaz Chaudhry; Sajid Rashid Ahmad; Rabia Nazir; Rimsha Javed; Muhammad Rashid Hafeez; Yasser Alraey; Lalita Ambigai Sivasamugham; Adeel Mahmood (Science of The Total Environment, 2024)

Unlocking biogas potential: Spatial analysis, economic viability, and climate resilience in southern regions of Khyber Pakhtunkhwa, Pakistan - Arshad Ahmad Khan; Sufyan Ullah Khan; Gorm Kipperberg; Tehseen Javed; Muhammad Abu Sufyan Ali; Rahman Ullah; Jianchao Luo (Science of The Total Environment, 2024)

Investigating biodiesel production from Chicken fat oil using bi-functional catalysts and microbubble mediated mass transfer - Maryam Asif; Fahad Javed; Muhammad Younas; Mazhar Amjad Gillani; William B. Zimmerman; Fahad Rehman (Fuel, 2024)

Molecular cloning, biological description, and functional analysis of Ajfos transcription factor in pathogen-induced Apostichopus japonicus - Yuan Ren; Yongping Xu; Zhenhui Wang; Yinan Wang; Jialin Zhang; Zhen Li; Yupeng Chen; Wei Go; Muhammad Tariq Javed; Qiang Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Inversion techniques for focal mechanism determination of small-magnitude earthquakes: a comparative study using the Burewala earthquake ($$M_w$$ $$\sim $$ 4) in Pakistan - Sadia Sabahat; Mohammad Tahir; Fatima Munir; Bilal Saif; Muhammad Tahir Iqbal; Javed Iqbal; Talat Iqbal (Journal of Seismology, 2024)

Development and Characterization of Glimepiride-Loaded Polymeric Nanoparticles: Formulation Design and Evaluation - Zaiba Irfan; Muhammad Imran Khan; Muhammad Farhan Sohail; Muhammad Furqan Akhtar; Muhammad Naeem Qaisar; Muhammad Kashif Javed; Fareeha Anwar; Badarqa-tul-Ayesha; Majid Anwar; Aslam Khan; Faizan Akram (Journal of Pharmaceutical Innovation, 2024)

Enhancement in the production of phenolic compounds from Fagonia indica callus cultures via Fusarium oxysporum triggered elicitation - Taimoor Khan; Muhammad Uzair Javed; Tehreem Mahmood; Bushra Khan; Tariq Khan; Muhammad Asad Ullah; Razia Khurshid; Gouhar Zaman; Christophe Hano; Nathalie Giglioli-Guivarc’h; Bilal Haider Abbasi (In Vitro Cellular & Developmental Biology - Plant, 2024)

WITHDRAWN: Valorization of Algal Biomass to Synthesize Heterogeneous gCN-Biochar Photocatalyst for the Treatment of Industrial Wastewater using Photocatalysis-Persulfate Oxidation Process - Aqsa Shafique; Hafiz Muhammad Uzair Ayub; Javed Iqbal; Shanawar Hamid; Fawad Ashraf; Muhammad Saif Ur Rehman; S. Boukhari; Mohamed A. Habila; Alam Nawaz; Tahir Fazal (Chemosphere, 2024)

Mitigating chromium toxicity in rice (Oryza sativa L.) via ABA and 6-BAP: Unveiling synergistic benefits on morphophysiological traits and ASA-GSH cycle - Khairiah Mubarak Alwutayd; Suliman Mohammed Suliman Alghanem; Rahaf Alwutayd; Sameera A. Alghamdi; Nadiyah M. Alabdallah; Rahmah N. Al-Qthanin; Wajiha Sarfraz; Noreen Khalid; Nayab Naeem; Baber Ali; Muhammad Hamzah Saleem; Sadia Javed; et al. (Science of The Total Environment, 2024)

First report on genotypic estimation of MRSA load in udder of nomadic sheep flocks affected with subclinical mastitis in Pakistan - Muhammad Jawad Sabir; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Muhammad Umar Javed; Farwa Anwaar (Research in Veterinary Science, 2024)

Protein extracted from Moringa oleifera Lam. Leaves: Bio-evaluation and characterization as suitable plant-based meat-protein alternative - Muhammad Sameem Javed; Smara Qaiser Alvi; Adnan Amjad; Hasan Sardar; Muhammad Junaid Anwar; Asma Javid; Sami Abou Fayssal; Pankaj Kumar; Tracy Abou Fayssal; Saikh M. Wabaidur; Mohammad K. Okla; Ibrahim A. Saleh; et al. (Regulatory Toxicology and Pharmacology, 2024)

Spherical Fe2O3 nanoparticles inhibit the production of aflatoxins (B1 and B2) and regulate total soluble solids and titratable acidity of peach fruit - Mahnoor Akbar; Naeem Ali; Muhammad Imran; Arshad Hussain; Syed Waqas Hassan; Urooj Haroon; Asif Kamal; Farhana; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (International Journal of Food Microbiology, 2024)

Deciphering the Role of Phytohormones and Osmolytes in Plant Tolerance Against Salt Stress: Implications, Possible Cross-Talk, and Prospects - Sadam Hussain; Muhammad Bilal Hafeez; Rabia Azam; Kashf Mehmood; Marjan Aziz; Sezai Ercisli; Talha Javed; Ali Raza; Noreen Zahra; Saddam Hussain; Xiaolong Ren (Journal of Plant Growth Regulation, 2024)

Hydrogeochemistry and prediction of arsenic contamination in groundwater of Vehari, Pakistan: comparison of artificial neural network, random forest and logistic regression models - Javed Iqbal; Chunli Su; Maqsood Ahmad; Muhammad Yousuf Jat Baloch; Abdur Rashid; Zahid Ullah; Hasnain Abbas; Anam Nigar; Asmat Ali; Arif Ullah (Environmental Geochemistry and Health, 2024)

Modelling of debris-flow susceptibility and propagation: a case study from Northwest Himalaya - Hamza Daud; Javed Iqbal Tanoli; Sardar Muhammad Asif; Muhammad Qasim; Muhammad Ali; Junaid Khan; Zahid Imran Bhatti; Ishtiaq Ahmad Khan Jadoon (Journal of Mountain Science, 2024)

Characterization of water-deficit tolerance in Upland cotton (Gossypium hirsutum L.) assessing morphological, biochemical, molecular and yield attributes - Muhammad Saeed; Muhammad Naeem; Alia Javed; Shagufta Perveen; Iqra Sajjad; Muhammad Zaid Yousaf; M. Shahid Munir Chohan; Muhammad Riaz; Sana Ullah; Xianliang Song (Acta Physiologiae Plantarum, 2024)

Bacterial inoculation remediates heavy metals toxicity through modulating biochemicals and antioxidant enzymes of Daucus carota L. grown in lead contaminated soil - Naima Huma Naveed; Naveed Abbas Nasir; Anis Ali Shah; Tahir Shahzad; Nasim Ahmad Yasin; Zain Ali; Muhammad Jamil; Talha Javed; Aamir Ali (South African Journal of Botany, 2023)

Synthesis of N-doped TiO2 nanoparticles with enhanced photocatalytic activity for 2,4-dichlorophenol degradation and H2 production - Javed Ali Khan; Murtaza Sayed; Noor S. Shah; Sanaullah Khan; Ashfaq Ahmad Khan; Muhammad Sultan; Ammar M. Tighezza; Jibran Iqbal; Grzegorz Boczkaj (Journal of Environmental Chemical Engineering, 2023)

Subtractive sequence analysis aided druggable targets mining in Burkholderia cepacia complex and finding inhibitors through bioinformatics approach - Syed Shah Hassan; Rida Shams; Ihosvany Camps; Zarrin Basharat; Saman Sohail; Yasmin Khan; Asad Ullah; Muhammad Irfan; Javed Ali; Muhammad Bilal; Carlos M. Morel (Molecular Diversity, 2023)

Variation in Soil C and P Fractions Associated with Microbial Biomass - Khuram Shehzad Khan; Muhammad Naveed; Muhammad Farhan Qadir; Adeel Ahmad; Hafiz Hassan Javed; Allah Ditta (Journal of Soil Science and Plant Nutrition, 2023)

Elucidating the Mechanistic Role of Zinc-Lysine to Enhance Cd Tolerance in Diverse Wheat (Triticum aestivum L.) Cultivars Through Distinct Morpho-Physio-Biochemical Improvements Under Cd Stress - Muhammad Hussaan; Saghir Abbas; Qasim Ali; Muhammad Sohail Akram; Kashif Tanwir; Ahmad Raza; Sherjeel Hashmat; Muhammad Aqeel; Hassan Javed Chaudhary; Muhammad Tariq Javed (Journal of Soil Science and Plant Nutrition, 2023)

Development of Aluminium (Al)-Tolerant Soybean Using Molecular Tools: Limitations and Future Directions - Adnan Rasheed; Anwar Ahmad Khan; Muhammad Nawaz; Athar Mahmood; Uzma Arif; Muhammad Umair Hassan; Javed Iqbal; Muhammad Hamzah Saleem; Basharat Ali; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Added value upshot of barley amalgamation in wheat flour to boost the physico-chemical quality attributes of flat bread - Muhammad Abdullah; Muhammad Zulkiffal; Tabussam Tufail; Farah Naz Akbar; Muhammad Owais; Javed Ahmed; Ahsan Javed; Muhammad Ijaz Tabassum; Amna Kanwal; Muhammad Asghar; Muhammad Musa; M. A. Rehman Arif; et al. (Cereal Research Communications, 2023)

Correction: Modeling future urban network capacity and land use/land cover simulation using GEE and remote sensing data - Muhammad Nabeel Khalid; Muhammad Nasar Ahmad; Muhammad Asif Javed; Sajid Rashid Ahmad (Arabian Journal of Geosciences, 2023)

Mapping impervious surface area increase and urban pluvial flooding using Sentinel Application Platform (SNAP) and remote sensing data - Muhammad Nasar Ahmad; Zhenfeng Shao; Akib Javed (Environmental Science and Pollution Research, 2023)

g-C3N4/graphene oxide/SnFe2O4 ternary composite for the effective sunlight-driven photocatalytic degradation of methylene blue - Suman Tahir; Muhammad Zahid; Muhammad Asif Hanif; Muhammad Yasir Javed (Environmental Science and Pollution Research, 2023)

Risk assessment of toxic and hazardous metals in paddy agroecosystem by biochar-for bio-membrane applications - Muhammad Kashif Irshad; Sihang Zhu; Wasim Javed; Jong Cheol Lee; Abid Mahmood; Sang Soo Lee; Shang Jianying; Gadah Albasher; Atif Ali (Chemosphere, 2023)

Graphene-grafted bimetallic MOF membranes for hazardous & toxic contaminants treatment - Ayesha Rehman; Zaib Jahan; Muhammad Bilal Khan Niazi; Tayyaba Noor; Farhan Javed; Sarah I. Othman; Mostafa R. Abukhadra; Alam Nawaz (Chemosphere, 2023)

Natural enrichment of Cd and Tl in the bark of trees from a rural watershed devoid of point sources of metal contamination - William Shotyk; Fiorella Barraza; Chad W. Cuss; Iain Grant-Weaver; Carla Germani; Muhammad Babar Javed; Stephen Hillier; Tommy Noernberg; Andrii Oleksandrenko (Environmental Research, 2023)

Bionanocomposite scaffolds based on MnS-nanorods loaded acacia-Senegal-gum hydrogels: Fabrication, characterization and biological evaluation - Hidayat Ullah; Junaid Ihsan; Rasha M.K. Mohamed; Muhammad Aslam Khan; Marvi Ghani; Naseem Rauf; Shafqat Ullah; Asif Javed; Muhammad Farooq (Bioactive Carbohydrates and Dietary Fibre, 2023)

Plant breeding for harmony between sustainable agriculture, the environment, and global food security: an era of genomics‐assisted breeding - Aqsa Hafeez; Baber Ali; Muhammad Ammar Javed; Aroona Saleem; Mahreen Fatima; Amin Fathi; Muhammad Siddique Afridi; Veysel Aydin; Mükerrem Atalay Oral; Fathia A. Soudy (Planta, 2023)

Deciphering the Impact of Acinetobacter sp. SG-5 Strain on Two Contrasting Zea mays L. Cultivars for Root Exudations and Distinct Physio-Biochemical Attributes Under Cadmium Stress - Saghir Abbas; Muhammad Tariq Javed; Muhammad Shahid; Kashif Tanwir; Muhammad Hamzah Saleem; Nabeel Khan Niazi (Journal of Plant Growth Regulation, 2023)

Modeling future urban network capacity and land use/land cover simulation using GEE and remote sensing data - Muhammad Nabeel Khalid; Muhammad Nasar Ahmad; Muhammad Asif Javed; Sajid Rashid Ahmad (Arabian Journal of Geosciences, 2023)

Assessment of the phycosphere microbial dynamics of microbial community associated with red algae culture under different cultural conditions - Asadullah Gujar; Muhammmad Ahsan Asghar; Muneefah Abdullah Alenezi; Muhammad Saleem Kubar; Kashif Ali Kubar; Ali Raza; Khansa Saleem; Hafiz Hassan Javed; Abu Zar Ghafoor; Muhammad Iftikhar Hussain; Abd Ullah; Hongli Cui; et al. (Environment, Development and Sustainability, 2023)

Glutathione and zinc application upregulate the antioxidant system increasing photosynthetic pigments and growth under water stress in maize (Zea mays L.) - Farah Saeed; Abida Kausar; Qasim Ali; Athar Mahmood; Talha Javed; Rubab Shabbir; Muhammad Fraz Ali (Brazilian Journal of Botany, 2023)

Zinc oxide nanoparticles: biogenesis and applications against phytopathogens - Fazal ur Rehman; Najeeba Paree Paker; Shafiq ur Rehman; Muhammad Tariq Javed; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Journal of Plant Pathology, 2023)

Modifying engineered nanomaterials to produce next generation agents for environmental remediation - Muhammad Arslan Ahmad; Muhammad Adeel; Noman Shakoor; Rabia Javed; Muhammad Ishfaq; Yutao Peng; Muhammad Zain; Imran Azeem; Ilyas Ali; Muhammad Usman; Zihao Wu; Gholamreza Gohari; et al. (Science of The Total Environment, 2023)

Synthesis of MXene-based single-atom catalysts for energy conversion applications - Muhammad Aizaz Ud Din; Syed Shoaib Ahmad Shah; Muhammad Sufyan Javed; Manzar Sohail; Aziz ur Rehman; Muhammad Altaf Nazir; Mohammed A. Assiri; Tayyaba Najam; Nanpu Cheng (Chemical Engineering Journal, 2023)

Assessment of application of ZnO nanoparticles on physiological profile, root architecture and antioxidant potential of Solanum lycopersicum - Fazal ur Rehman; Najeeba Paree Paker; Mohsin Khan; Nida Zainab; Naeem Ali; Muhammad Farooq Hussain Munis; Muhammad Iftikhar; Hassan Javed Chaudhary (Biocatalysis and Agricultural Biotechnology, 2023)

Metabolomics Analysis Reveals Soybean Node Position Influence on Metabolic Profile of Soybean Seed at Various Developmental Stages - Dennis Takpah; Muhammad Ahsan Asghar; Ali Raza; Hafiz Hassan Javed; Abd Ullah; Xiangqing Huang; Khansa Saleem; Cong-Wei Xie; Xinli Xiao; Kyei Sarpong Clement; Muhammad Umer Farooq; Wenyu Yang; et al. (Journal of Plant Growth Regulation, 2023)

Life table parameters and feeding potential of Chrysoperla carnea (Stephens) on eggs of Pyrilla perpusilla (Walker) - Muhammad Umer; Javed khan; Fan Fan; Xiaofan Yang; Mengyao Li; Asim Iqbal; Guoshu Wei (Journal of Plant Diseases and Protection, 2023)

Insight into the environmental fate, hazard, detection, and sustainable degradation technologies of chlorpyrifos—an organophosphorus pesticide - Pankaj Kumar; Muhammad Arshad; Amel Gacem; Sunil Soni; Snigdha Singh; Manoj Kumar; Virendra Kumar Yadav; Mohd. Tariq; Ramesh Kumar; Deepankshi Shah; Shivraj Gangadhar Wanale; Mohammed Khaloofah Mola Al Mesfer; et al. (Environmental Science and Pollution Research, 2023)

Assessment of landcover impacts on the groundwater quality using hydrogeochemical and geospatial techniques - Javed Iqbal; Gomal Amin; Chunli Su; Ehsan Haroon; Muhammad Yousuf Jat Baloch (Environmental Science and Pollution Research, 2023)

Correction to: Long-term spatio-temporal trends in atmospheric aerosols and trace gases over Pakistan using remote sensing - Muhammad Adil Javed; Usman Mehmood; Salman Tariq; Zia ul Haq (Acta Geophysica, 2023)

Alleviation of arsenic toxicity-induced oxidative stress in lemon grass by methyl jasmonate - Khansa Saleem; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Ali Raza; Mahmoud F. Seleiman; Abd Ullah; Altafur Rahman; Sufyan Iqbal; Aamir Hanif; Shakeel Imran; Sajid Mahmood Nadeem; Junbo Du; et al. (South African Journal of Botany, 2023)

Influence of soil microplastic contamination and cadmium toxicity on the growth, physiology, and root growth traits of Triticum aestivum L. - Babar Iqbal; Qaiser Javed; Ismail Khan; Muhammad Tariq; Naveed Ahmad; Hosam O. Elansary; Arshad Jalal; Guanlin Li; Daolin Du (South African Journal of Botany, 2023)

Biosynthesized manganese oxide nanoparticles maintain firmness of tomato fruit by modulating soluble solids and reducing sugars under biotic stress - Maryam Anar; Mahnoor Akbar; Kinza Tahir; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Physiological and Molecular Plant Pathology, 2023)

Corrigendum to “Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns” [Cryobiology 110 (2023) 69–78] - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

Boosting the energy storage performance of aqueous NH4+ symmetric supercapacitor based on the nanostructured molybdenum disulfide nanosheets - Muhammad Sufyan Javed; Xiaofeng Zhang; Salamat Ali; Syed Shoaib Ahmad Shah; Awais Ahmad; Iftikhar Hussain; Shahid Hussain; Shaukat Khan; Mohamed Ouladsmane; Sayed M. Tag ElDin; Waqas Ul Arifeen; Weihua Han (Chemical Engineering Journal, 2023)

Cadmium Prevalence in Cacao (Theobroma cacao L.) and Potential Remediation Strategies - Babar Hussain; Shibin Liu; Shafeeq Ur Rahman; Santos Triunfo Leiva-Espinoza; Khadija Javed; Shengyan Pu; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Correction: Ascorbic and Salicylic Acids Vitalized Growth, Biochemical Responses, Antioxidant Enzymes, Photosynthetic Efciency, and Ionic Regulation to Alleviate Salinity Stress in Sorghum bicolor - Muhammad Azeem; Robina Sultana; Athar Mahmood; Muhammad Qasim; Zamin Shaheed Siddiqui; Sahar Mumtaz; Talha Javed; Muhammad Umar; M. Yousuf Adnan; Manzer H. Siddiqui (Journal of Plant Growth Regulation, 2023)

Drinking Water Quality Assessment of Government, Non-Government and Self-Based Schemes in the Disaster Affected Areas of Khyber Pakhtunkhwa, Pakistan - Javed Nawab; Abdur Rahman; Sardar Khan; Junaid Ghani; Zahid Ullah; Haris Khan; Muhammad Waqas (Exposure and Health, 2023)

Effect of green Fe2O3 nanoparticles in controlling Fusarium fruit rot disease of loquat in Pakistan - Faryal Niazi; Musrat Ali; Urooj Haroon; Farhana; Asif Kamal; Taskeen Rashid; Fareeha Anwar; Rabia Nawab; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Brazilian Journal of Microbiology, 2023)

Nanotoxicity assessment in plants: an updated overview - Hira Zafar; Rabia Javed; Muhammad Zia (Environmental Science and Pollution Research, 2023)

Ascorbic and Salicylic Acids Vitalized Growth, Biochemical Responses, Antioxidant Enzymes, Photosynthetic Efficiency, and Ionic Regulation to Alleviate Salinity Stress in Sorghum bicolor - Muhammad Azeem; Robina Sultana; Athar Mahmood; Muhammad Qasim; Zamin Shaheed Siddiqui; Sahar Mumtaz; Talha Javed; Muhammad Umar; M. Yousuf Adnan; Manzer H. Siddiqui (Journal of Plant Growth Regulation, 2023)

Diosgenin, a steroidal sapogenin, arrests arthritis through modulation of inflammatory cytokines and oxidative stress biomarkers in Wistar rats - Maira Javed; Ammara Saleem; Muhammad Furqan Akhtar (Inflammopharmacology, 2023)

Long-term spatio-temporal trends in atmospheric aerosols and trace gases over Pakistan using remote sensing - Muhammad Adil Javed; Usman Mehmood; Salman Tariq; Zia ul Haq (Acta Geophysica, 2023)

Screening and growth assessment of indigenous and exotic sesame genotypes under osmotic stress - Jahangir Ahmed; Ghulam Qadir; Muhammad Fraz Ali; Talha Javed; Hafiz Muhammad Jhanzab; Fahad Masoud Wattoo; Imran Mahmood; Muhammad Ansar; Muhammad Akram Khan; Usman Zulfiqar; Bilal Ahamad Paray (South African Journal of Botany, 2023)

Applicability of machine learning techniques in predicting wheat yield based on remote sensing and climate data in Pakistan, South Asia - Sana Arshad; Jamil Hasan Kazmi; Muhammad Gohar Javed; Safwan Mohammed (European Journal of Agronomy, 2023)

Bio-fabrication of zinc oxide nanoparticles from Picea smithiana and their potential antimicrobial activities against Xanthomonas campestris pv. Vesicatoria and Ralstonia solanacearum causing bacterial leaf spot and bacterial wilt in tomato - Fazal ur Rehman; Najeeba Paree Paker; Mohsin Khan; Muhammad Naeem; Muhammad Farooq Hussain Munis; Shafiq ur Rehman; Hassan Javed Chaudhary (World Journal of Microbiology and Biotechnology, 2023)

A causal link between financialization and ecological status: a novel framework for Asian countries? - Saeed Ahmad Sabir; Mubeen Abdur Rehman; Muhammad Zahid Javed; Usman Mehmood; Rabia Ishaq (Environmental Science and Pollution Research, 2023)

Health risk assessment and bioaccumulation of potentially toxic metals from water, soil, and forages near coal mines of district Chakwal, Punjab, Pakistan - Nida Zainab; Shehzad Mehmood; Amna Shafiq-ur-Rehman; Adeela Munir; Zafar Iqbal Tanveer; Zaib Un Nisa; Muhammad Imran; Muhammad Tariq Javed; Hassan Javed Chaudhary (Environmental Geochemistry and Health, 2023)

Geospatial soil loss risk assessment using RUSLE model: a study of Panjkora River Basin, Khyber Pakhtunkhwa, Pakistan - Muhammad Jamal Nasir; Said Alam; Waqas Ahmad; Sayed M. Bateni; Javed Iqbal; Mansour Almazroui; Burhan Ahmad (Arabian Journal of Geosciences, 2023)

RETRACTED: Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2023)

Genotoxic effects of polycyclic aromatic hydrocarbons (PAHs) present in vehicle-wash wastewater on grass carp (Ctenopharyngodon idella) and freshwater mussels (Anodonta cygnea) - Sardar Khan; Zahir Qamar; Ajmal Khan; Muhammad Waqas; Javed Nawab; Muhmmmad Khisroon; Ajmal Khan (Environmental Pollution, 2023)

Biodegradation of monocrotophos by Brucella intermedia Msd2 isolated from cotton plant - Shazmin; Siti Aqlima Ahmad; Tatheer Alam Naqvi; Muhammad Farooq Hussain Munis; Muhammad Tariq Javed; Hassan Javed Chaudhary (World Journal of Microbiology and Biotechnology, 2023)

Improving Lignin Metabolism, Lodging Resistance, and Yield of Rapeseed (Brassica napus L.) by Applying Straw-Fermented Fertilizer - Yue Hu; Hafiz Hassan Javed; Yong-Li Du; Qi-Wen Liao; Wen Ye; Jing Zhou; Xiao Peng; Muhammad Arslan; Ali Raza; Yong-Cheng Wu (Journal of Soil Science and Plant Nutrition, 2023)

Optimum Zinc Fertilization and Sowing Date Improved Growth, Yield Components, and Grain Zn Contents of Bread Wheat Under Different Tillage Systems - Ijaz Hussain; Muhammad Ijaz; Sami Ul-Allah; Abdul Sattar; Ahmad Sher; Ahmad Nawaz; Abdul Ghaffar; Muhammad Habib ur Rahman; Saeed Ahmad; Iqra Rasheed; Omaima Nasif; Mohammad Javed Ansari (Journal of Soil Science and Plant Nutrition, 2023)

Arsenic Speciation in Rice, Mechanisms and Associated Health Risk Through Rice Consumption in Various Districts of Khyber Pakhtunkhwa, Pakistan - Tasneem Sarwar; Sardar Khan; Javed Nawab; Said Muhammad; Shehla Amin; Janas Khan; Adnan Sarwar; Iqbal Haider; Qing Huang (Exposure and Health, 2023)

Arsenic Removal from Groundwater Using Iron Pyrite: Influence Factors and Removal Mechanism - Muhammad Yousuf Jat Baloch; Chunli Su; Shakeel Ahmed Talpur; Javed Iqbal; Kulvinder Bajwa (Journal of Earth Science, 2023)

In-field deployable and facile nanosensor for the detection of pesticides residues - Naveed Akhtar Shad; Anam Munawar; Yasir Javed; Allah Rakha; Ahsan Riaz; Salah Ud Din; Iqra Zareef; Muhammad Munir Sajid; Muahmmad Farhan Khan; Sareen Akhtar; Midhat Salman (Analytica Chimica Acta, 2023)

Estimating ground-level PM2.5 using subset regression model and machine learning algorithms in Asian megacity, Dhaka, Bangladesh - Abu Reza Md. Towfiqul Islam; Mohammed Al Awadh; Javed Mallick; Subodh Chandra Pal; Rabin Chakraborty; Md. Abdul Fattah; Bonosri Ghose; Most. Kulsuma Akther Kakoli; Md. Aminul Islam; Hasan Raja Naqvi; Muhammad Bilal; Ahmed Elbeltagi (Air Quality, Atmosphere & Health, 2023)

Exploration of plant growth promoting traits and regulatory mechanisms of Bacillus anthracis PM21 in enhancing salt stress tolerance in maize - Muhammad Atif Azeem; Fawad Ali; Abid Ullah; Mahmood Iqbal; Kishwar Ali; Dunia A. Al Farraj; Mohamed S. Elshikh; Qirat Naz; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2023)

Ecological footprint, globalization, and economic growth: evidence from Asia - Saba Javeed; Hafiz Muhammad Abubakar Siddique; Fahad Javed (Environmental Science and Pollution Research, 2023)

Application of silicon and sodium hydrosulfide alleviates arsenic toxicity by regulating the physio-biochemical and molecular mechanisms of Zea mays - Aishah Alatawi; Manar Fawzi Bani Mfarrej; Rana M. Alshegaihi; Muhammad Ahsan Asghar; Sahar Mumtaz; Ghulam Yasin; Romina Alina Marc; Shah Fahad; Mohsen Mohamed Elsharkawy; Sadia Javed; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

RETRACTED: Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review - Awais Ahmad; Shumila Shaheen; Saadat Majeed; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Sufyan Javed; Rafael Luque; Lalitha Gnanasekaran (Fuel, 2023)

Interactive effect of salicylic acid and triacontanol to improve lead stress tolerance in maize (Zea mays L.) - Javed Iqbal; Shagufta Perveen; Abida Parveen; Muhammad Saeed; Sara Zafar; Naeem Iqbal (Arabian Journal of Geosciences, 2023)

Multiple strategies for the development of multienzyme complex for one-pot reactions - Bahzad Ahmad Farhan; Li Zhihe; Shehbaz Ali; Tawaf Ali Shah; Li Zhiyu; Andong Zhang; Sadia Javed; Muhammad Asad (Environmental Science and Pollution Research, 2023)

Erratum to ‘Role of endophytic bacteria in salinity stress amelioration by physiological and molecular mechanisms of defense: A comprehensive review’ South African Journal of Botany, Volume 151, December 2022, Pages 33-46 - Baber Ali; Aqsa Hafeez; Muhammad Ammar Javed; Muhammad Siddique Afridi; Hina Ali Abbasi; Ayesha Qayyum; Tayyaba Batool; Abid Ullah; Romina Alina Marc; Soad K. Al Jaouni; Dalal Hussien M. Alkhalifah; Samy Selim (South African Journal of Botany, 2023)

Removal of ceftriaxone sodium antibiotic from pharmaceutical wastewater using an activated carbon based TiO2 composite: Adsorption and photocatalytic degradation evaluation - Muneeb Abdullah; Javed Iqbal; Muhammad Saif Ur Rehman; Usman Khalid; Fahad Mateen; Salman Noshear Arshad; Abdullah G. Al-Sehemi; Hamed Algarni; Omar A. Al-Hartomy; Tahir Fazal (Chemosphere, 2023)

Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

Reconnoitering the capabilities of nodule endophytic Pantoea dispersa for improved nodulation and grain yield of chickpea (Cicer arietinum L.) - Mohsin Tariq; Nayab Hasnain; Ijaz Rasul; Muhammad Azeem Asad; Aqsa Javed; Kamran Rashid; Javeria Shafique; Wajeeha Iram; Amir Hameed; Marriam Zafar (World Journal of Microbiology and Biotechnology, 2023)

Remediation of Environmental Contaminants Through Phytotechnology - Abdul Latif; Aown Abbas; Javed Iqbal; Muhammad Azeem; Waleed Asghar; Rehmat Ullah; Muhammad Bilal; Muhammad Arsalan; Madeeha Khan; Rizwan Latif; Muhammad Ehsan; Asad Abbas; et al. (Water, Air, & Soil Pollution, 2023)

Human Health and Ecological Risks Associated with Total and Bioaccessible Concentrations of Cadmium and Lead in Urban Park Soils - Muhammad Amjad Khan; Javed Nawab; Anwarzeb Khan; Mark L. Brusseau; Shah Nawaz Khan; Neelum Ali; Saraj Bahadur; Sardar Khan; Qing Huang (Bulletin of Environmental Contamination and Toxicology, 2023)

Assessment of the dibenzothiophene desulfurization potential of indigenously isolated bacterial consortium IQMJ-5: a different approach to safeguard the environment - Javed Khan; Muhammad Ishtiaq Ali; Asif Jamal; Jahangir Khan Achakzai; Jafir Hussain Shirazi; Abdul Haleem (Archives of Microbiology, 2023)

Groundwater fluoride and nitrate contamination and associated human health risk assessment in South Punjab, Pakistan - Javed Iqbal; Chunli Su; Mengzhu Wang; Hasnain Abbas; Muhammad Yousuf Jat Baloch; Junaid Ghani; Zahid Ullah; Md. Enamul Huq (Environmental Science and Pollution Research, 2023)

A Hematological and Histopathological Study on Diphenhydramine Nasal Nano-gel and Nano-emulgel for the Management of Allergic Rhinitis in Animal Model - Hina Javed; Syed Nisar Hussain Shah; Furqan Muhammad Iqbal; Nida Javed; Benish Saeed (AAPS PharmSciTech, 2023)

Elucidating molecular characterization of chlorpyrifos and profenofos degrading distinct bacterial strains for enhancing seed germination potential of Gossypium arboreum L - Najeeba Paree Paker; Shehzad Mehmood; Muhammad Tariq Javed; Christos A. Damalas; Fazal ur Rehman; Hassan Javed Chaudhary; Muhammad Zeshan Munir; Mahrukh Malik (Environmental Science and Pollution Research, 2023)

In-situ construction of binder-free MnO2/MnSe heterostructure membrane for high-performance energy storage in pseudocapacitors - Qasim Abbas; Abdul Mateen; Sajid Hussain Siyal; Najam Ul Hassan; Asma A. Alothman; Mohamed Ouladsmane; Sayed M. Eldin; Mohd Zahid Ansari; Muhammad Sufyan Javed (Chemosphere, 2023)

The versatility of nanocellulose, modification strategies, and its current progress in wastewater treatment and environmental remediation - Ajmal Shahzad; Muhammad Wajid Ullah; Jawad Ali; Kazim Aziz; Muhammad Asif Javed; Zhijun Shi; Sehrish Manan; Mazhar Ul-Islam; Mudasir Nazar; Guang Yang (Science of The Total Environment, 2023)

Earth- and marine-life-resembling nanostructures for electrochemical energy storage - Iftikhar Hussain; Charmaine Lamiel; Muhammad Sufyan Javed; Muhammad Ahmad; Xi Chen; Sumanta Sahoo; Xiaoxia Ma; Majed A. Bajaber; Mohd Zahid Ansari; Kaili Zhang (Chemical Engineering Journal, 2023)

Adsorption modeling and thermodynamic characteristics of silver ions on to low-rank Pakistani coal - Tariq Javed; Nasir Khalid; Muhammad Latif Mirza (Sustainable Water Resources Management, 2023)

Biofilm formation and flocculation potential analysis of halotolerant Bacillus tequilensis and its inoculation in soil to mitigate salinity stress of chickpea - Urooj Haroon; Muhammad Farooq Hussain Munis; Fiza Liaquat; Maria Khizar; Minhas Elahi; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2023)

Geochemistry and in-situ U-Th/Pb Geochronology of the Jambil Meta-Carbonatites, Northern Pakistan: Implications on Petrogenesis and Tectonic Evolution - Asad Khan; Shah Faisal; Kyle P. Larson; Delores M. Robinson; Huan Li; Zaheen Ullah; Mark Button; Javed Nawab; Muhammad Farhan; Liaqat Ali; Muhammad Ali (Journal of Earth Science, 2023)

Microwave-assisted sustainable exploration of cocklebur leaves (Xanthium strumarium L.) as a novel source of distinct yellow natural colorant for dyeing cotton fabric - Muhammad Hussaan; Ahmad Raza; Noman Habib; Shahid Adeel; Naeem Iqbal; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2023)

Green synthesized Ag decorated CeO2 nanoparticles: Efficient photocatalysts and potential antibacterial agents. - Awais Ahmad; Muhammad Sufyan Javed; Safia Khan; Tahani Mazyad Almutairi; Abdallah A.A. Mohammed; Rafael Luque (Chemosphere, 2023)

Impact of seasons and wastewater cultivation on the biomass and biodiesel production by the Plectonema terebrans BERC10 as a candidate for a multiproduct algal biorefinery - Muhammad Nabeel Haider; Aqib Zafar Khan; Muhammad Usman; Deepanraj Balakrishnan; Muhammad Rizwan Javed; Sana Malik; Chen-Guang Liu; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf (Fuel, 2023)

Hydrogen Production through Water Vapors using Optimized Corona-DBD Hybrid Plasma Micro-Reactor - Muhammad Younas; Sumeer Shafique; Abrar Faisal; Ainy Hafeez; Fahed Javed; Maria Mustafa; Fahad Rehman (Fuel, 2023)

The quest for negative electrode materials for Supercapacitors: 2D materials as a promising family - Muhammad Sufyan Javed; Abdul Mateen; Iftikhar Hussain; Salamat Ali; Sumreen Asim; Awais Ahmad; Elsayed tag Eldin; Majed A. Bajaber; Tayyaba Najam; Weihua Han (Chemical Engineering Journal, 2023)

Genome mining, antimicrobial and plant growth-promoting potentials of halotolerant Bacillus paralicheniformis ES-1 isolated from salt mine - Sajid Iqbal; Muhammad Qasim; Hazir Rahman; Naeem Khan; Rehan Zafar Paracha; Muhammad Faraz Bhatti; Aneela Javed; Hussnain Ahmed Janjua (Molecular Genetics and Genomics, 2023)

Biochemical Characterization and Potential of Bacillus safensis Strain SCAL1 to Mitigate Heat Stress in Solanum lycopersicum L. - Tehmeena Mukhtar; Fawad Ali; Mazhar Rafique; Javed Ali; Muhammad Siddique Afridi; Donald Smith; Shehzad Mehmood; Amna; Alfred Souleimanov; Ghulam Jellani; Tariq Sultan; Farooq Hussain Munis; et al. (Journal of Plant Growth Regulation, 2023)

Occurrence and Distribution of Heavy Metals in Mining Degraded Soil and Medicinal Plants: A Case Study of Pb/Zn Sulfide Terrain Northern Areas, Pakistan - Javed Nawab; Muhammad Idress; Sajid Ullah; Gul Rukh; Rimsha Zainab; Hassan Sher; Junaid Ghani; Sardar Khan; Zahid Ullah; Imran Ahmad; Syed Weqas Ali (Bulletin of Environmental Contamination and Toxicology, 2023)

Modelling land use/land cover (LULC) change dynamics, future prospects, and its environmental impacts based on geospatial data models and remote sensing data - Muhammad Nasar Ahmad; Zhenfeng Shao; Akib Javed (Environmental Science and Pollution Research, 2022)

Genome wide association mapping of yield and various desirable agronomic traits in Rice - Muhammad Ashfaq; Abdul Rasheed; Muhammad Sajjad; Muhammad Ali; Bilal Rasool; Muhammad Arshad Javed; Sami Ul Allah; Shabnum Shaheen; Alia Anwar; Muhammad Shafiq Ahmad; Urooj Mubashar (Molecular Biology Reports, 2022)

Zinc–Lysine (Zn–Lys) Decipher Cadmium Tolerance by Improved Antioxidants, Nutrient Acquisition, and Diminished Cd Retention in Two Contrasting Wheat Cultivars - Muhammad Hussaan; Kashif Tanwir; Saghir Abbas; Muhammad Tariq Javed; Naeem Iqbal (Journal of Plant Growth Regulation, 2022)

Genetic diversity and population structure assessed through simple sequence repeat markers in Saccharum spp. hybrids from Pakistan and Sri Lanka - Sundas Shahzad; Muhammad Saeed; Shagufta Perveen; Muhammad Azeem; Iqra Sajjad; Shazia Saeed; Muhammad Naeem; Alia Javed; Iqra Sultan; Ukasha Faria; Sana Maryam; Muhammad Zaid Yousaf (Genetic Resources and Crop Evolution, 2022)

Cytotoxic and genotoxic evaluation of bisphenol S on onion root tips by Allium cepa and comet tests - Muhammad Muddassir Ali; Areej Fatima; Sadia Nawaz; Abdul Rehman; Maryam Javed; Asif Nadeem (Environmental Science and Pollution Research, 2022)

Farmers’ climate change risk perception, adaptation capacity and barriers to adaptation: a multi-method approach - Muhammad Humayun Kabir; Kh. Zulfikar Hossain; Md. Javed Azad; Mou Leong Tan (Journal of Environmental Studies and Sciences, 2022)

Integration of RT-LAMP and Microfluidic Technology for Detection of SARS-CoV-2 in Wastewater as an Advanced Point-of-Care Platform - Ahmed Donia; Muhammad Furqan Shahid; Sammer-ul Hassan; Ramla Shahid; Aftab Ahmad; Aneela Javed; Muhammad Nawaz; Tahir Yaqub; Habib Bokhari (Food and Environmental Virology, 2022)

Mixing tannery effluent had fertilizing effect on growth, nutrient accumulation, and photosynthetic capacity of some cucurbitaceous vegetables: A little help from foe - Muhammad Zaheer; Zafar Ullah Zafar; Habib-ur-Rehman Athar; Hussan Bano; Misbah Amir; Ayesha Khalid; Hamid Manzoor; Muhammad Javed; Muhammad Iqbal; Chukwuma C. Ogbaga; Muhammad Kamran Qureshi (Environmental Science and Pollution Research, 2022)

Acinetobacter schindleri SR-5–1 decipher morpho-physio-biochemical and nutritional improvements to Pisum sativum L. and Linum usitatissimum L. maintained under wastewater/cadmium stress - Sherjeel Hashmat; Kashif Tanwir; Saghir Abbas; Muhammad Shahid; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2022)

NGS-driven molecular diagnosis of heterogeneous hereditary neurological disorders reveals novel and known variants in disease-causing genes - Ayaz Khan; Shixiong Tian; Muhammad Tariq; Sheraz Khan; Muhammad Safeer; Naimat Ullah; Nazia Akbar; Iram Javed; Mahnoor Asif; Ilyas Ahmad; Shahid Ullah; Humayoon Shafique Satti; et al. (Molecular Genetics and Genomics, 2022)

Biomonitoring of mercury in water, sediments, and fish (brown and rainbow trout) from remote alpine lakes located in the Himalayas, Pakistan - Javed Nawab; Junaid Ghani; Syed Aziz Ur Rehman; Muhammad Idress; Muhammad Luqman; Sardar Khan; Ali Asghar; Ziaur Rahman (Environmental Science and Pollution Research, 2022)

Source parameters of the Fatehjang, Pakistan earthquake $$(M_{w} 4.1)$$ of 28 August 2020 - Sadia Sabahat; Mohammad Tahir; Muhammad Tahir Iqbal; Javed Iqbal; Talat Iqbal (Arabian Journal of Geosciences, 2022)

Effects of maize silage substitution with sugarbeet or citrus pulp ensiled with corncobs on growth performance, digestibility, and economic benefits in buffalo calves - Muhammad Iqbal Anjum; Shahbaz Javaid; Faisal Ashfaq; Javed Iqbal (Tropical Animal Health and Production, 2022)

Yttrium Doped Bismuth Vanadate Titania Heterojunction for Efficient Photoreduction of Cr from Wastewater Under Visible Light - Uswa Zahoor; Muhammad Imran Rameel; Ahad Hussain Javed; Muhammad Abdullah Khan; Jehan Y. Al-Humaidi; Sajid Iqbal; Afrah Mohammed Aldawsari; Afzal Shah (International Journal of Environmental Research, 2022)

Deciphering distinct root exudation, ionomics, and physio-biochemical attributes of Serratia marcescens CP-13 inoculated differentially Cd tolerant Zea mays cultivars - Kashif Tanwir; Muhammad Shahid; Saghir Abbas; Qasim Ali; Muhammad Sohail Akram; Hassan Javed Chaudhary; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2022)

Assessing Salt Tolerance Induction in Potato by Salicylic Acid Using Morpho-Physio-Biochemical, Ionic, and Yield Indices - Hafiz Nazar Faried; C. M. Ayyub; Fahad Masoud Wattoo; Mohsin Bashir; Kashif Razzaq; Gulzar Akhtar; Abid Hussain; Sami Ullah; Javed Iqbal Wattoo; Muhammad Amin; Shoaib Munir; Muhammad Rashid Shaheen; et al. (Potato Research, 2022)

Structural and Electronic (Absorption and Fluorescence) Properties of a Stable Triplet Diphenylcarbene: A DFT Study - Abrar Ul Hassan; Ayesha Mohyuddin; Sohail Nadeem; Cihat Güleryüz; Sadaf Ul Hassan; Mohsin Javed; Muhammad Salman Muhsan (Journal of Fluorescence, 2022)

Pcal_2031, a RecA/Rad51 homologue from Pyrobaculum calidifontis, complements the ultraviolet light sensitivity of Escherichia coli - Syed Nasim Abbas; Mehwish Aslam; Amina Maqsood; Hafiza Zumra Fatima; Muhammad Arshad Javed; Naeem Rashid (Biologia, 2022)

Halotolerant Plant Growth-Promoting Rhizobacteria Induce Salinity Tolerance in Wheat by Enhancing the Expression of SOS Genes - Urooj Haroon; Maria Khizar; Fiza Liaquat; Musrat Ali; Mahnoor Akbar; Kinza Tahir; Syeda Saira Batool; Asif Kamal; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Journal of Plant Growth Regulation, 2022)

Distribution and Bioaccumulation of Essential and Toxic Metals in Tissues of Thaila (Catla catla) from a Natural Lake, Pakistan and Its Possible Health Impact on Consumers - Muhammad Saleem; Javed Iqbal; Zongbo Shi; Scott H. Garrett; Munir H. Shah (Journal of Marine Science and Engineering, 2022)
Although fish are often recommended as a component of a healthy diet, the environmental accumulation of heavy metals in many fish species has been of considerable concern for those weighing the nutritional health benefits against adverse toxic outcome of excess intake of toxic metals. This study aimed to determine the concentration of essential and toxic metals in the tissues of Catla catla in Mangla Lake and to assess the possible risk to the consumers. Fifty samples of Catla catla were collected from Mangla Lake, Mirpur, Azad Jammu and Kashmir, Pakistan and analyzed for eighteen metals including essential and trace metals. The measured range concentrations (µg/g, wet weight) in muscle tissues, in decreasing order, were: K (955–1632), Ca (550–2081), Na (449–896), Mg (129–312), Zn (61.2–215), Fe (11.6–26.8), Sr (2.60–9.27), Pb (1.72–7.81), Se (1.55–3.55), Co (0.12–4.08), Mn (1.04–4.33), Ni (0.69–3.06), Cu (0.88–2.78), Cr (0.45–1.88), As (0.67–1.58), Cd (0.28–0.56), Hg (0.17–0.57) and Li (0.12–0.38). The metal concentrations found in this study were comparatively higher than those reported in literature. A majority of the metals exhibited higher accumulation in gills compared with those in scales and muscles. Mean levels of Pb, As, Co, Mn, Cd, Cr and Zn in Catla catla muscle were found to be exceeding the international permissible limits for the safe human consumption. The condition factor (K), as an indicator of fish health status, indicated that Catla catla of Mangla Lake are in good health condition. The metal pollution index (MPI) of gills (27.9), scales (12.5) and muscle (7.57) indicated low contamination. Moreover, human health risk was evaluated using estimated weekly intake (EWI) and daily intake (EDI), target hazard quotient (THQ), hazard index (HI) and target cancer risk (TCR). Estimated weekly and daily intake values for As, Cd, Cr, Hg, Ni and Pb were higher than provisional permissible tolerable weekly intake and permissible tolerable daily intake while THQ for As, Cd, Cr, Hg, Pb, Se and Zn was higher than 1. The THQ for As, Hg and Pb was several folds higher than 1, indicative of lifetime non-carcinogenic health risks to the consumers. The hazard index indicated cumulative risk, which greatly increased with increasing fish consumption. Target cancer risk indicated that the people eating the Catla catla from Mangla Lake were exposed to As, Cd, Cr, Ni and Pb with a significant lifetime carcinogenic risk. In summary, consumption of Catla catla from this lake was found to be associated with an increased lifetime risk to the general health of the consumers.

Fabrication of polysulfone mixed matrix membrane for wastewater treatment - Kousar Parveen; Uzaira Rafique; Muhammad Javed Akhtar (Journal of Environmental Health Science and Engineering, 2022)

Mix-method modelling of actors’ capacity for environmental sustainability and climate compatible development in energy sector - Kanwar Muhammad Javed Iqbal; Nadia Akhtar; Muhammad Owais Khan; Muhammad Irfan Khan (Environmental Science and Pollution Research, 2022)

Geological mapping and neo-tectonics studies of the eocene limestone distributed over Mala Khel Anticline, Trans Indus ranges, North-West Himalayas, Pakistan - Nazir-ur- Rehman; Sajjad Ahmad; Shah Faisal; Asghar Ali; Muhammad Waqar Azeem; Afrasiab; Shuja Ullah; Salik Javed (Arabian Journal of Geosciences, 2022)

Development of Optimized Sumatriptan–Prochlorperazine Combined Orodispersible Films Without Disintegrant: in vitro, ex vivo and in vivo Characterization - Sana Javed; Amjad Hussain; Pervaiz Akhtar Shah; Syed Atif Raza; Ubaid Ullah Anwer; Rahat Shamim; Fatima Rasool; Muhammad Ahsan Hafiz; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2022)

Heavy metal remediation and resistance mechanism of Aeromonas , Bacillus , and Pseudomonas : A review - Ali Fakhar; Bushra Gul; Ali Raza Gurmani; Shah Masaud Khan; Shafaqat Ali; Tariq Sultan; Hassan Javed Chaudhary; Mazhar Rafique; Muhammad Rizwan (Critical Reviews in Environmental Science and Technology, 2022)

Application of zinc oxide nanoparticles immobilizes the chromium uptake in rice plants by regulating the physiological, biochemical and cellular attributes - Farwa Basit; Muhammad Mudassir Nazir; Muhammad Shahid; Saghir Abbas; Muhammad Tariq Javed; Tahir Naqqash; Yihan Liu; Guan Yajing (Physiology and Molecular Biology of Plants, 2022)

Single nucleotide polymorphism based assessment of genetic diversity in local and exotic onion genotypes - Najma Tabussam; Rashid Mehmood Rana; Fahad Masoud Wattoo; Azeem Iqbal Khan; Rai Muhammad Amir; Talha Javed; Sunny Ahmar; Eldessoky S. Dessoky; Nader R. Abdelsalam (Molecular Biology Reports, 2022)

Omics: a tool for resilient rice genetic improvement strategies - Muhammad Naeem; Zeeshan Ali; Anzal Khan; Sami-Ul-Allah; Hassan Javed Chaudhary; Javeria Ashraf; Faheem Shahzad Baloch (Molecular Biology Reports, 2022)

Methotrexate-loaded biodegradable nanoparticles exert anti-arthritic effect by downregulating pro-inflammatory cytokines in Freund’s complete adjuvant-induced arthritic rats - Muhammad Usman Saleem; Faqir Muhammad; Ali Sharif; Muhammad Imran Arshad; Kanwal Akhtar; Yasir Javed; Bushra Akhtar (Inflammopharmacology, 2022)

Exploring the dynamic effects of shocks in monetary and fiscal policies on the environment of developing economies: evidence from the CS-ARDL approach - Shaista Noureen; Javed Iqbal; Muhammad Zubair Chishti (Environmental Science and Pollution Research, 2022)

Cyclo(L-Leucyl-L-Prolyl) from Lactobacillus coryniformis BCH-4 inhibits the proliferation of Aspergillus flavus: an in vitro to in silico approach - Mahwish Salman; Anam Tariq; Ghulam Mustafa; Muhammad Rizwan Javed; Shazia Naheed; Sarmad Ahmad Qamar (Archives of Microbiology, 2022)

Exopolysaccharides production from marine Bacillus strains and their antioxidant and bio-flocculant capacities - Nimrah Khalid; Muhammad Asgher; Fatma Hussain; Javed Iqbal (Archives of Microbiology, 2022)

Hardwood modified and unmodified biochar amendments used for saline alkali soil remediation: phosphorus availability and its plant uptake - Ihsan Ullah; Sardar Khan; Javed Nawab; Muhammad Amjad Khan; Shah Jehan (Arabian Journal of Geosciences, 2022)

Imaging of rupture process of 2005 Mw 7.6 Kashmir earthquake using back projection techniques - Mahmood Sultan; Farhan Javed; Muhammad Fahad Mahmood; Muhammad Ali Shah; Khawar Ashfaq Ahmed; Talat Iqbal (Arabian Journal of Geosciences, 2022)

Biorational approach for management of whitefly, Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae), on cotton crop - Muhammad Iqbal; Muhammad Jalal Arif; Shafqat Saeed; Mansoor ul Hasan; Nazir Javed (International Journal of Tropical Insect Science, 2022)

Purification and functional characterization of lectin from Chenopodium album - Mahwish Javed; Muhammad Bilal; Bushra Tabassum; Arif Malik; Olawale Samuel Adeyinka; Muhammad Tariq; Idrees Ahmad Nasir (Journal of Proteins and Proteomics, 2022)

Performance and welfare of dairy buffaloes subjected to different cooling strategies during subtropical summer - Musa Bah; Muhammad Qamer Shahid; Talat Naseer Pasha; Khalid Javed (Tropical Animal Health and Production, 2022)

Growth prediction of Alternanthera philoxeroides under salt stress by application of artificial neural networking - Qaiser Javed; Ahmad Azeem; Jianfan Sun; Ikram Ullah; Daolin Du; Muhammad Ali Imran; Muhammad Imran Nawaz; Hassan T. Chattha (Plant Biosystems, 2022)

An impact of climate change and groundwater salinity on shadow price of water, farmers’ revenue, and socioeconomic and environmental indicators in district Kohat-Pakistan - Arshad Ahmad Khan; Sufyan Ullah Khan; Muhammad Abu Sufyan Ali; Tehseen Javed; Aftab Khan; Jianchao Luo (Environmental Science and Pollution Research, 2022)

Anti-hepatitis C virus and synergistic potential of Syzgium cumine a bioassay guided screening in liver-infected hepatocytes - Sana Riaz; Hira Tiwana; Muhammad Adil; Khaver Ali; Tariq Javed (Archives of Microbiology, 2022)

Phenomena, factors of wax deposition and its management strategies - Syed Imran Ali; Shaine Mohammadali Lalji; Javed Haneef; Muhammad Arqam Khan; Mohsin Yousufi; Nimra Yousaf; Abdus Saboor (Arabian Journal of Geosciences, 2022)

Seed Priming with Sodium Nitroprusside and H2O2 Confers Better Yield in Wheat Under Salinity: Water Relations, Antioxidative Defense Mechanism and Ion Homeostasis - Noman Habib; Qasim Ali; Shafaqat Ali; Muhammad Zulqarnain Haider; Muhammad Tariq Javed; Mubashra Khalid; Rashida Perveen; Abdulaziz Abdullah Alsahli; Mohammed Nasser Alyemeni (Journal of Plant Growth Regulation, 2021)

Genome-wide identification and characterization of a plant-specific Dof transcription factor gene family in olive (Olea europaea) and its comparison with Arabidopsis - Mariyam; Muhammad Shafiq; Muhammad Haseeb; Rana Muhammad Atif; Syed Agha Armaghan Asad Abbas Naqvi; Numan Ali; Muhammad Arshad Javed; Fizza Gillani; Muhammad Saleem Haider (Horticulture, Environment, and Biotechnology, 2021)

Correction to: Inventory and Quantitative Valuation of Geological and Geomorphological Sites from Gilgit‑Baltistan, Northern Pakistan - Javed Akhter Qureshi; Muzammil Khan; Shehzad Sikandar; Garee Khan; Naeem Abbas; Asghar Khan; Muhammad Alam; Rehmat Karim; Sarah J. Halvorson (Geoheritage, 2021)

Inventory and Quantitative Valuation of Geological and Geomorphological Sites from Gilgit-Baltistan, Northern Pakistan - Javed Akhter Qureshi; Muzammil Khan; Shehzad Sikandar; Garee Khan; Naeem Abbas; Asghar Khan; Muhammad Alam; Rehmat Karim; Sarah J. Halvorson (Geoheritage, 2021)

Functional identification of G. hirsutum genes for their role in normal plant development and resistance against Verticillium dahliae using virus-induced gene silencing - Roma Mustafa; Muhammad Javed Iqbal; Muhammad Hamza; Atiq Ur Rehman; Ismail Buzdar; Hira Kamal; Shahid Mansoor; Imran Amin (European Journal of Plant Pathology, 2021)

Facile synthesis, spectroscopic evaluation and antimicrobial screening of metal endowed triazole compounds - Sajjad H. Sumrra; Wardha Zafar; Hassan Javed; Muddassar Zafar; Muhammad Z. Hussain; Muhammad Imran; Muhammad A. Nadeem (BioMetals, 2021)

Exogenous melatonin regulates chromium stress-induced feedback inhibition of photosynthesis and antioxidative protection in Brassica napus cultivars - Ahsan Ayyaz; Muhammad Ahsan Farooq; Muhammad Dawood; Abdul Majid; Muhammad Javed; Habib‐ur‐Rehman Athar; Hussan Bano; Zafar Ullah Zafar (Plant Cell Reports, 2021)

Expression studies of stress responsive genes in cotton Gossypium hirsutum L. - Muhammad Naeem; Muhammad Iqbal; Sami Ul-Allah; Hassan Javed Chaudhary; Wajad Nazeer; Javeria Ashraf; Faheem Shahzad Baloch (Molecular Biology Reports, 2021)

Long-term copper exposure promotes apoptosis and autophagy by inducing oxidative stress in pig testis - Yuanliang Li; Hanming Chen; Jianzhao Liao; Keli Chen; Muhammad Tariq Javed; Na Qiao; Qiwen Zeng; Bingxian Liu; Jiangnan Yi; Zhaoxin Tang; Ying Li (Environmental Science and Pollution Research, 2021)

Occurrence, distribution, and pollution indices of potentially toxic elements within the bed sediments of the riverine system in Pakistan - Javed Nawab; Zia Ud Din; Riaz Ahmad; Sardar Khan; Mazhar Iqbal Zafar; Shah Faisal; Waleed Raziq; Hamza Khan; Zia Ur Rahman; Abid Ali; Muhammad Qayash Khan; Sajid Ullah; et al. (Environmental Science and Pollution Research, 2021)

An asymmetric analysis of the role of exports and imports in consumption-based carbon emissions in the G7 economies: evidence from nonlinear panel autoregressive distributed lag model - Najibullah; Javed Iqbal; Misbah Nosheen; Muhammad Waqas Khan; Ehtsham Ul Haq Raja; Muhammad Jasim (Environmental Science and Pollution Research, 2021)

Evaluation of the allelopathic effects of leachate from an invasive species (Wedelia triobata) on its own growth and performance and those of a native congener (W. chinensis) - Muhammad Saif Ullah; Jianfan Sun; Susan Rutherford; Ikram Ullah; Qaiser Javed; Ghulam Rasool; Muhammad Ajmal; Daolin Du (Biological Invasions, 2021)

Biotechnological approaches in agriculture and environmental management - bacterium Kocuria rhizophila 14ASP as heavy metal and salt- tolerant plant growth- promoting strain - Muhammad Siddique Afridi; Jonathan d. Van Hamme; Jochen Bundschuh; Sumaira; Muhammad Nadeem Khan; Abdul Salam; Muhammad Waqar; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Biologia, 2021)

Deciphering distinct biological control and growth promoting potential of multi-stress tolerant Bacillus subtilis PM32 for potato stem canker - Shehzad Mehmood; Muhammad Atif Muneer; Muhammad Tahir; Muhammad Tariq Javed; Tariq Mahmood; Muhammad Siddique Afridi; Najeeba Paree Pakar; Hina Ali Abbasi; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2021)

Correction to: influence of foliar glutathione and putrescine on metabolism and mineral status of genetically diverse rapeseed cultivars under hexavalent chromium stress - Almas Jahan; Muhammad Iqbal; Fahad Shafiq; Arif Malik; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2021)

Globalization, financial development, and environmental sustainability: evidence from heterogenous income groups of Asia - Ayaz Zafar; Muhammad Tariq Majeed; Misbah Nosheen; Javed Iqbal (Environmental Science and Pollution Research, 2021)

Influence of foliar glutathione and putrescine on metabolism and mineral status of genetically diverse rapeseed cultivars under hexavalent chromium stress - Almas Jahan; Muhammad Iqbal; Fahad Shafiq; Arif Malik; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2021)

The nexus between meteorological parameters and COVID-19 pandemic: case of Islamabad, Pakistan - Abdul Rehman; Fatima Ashraf; Zeeshan Javed; Mudassar Hussain; Taimoor Hassan Farooq; Awais Shakoor; Sher Muhammad Shahzad (Environmental Sustainability, 2021)

Jasmonic acid: a key frontier in conferring abiotic stress tolerance in plants - Ali Raza; Sidra Charagh; Zainab Zahid; Muhammad Salman Mubarik; Rida Javed; Manzer H. Siddiqui; Mirza Hasanuzzaman (Plant Cell Reports, 2021)

Correction to: Bacillus subtilis Y16 and biogas slurry enhanced potassium to sodium ratio and physiology of sunflower (Helianthus annuus L.) to mitigate salt stress - Samina Hamid; Iftikhar Ahmad; Muhammad Javed Akhtar; Muhammad Nadeem Iqbal; Muhammad Shakir; Muhammad Tahir; Atta Rasool; Annum Sattar; Mahreen Khalid; Allah Ditta; Bo Zhu (Environmental Science and Pollution Research, 2021)

Bacillus subtilis Y16 and biogas slurry enhanced potassium to sodium ratio and physiology of sunflower (Helianthus annuus L.) to mitigate salt stress - Samina Hamid; Iftikhar Ahmad; Muhammad Javed Akhtar; Muhammad Nadeem Iqbal; Muhammad Shakir; Muhammad Tahir; Atta Rasool; Annum Sattar; Mahreen Khalid; Allah Ditta; Bo Zhu (Environmental Science and Pollution Research, 2021)

Efficacy of rhizobacterial exopolysaccharides in improving plant growth, physiology, and soil properties - Abubakar Dar; Zahir Ahmad Zahir; Muhammad Iqbal; Atif Mehmood; Atif Javed; Azhar Hussain; Bushra; Maqshoof Ahmad (Environmental Monitoring and Assessment, 2021)

Spatial variation of b-value, creep rate, and seismic moment release along Chaman fault system - Junaid Ahmed; Farhan Javed; Waqar Ali Zafar; Talat Iqbal; Muhammad Ali Shah (Arabian Journal of Geosciences, 2021)

Geological and petrographic investigations of the Miocene Molasse deposits in Sub-Himalayas, District Sudhnati, Pakistan - Asim Javed; Ali Wahid; Muhammad Saleem Mughal; Muhammad Sabir Khan; Raja Saad Qammar; Syed Haroon Ali; Numair Ahmad Siddiqui; Muhammad Atif Iqbal (Arabian Journal of Geosciences, 2021)

Adoption of green IT in Pakistan: a comparison of three competing models through model selection criteria using PLS-SEM - Saqib Ali; Hafiz Muhammad Usama Javed; Muhammad Danish (Environmental Science and Pollution Research, 2021)

Bismuth vanadate/MXene (BiVO4/Ti3C2) heterojunction composite: enhanced interfacial control charge transfer for highly efficient visible light photocatalytic activity - Muhammad Munir Sajid; Sadaf Bashir Khan; Yasir Javed; Nasir Amin; Zhengjun Zhang; Naveed Akhtar Shad; Haifa Zhai (Environmental Science and Pollution Research, 2021)

Genetic architecture of Al3+ toxicity tolerance in rice F2:3 populations determined through QTL mapping - Nusrat Jahan; Muhammad Arshad Javed; Anwar Khan; Fazilah Abd Manan; Bushra Tabassum (Ecotoxicology, 2021)

Exogenous Application of Melatonin Induces Tolerance to Salt Stress by Improving the Photosynthetic Efficiency and Antioxidant Defense System of Maize Seedling - Shakeel Ahmad; Wenwen Cui; Muhammad Kamran; Irshad Ahmad; Xiangping Meng; Xiaorong Wu; Wennan Su; Tehseen Javed; Hamed A. El-Serehy; Zhikuan Jia; Qingfang Han (Journal of Plant Growth Regulation, 2021)

Assessment of pathogenicity of Beauveria bassiana, Metarhizium anisopliae, Verticillium lecanii and Bacillus thuringiensis var. kurstaki against Bactrocera cucurbitae Coquillett (Diptera: Tephritidae) via diet-bioassay technique under controlled conditions - Mubashar Iqbal; Muhammad Dildar Gogi; Bilal Atta; Muhammad Junaid Nisar; Muhammad Jalal Arif; Nazir Javed (International Journal of Tropical Insect Science, 2021)

Phytochemical profiling, in vitro and in vivo anti-inflammatory, analgesic and antipyretic potential of Sesuvium sesuvioides (Fenzl) Verdc. (Aizoaceae) - M. Sajid-ur-Rehman; Saiqa Ishtiaq; Mohsin Abbas Khan; Meshal Alshamrani; Muhammad Younus; Ghazala Shaheen; Muhammad Abdullah; Ghulam Sarwar; Muhammad Sohaib Khan; Faraza Javed (Inflammopharmacology, 2021)

Correction to: Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Chromium retention potential of two contrasting Solanum lycopersicum Mill. cultivars as deciphered by altered pH dynamics, growth, and organic acid exudation under Cr stress - Muhammad Tariq Javed; Kashif Tanwir; Saghir Abbas; Muhammad Hamzah Saleem; Robina Iqbal; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2021)

Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Tree-ring-based temperature reconstruction from the western Himalayan region in northern Pakistan since 1705 C.E. - Adam Khan; Moinuddin Ahmed; Narayan Prasad Gaire; Javed Iqbal; Muhammad Faheem Siddiqui; Afsheen Khan; Mohib Shah; Ali Hazrat; Najm Us Saqib; Wali Khan Mashwani; Sher Shah; Sanjaya Bhandari (Arabian Journal of Geosciences, 2021)

Do technological innovations promote green growth in the European Union? - Misbah Nosheen; Javed Iqbal; Muhammad Ali Abbasi (Environmental Science and Pollution Research, 2021)

Amplicon sequencing reveals significantly increased Vibrio abundance and associated gene functions in vibriosis‐infected black tiger shrimp ( Penaeus monodon ) - Md Javed Foysal; Farhana Momtaz; A.Q.M. Robiul Kawser; Md Hazrat Ali; Topu Raihan; Muhammad A. B. Siddik; Md Mahbubur Rahman; Alfred Tay (Journal of Fish Diseases, 2021)
Vibriosis caused by luminous Vibrio species is one of the biggest challenges to shrimp industry in Bangladesh. This study aimed to characterize whole microbial communities from Vibrio ‐infected black tiger shrimp ( Penaeus monodon ) using 16S rRNA‐based amplicon sequencing. A total of 36 disease‐free and infected shrimp were collected from six different hatcheries in Bagerhat, Bangladesh. A final pool of 12 samples ( n = 6) was created by homogenization of the hepatopancreas samples from three shrimps collected from each hatchery for the same group. The amplicon sequencing data revealed significant ( p p Proteobateria and Aeromonas were the most dominant bacteria at phylum and genus level in both groups and identified as core microbiota in the community. Two bacterial groups at phyla level and eight at genus level were found associated with the alteration of hepatopancreas microbial communities and associated gene functions in vibriosis‐infected shrimp, revealed by differential abundance and KEGG pathway analysis. The overwhelming abundance of Citroibacter , Shewanella and Candidatus lineages in vibriosis‐infected shrimp needs further investigations.

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Delineating Novel Therapeutic Drug and Vaccine Targets for Staphylococcus cornubiensis NW1T Through Computational Analysis - Mohibullah Shah; Samavia Jaan; Batool Fatima; Muhammad Sameem Javed; Adnan Amjad; Asifullah Khan; Sahib Gul Afridi; Umar Nishan; Anwar Iqbal; Haq Nawaz (International Journal of Peptide Research and Therapeutics, 2021)

Proposed formulation of surface water quality and modelling using gene expression, machine learning, and regression techniques - Muhammad Izhar Shah; Muhammad Faisal Javed; Taher Abunama (Environmental Science and Pollution Research, 2021)

Elucidating Cd-mediated distinct rhizospheric and in planta ionomic and physio-biochemical responses of two contrasting Zea mays L. cultivars - Saghir Abbas; Muhammad Tariq Javed; Qasim Ali; Muhammad Sohail Akram; Kashif Tanwir; Shafaqat Ali; Hassan Javed Chaudhary; Naeem Iqbal (Physiology and Molecular Biology of Plants, 2021)

Potential risk and source distribution of groundwater contamination by mercury in district Swabi, Pakistan: Application of multivariate study - Seema Anjum Khattak; Abdur Rashid; Muhammad Tariq; Liaqat Ali; Xubo Gao; Muhammad Ayub; Asif Javed (Environment, Development and Sustainability, 2021)

Correction to: Effect of Endoxylanase and Iron Oxide Nanoparticles on Performance and Histopathological Features in Broilers - Hamza Rehman; Muzamal Akram; Mubin Mustafa Kiyani; Muhammad Talha Yasin; Abdul Ghani; Javed Iqbal Saggu; Syed Sajid Hussain Shah; Zafar Mahmood Khalid; Syed Ali Imran Bokhari (Biological Trace Element Research, 2021)

Characterization of fungal flora associated with sternorrhyncha insects of cotton plants - Waheed Anwar; Kiran Nawaz; Muhammad Asim Javed; Adnan Akhter; Ahmad Ali Shahid; Muhammad Saleem Haider; Muhammad Zia Ur Rehman; Sajid Ali (Biologia, 2021)

Interactive role of zinc and iron lysine on Spinacia oleracea L. growth, photosynthesis and antioxidant capacity irrigated with tannery wastewater - Ihsan Elahi Zaheer; Shafaqat Ali; Muhammad Hamzah Saleem; Mohsin Ali; Muhammad Riaz; Sehar Javed; Anam Sehar; Zohaib Abbas; Muhammad Rizwan; Mohamed A. El-Sheikh; Mohammed Nasser Alyemeni (Physiology and Molecular Biology of Plants, 2020)

Plant growth-promoting Bacillus sp. strain SDA-4 confers Cd tolerance by physio-biochemical improvements, better nutrient acquisition and diminished Cd uptake in Spinacia oleracea L. - Muhammad Shahid; Muhammad Tariq Javed; Kashif Tanwir; Muhammad Sohail Akram; Syeda Khola Tazeen; Muhammad Hamzah Saleem; Sajid Masood; Sadia Mujtaba; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2020)

Analyzing extended STIRPAT model of urbanization and CO2 emissions in Asian countries - Misbah Nosheen; Muhammad Ali Abbasi; Javed Iqbal (Environmental Science and Pollution Research, 2020)

The role of sense of place, risk perception, and level of disaster preparedness in disaster vulnerable mountainous areas of Gilgit-Baltistan, Pakistan - Garee Khan; Javed Akhter Qureshi; Anwar Khan; Attaullah Shah; Sajid Ali; Iram Bano; Muhammad Alam (Environmental Science and Pollution Research, 2020)

Identification of Edible Fish Species of Pakistan Through DNA Barcoding - Muhammad Zubair Ghouri; Muhammad Ismail; Muhammad Asif Javed; Sultan Habibullah Khan; Nayla Munawar; Abdullah Bin Umar; Mehr-un-Nisa; Syed Ovais Aftab; Shazia Amin; Zulqurnain Khan; Aftab Ahmad (Frontiers in Marine Science, 2020)

First report of apple mosaic virus in peach in Pakistan - Azhar Ul Islam; Muhammad Wahaj Javed; Muhammad Akram; Javed Rahman; Muhammad Tahir; Muhammad Farooq Hussain Munis; Abu Bakr Umer Farooq (Journal of Plant Pathology, 2020)

Impact assessment of urban development patterns on land surface temperature by using remote sensing techniques: a case study of Lahore, Faisalabad and Multan district - Muhammad Sajid Saleem; Sajid Rashid Ahmad; Shafiq-Ur-Rehman; Muhammad Asif Javed (Environmental Science and Pollution Research, 2020)

Identification of irrigation potential areas, using multi-criteria analysis in Khyber District, Pakistan - Muhammad Waleed; Sajid Rashid Ahmad; Muhammad Asif Javed; Saifullah Samiullah (Environmental Science and Pollution Research, 2020)

Dietary intake assessment of pyrethroid residues from okra and eggplant grown in peri-urban areas of Punjab, Pakistan - Adnan Amjad; Muhammad Atif Randhawa; Muhammad Sameem Javed; Zafarullah Muhammad; Mussawar Ashraf; Zulfiqar Ahmad; Shamas Murtaza (Environmental Science and Pollution Research, 2020)

Methylphenidate and Rosmarinus officinalis improves cognition and regulates inflammation and synaptic gene expression in AlCl3-induced neurotoxicity mouse model - Anibah Khalid; Umme Aimen Abbasi; Sanila Amber; Sumera; Fatima Javed Mirza; Muhammad Asif; Aneela Javed; Saadia Zahid (Molecular Biology Reports, 2020)

Green remediation of saline–sodic Pb-factored soil by growing salt-tolerant rice cultivar along with soil applied inorganic amendments - Muhammad Mazhar Iqbal; Tayyaba Naz; Mazhar Iqbal Zafar; Muhammad Imtiaz; Omer Farooq; Atique ur Rehman; Shafaqat Ali; Muhammad Rizwan; Sabir Hussain; Wasim Javed; Ghulam Murtaza; Muhammad Afzal; et al. (Paddy and Water Environment, 2020)

Flash flood risk modeling of swat river sub-watershed: a comparative analysis of morphometric ranking approach and El-Shamy approach - Muhammad Jamal Nasir; Javed Iqbal; Waqas Ahmad (Arabian Journal of Geosciences, 2020)

Modulation of growth and key physiobiochemical attributes after foliar application of zinc sulphate (ZnSO4) on wheat (Triticum aestivum L.) under cadmium (Cd) stress - Shagufta Perveen; Muhammad Saeed; Abida Parveen; Muhammad Tariq Javed; Sara Zafar; Naeem Iqbal (Physiology and Molecular Biology of Plants, 2020)

Biofortification with Zinc and Iron Improves the Grain Quality and Yield of Wheat Crop - Yasir Ramzan; Muhammad Bilal Hafeez; Shahbaz Khan; Majid Nadeem; Saleem-ur-Rahman; Sumaira Batool; Javed Ahmad (International Journal of Plant Production, 2020)

Bioaccumulation of ytterbium oxide nanoparticles insinuate oxidative stress, inflammatory, and pathological lesions in ICR mice - Muhammad Adeel; Jin Tingting; Tariq Hussain; Xiao He; Muhammad Arslan Ahmad; Muhammad Kashif Irshad; Noman Shakoor; Peng Zhang; Xie Changjian; Yi Hao; Zhang Zhiyong; Rabia Javed; et al. (Environmental Science and Pollution Research, 2020)

Bioaccumulation of potentially toxic elements in spinach grown on contaminated soils amended with organic fertilizers and their subsequent human health risk - Zawar Hussain; Mehboob Alam; Muhammad Amjad Khan; Muhammad Asif; Muhammad Azhar Shah; Shehnaz Khan; Sardar Khan; Javed Nawab (Arabian Journal of Geosciences, 2020)

Vegetation-environment relationship in conifer dominating forests of the mountainous range of Indus Kohistan in northern Pakistan - Adam Khan; Moinuddin Ahmed; Muhammad Faheem Siddiqi; Mohib Shah; Eduardo Soares Calixto; Afsheen Khan; Paras Shah; Javed Iqbal; Muhammad Azeem (Journal of Mountain Science, 2020)

Foliar application of melatonin delay leaf senescence in maize by improving the antioxidant defense system and enhancing photosynthetic capacity under semi-arid regions - Shakeel Ahmad; Wennan Su; Muhammad Kamran; Irshad Ahmad; Xiangping Meng; Xiaorong Wu; Tehseen Javed; Qingfang Han (Protoplasma, 2020)

Effect of Buried Straw Layer Coupled with Fertigation on Florescence and Yield Parameters of Chinese Cabbage Under Greenhouse Environment - Ghulam Rasool; Xiangping Guo; Zhenchang Wang; Muhammad Hassan; Muhammad Aleem; Qaiser Javed; Sheng Chen (Journal of Soil Science and Plant Nutrition, 2020)

In-vitro evaluation of antimicrobial, antioxidant, alpha-amylase inhibition and cytotoxicity properties of Cannabis sativa - Syed Bilal Shah; Lubna Sartaj; Shahid Hussain; Nabi Ullah; Muhammad Idrees; Asma Shaheen; Muhammad Sufyan Javed; Muhammad Kashif Aslam (Advances in Traditional Medicine, 2020)

Characterization of antifungal metabolites produced by Lactobacillus plantarum and Lactobacillus coryniformis isolated from rice rinsed water - Shazia Anwer Bukhari; Mahwish Salman; Muhammad Numan; Muhammad Rizwan Javed; Muhammad Zubair; Ghulam Mustafa (Molecular Biology Reports, 2020)

Molecular characterization of genetic diversity and similarity centers of safflower accessions with ISSR markers - Fawad Ali; Muhammad Azhar Nadeem; Ephrem Habyarimana; Abdurrahim Yılmaz; Muhammad Amjad Nawaz; Iftikhar Hussain Khalil; Sezai Ercişli; Gyuhwa Chung; Hassan Javed Chaudhary; Faheem Shehzad Baloch (Brazilian Journal of Botany, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Antibiotics in poultry manure and their associated health issues: a systematic review - Juma Muhammad; Sardar Khan; Jian Qiang Su; Abd El-Latif Hesham; Allah Ditta; Javed Nawab; Abid Ali (Journal of Soils and Sediments, 2020)

First report of brown rot caused by Rhizopus arrhizus on tomato in Pakistan - Fiza Liaquat; Qunlu Liu; Samiah Arif; Iftikhar Hussain Shah; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Journal of Plant Pathology, 2019)

The effect of lead pollution on nutrient solution pH and concomitant changes in plant physiology of two contrasting Solanum melongena L. cultivars - Muhammad Tariq Javed; Noman Habib; Muhammad Sohail Akram; Qasim Ali; Muhammad Zulqurnain Haider; Kashif Tanwir; Asia Shauket; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2019)

Impact assessment of land use change on surface temperature and agricultural productivity in Peshawar-Pakistan - Imran Khan; Tehseen Javed; Ahmad Khan; Hongdou Lei; Ihsan Muhammad; Imad Ali; Xuexi Huo (Environmental Science and Pollution Research, 2019)

Toward GIS-Based Approach for Identification of Ecological Sensitivity Areas: Multi-Criteria Evaluation Technique for Promotion of Tourism in Soon Valley, Pakistan - Muhammad Atif Butt; Khadija Nisar; Syed Amer Mahmood; Javed Sami; Jahanzeb Qureshi; Ghulam Jaffer (Journal of the Indian Society of Remote Sensing, 2019)

Amelioration of toxicopathological effects of cadmium with silymarin and milk thistle in male Japanese quail (Coturnix japonica) - Muhammad Kashif Saleemi; Muhammad Waseem Tahir; Rao Zahid Abbas; Masood Akhtar; Aamir Ali; Muhammad Tariq Javed; Zahida Fatima; Muhammad Zubair; Sheraz Ahmed Bhatti; Zahoor Ul Hassan (Environmental Science and Pollution Research, 2019)

Effects of Rhizophagus clarus and biochar on growth, photosynthesis, nutrients, and cadmium (Cd) concentration of maize (Zea mays) grown in Cd-spiked soil - Mazhar Rafique; Ibrahim Ortas; Muhammad Rizwan; Tariq Sultan; Hassan Javed Chaudhary; Mehmet Işik; Oğuzhan Aydin (Environmental Science and Pollution Research, 2019)

The accumulation of cadmium in wheat (Triticum aestivum) as influenced by zinc oxide nanoparticles and soil moisture conditions - Zahra Saeed Khan; Muhammad Rizwan; Muhammad Hafeez; Shafaqat Ali; Muhammad Rizwan Javed; Muhammad Adrees (Environmental Science and Pollution Research, 2019)

Removal of pirimicarb from agricultural waste water using cellulose acetate–modified ionic liquid membrane - Sana Zulfiqar; Uzaira Rafique; Muhammad Javed Akhtar (Environmental Science and Pollution Research, 2019)

Influence of different organic geo-sorbents on Spinacia oleracea grown in chromite mine-degraded soil: a greenhouse study - Javed Nawab; Nayab Khan; Riaz Ahmed; Sardar Khan; Junaid Ghani; Ziaur Rahman; Fawad Khan; Xiaoping Wang; Juma Muhammad; Hassan Sher (Journal of Soils and Sediments, 2019)

Molecular characterization and interactome analysis of aerolysin ( aer ) gene from fish pathogen Aeromonas veronii : The pathogenicity inferred from sequence divergence and linked to histidine kinase ( che A) - Md Javed Foysal; Farhana Momtaz; Md Hazrat Ali; Muhammad A. B. Siddik; Md Reaz Chaklader; Md Mahbubur Rahman; Md Shamsul Haque Prodhan; Anthony Cole (Journal of Fish Diseases, 2019)
Aerolysin ( aer ) is one of the most important and abundant virulence factors in the infection of fish by Aeromonas veronii . A comprehensive study on the molecular characterization and pathogenicity of the aer gene from 34 A. veronii isolates from diseased carp and catfish was carried out and its interactome was analysed to observe the functional correlations between aer and other proteins within the A. veronii network. The PCR‐based amplification of aer from the 34 isolates of A. veronii showed more aer ‐positive isolates from catfish with a high pathogenic potential in the in vivo challenge test than the carp fish. The analysis of aer gene sequence from challenged fish revealed significant sequence divergence according to the types and geographical distribution of the fish. The networking analysis of aer from the model A. veronii B565 revealed histidine kinase ( che A) as the most functional interacting partner. The study of the interaction between aer from the experimental A. veronii and che A demonstrated that the A chain of che A plays a more important role than the corresponding B chain during contact, and a linker sequence of 15 residues controlled the entire interaction process. Therefore, che A could be an excellent drug target for controlling A. veronii infection of fish.

Assessment of Circulating Biochemical Markers in Mice Receiving Cinnamon and Glycyrrhizin Under Carbon Tetrachloride Induced Hepatic Injury - Mahmood Rasool; Arif Malik; Sadia Saleem; Shakeel Ahmed Ansari; Javed Iqbal; Muhammad Asif; Mohammed Amjad Kamal; Mohammed Hussain Al-Qahtani; Sajjad Karim (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Characteristics of pipe corrosion scales in untreated water distribution system and effect on water quality in Peshawar, Pakistan - Dilawar Farhan Shams; Saeed Islam; Baoyou Shi; Waliullah Khan; Buddhika Gunawardana; Maryam Saad; Muhammad Qasim; Haider Ali Javed; Sahib Gul Afridi; Muhammad Naeem; Gul Shahzada Khan (Environmental Science and Pollution Research, 2019)

CRISPR-Cas System: History and Prospects as a Genome Editing Tool in Microorganisms - Muhammad R. Javed; Maria Sadaf; Temoor Ahmed; Amna Jamil; Marium Nawaz; Hira Abbas; Anam Ijaz (Current Microbiology, 2018)

A comprehensive study on the surface chemistry of particulate matter collected from Jeddah, Saudi Arabia - Asim Jilani; Syed Zajif Hussain; Mohd Hafiz Dzarfan Othman; Usama Zulfiqar; Muhammad Bilal Shakoor; Imran Ullah Khan; Javed Iqbal; Attieh A. Al-Ghamdi; Ahmed Alshahrie (Journal of Atmospheric Chemistry, 2018)

Effect of ambient management interventions on the production and physiological performance of lactating Sahiwal cattle during hot dry summer - Mehtab Ahmad; Jalees Ahmed Bhatti; Muhammad Abdullah; Khalid Javed; Mehboob Ali; Ghazanfar Rashid; Rafi Uddin; Ali Hassan Badini; Mudassar Jehan (Tropical Animal Health and Production, 2018)

Monitoring and spatiotemporal variations of pyrethroid insecticides in surface water, sediment, and fish of the river Chenab Pakistan - Ghazala Riaz; Amtul Bari Tabinda; Muhammad Kashif; Abdullah Yasar; Adeel Mahmood; Rizwan Rasheed; Muhammad Imran Khan; Javed Iqbal; Sidra Siddique; Yusra Mahfooz (Environmental Science and Pollution Research, 2018)

Genetic characterization of phenicol-resistant Escherichia coli and role of wild-type repressor/regulator gene (acrR) on phenicol resistance - Muhammad Yaqoob; Li Ping Wang; Jam Kashif; Javed Memon; Sajid Umar; Muhammad Farooq Iqbal; Muhammad Fiaz; Cheng-Ping Lu (Folia Microbiologica, 2018)

Lead Toxicity in Cereals and Its Management Strategies: a Critical Review - Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Muhammad Rizwan Javed; Arooj Bashir (Water, Air, & Soil Pollution, 2018)

Riverine flood assessment in Jhang district in connection with ENSO and summer monsoon rainfall over Upper Indus Basin for 2010 - Bushra Khalid; Bueh Cholaw; Débora Souza Alvim; Shumaila Javeed; Junaid Aziz Khan; Muhammad Asif Javed; Azmat Hayat Khan (Natural Hazards, 2018)

Transcriptome analysis reveals the molecular mechanism of hepatic metabolism disorder caused by chromium poisoning in chickens - Xinxin Tian; Hui Zhang; Yali Zhao; Khalid Mehmood; Xiaoxing Wu; Zhenyu Chang; Min Luo; Xueting Liu; Muhammad Ijaz; Muhammad Tariq Javed; Donghai Zhou (Environmental Science and Pollution Research, 2018)

Sugar beet extract acts as a natural bio-stimulant for physio-biochemical attributes in water stressed wheat (Triticum aestivum L.) - Ali Noman; Qasim Ali; Jazia Naseem; M. Tariq Javed; Hina Kanwal; Waqar Islam; Muhammad Aqeel; Noreen Khalid; Sara Zafar; Muhammad Tayyeb; Naeem Iqbal; Mahmooda Buriro; et al. (Acta Physiologiae Plantarum, 2018)

Formulation Development and Evaluation of Diphenhydramine Nasal Nano-Emulgel - Hina Javed; Syed Nisar Hussain Shah; Furqan Muhammad Iqbal (AAPS PharmSciTech, 2018)

Elicitation of Secondary Metabolites in Callus Cultures of Stevia rebaudiana Bertoni Grown Under ZnO and CuO Nanoparticles Stress - Rabia Javed; Buhara Yucesan; Muhammad Zia; Ekrem Gurel (Sugar Tech, 2018)

Osteopontin gene polymorphism association with milk traits and its expression analysis in milk of riverine buffalo - Sidra Manzoor; Asif Nadeem; Javed Maryam; Abu Saeed Hashmi; Muhammad Imran; Masroor Ellahi Babar (Tropical Animal Health and Production, 2018)

Comparison of total ozone column observations from space-borne Ozone Monitoring Instrument with ground-based Dobson Ozone Spectrophotometer measurements at an urban location in Indo-Gangetic Basin - Zia Ul-Haq; Zertasha Ramzan; Salman Tariq; Syeda Adila Batool; Muhammad Ali; Javed Sami (International Journal of Remote Sensing, 2018)

Deciphering the growth, organic acid exudations, and ionic homeostasis of Amaranthus viridis L. and Portulaca oleracea L. under lead chloride stress - Muhammad Tariq Javed; Muhammad Sohail Akram; Noman Habib; Kashif Tanwir; Qasim Ali; Nabeel Khan Niazi; Huma Gul; Naeem Iqbal (Environmental Science and Pollution Research, 2018)

Combined Applications of Aminoethoxyvinylglycine with Salicylic Acid or Nitric Oxide Reduce Oxidative Stress in Peach During Ripening and Cold Storage - Mohammad Javed Tareen; Zora Singh; Ahmad Sattar Khan; Nadeem Akhtar Abbasi; Muhammad Naveed (Journal of Plant Growth Regulation, 2017)

Potentially Toxic Metals and Biological Contamination in Drinking Water Sources in Chromite Mining-Impacted Areas of Pakistan: A Comparative Study - Javed Nawab; Sardar Khan; Muhammad Amjad Khan; Hassan Sher; Ubaid Ur Rehamn; Sharafat Ali; Syed Mehboob Shah (Exposure and Health, 2017)

Differential effects of plant growth regulators on physiology, steviol glycosides content, and antioxidant capacity in micropropagated tissues of Stevia rebaudiana - Rabia Javed; Buhara Yucesan; Muhammad Zia; Ekrem Gurel (Biologia, 2017)

Terbufos sulfone aggravates kidney damage in STZ-induced diabetic rats - Syed Muhammad Nurulain; Shreesh Ojha; Mohamed Shafiullah; Javed Yasin; Tayyaba Yasmin; Tariq Saeed; Ernest Adeghate (Biologia, 2017)

Ethnoveterinary health management practices using medicinal plants in South Asia – a review - Shanoo Suroowan; Faisal Javeed; Mushtaq Ahmad; Muhammad Zafar; Mehwish Jamil Noor; Sadaf Kayani; Ali Javed; Mohamad Fawzi Mahomoodally (Veterinary Research Communications, 2017)

Appraisal for site specific plant nutrient management through spatial variability and mapping in hilly areas of northern Pakistan - Munir Ahmad; Dost Muhammad; Maria Mussarat; Abid Ali Khan; Shah Faisal Khan; Muhammad Waqas Javed (Journal of Soils and Sediments, 2017)

Changes in rubisco, cysteine-rich proteins and antioxidant system of spinach (Spinacia oleracea L.) due to sulphur deficiency, cadmium stress and their combination - Rita Bagheri; Javed Ahmad; Humayra Bashir; Muhammad Iqbal; M. Irfan Qureshi (Protoplasma, 2017)

Direct and indirect effects of wastewater use and herd environment on the occurrence of animal diseases and animal health in Pakistan - Ehsan Elahi; Liqin Zhang; Muhammad Abid; Muhammad Tariq Javed; Han Xinru (Environmental Science and Pollution Research, 2017)

Congener-specific evaluation of biota-sediment accumulation factor model for HCHs and DDTs under small-scale in situ riverine condition - Muhammad Aamir; Sardar Khan; Mengling Tang; Zahir Qamar; Anwarzeb Khan; Javed Nawab (Journal of Soils and Sediments, 2017)

Equilibrium modeling of cadmium biosorption from aqueous solution by compost - Iftikhar Ahmad; Muhammad Javed Akhtar; Iram Bashir Khan Jadoon; Muhammad Imran; Muhammad Imran; Shahid Ali (Environmental Science and Pollution Research, 2017)

Microwave-assisted enhancement of milkweed (Calotropis procera L.) leaves as an eco-friendly source of natural colorants for textile - Muhammad Hussaan; Naeem Iqbal; Shahid Adeel; Muhammad Azeem; M. Tariq Javed; Ali Raza (Environmental Science and Pollution Research, 2017)

Influence of sub-lethal crude oil concentration on growth, water relations and photosynthetic capacity of maize (Zea mays L.) plants - Habib-ur-Rehman Athar; Sarah Ambreen; Muhammad Javed; Mehwish Hina; Sumaira Rasul; Zafar Ullah Zafar; Hamid Manzoor; Chukwuma C. Ogbaga; Muhammad Afzal; Fahad Al-Qurainy; Muhammad Ashraf (Environmental Science and Pollution Research, 2016)

Drought tolerance potential of Vigna mungo L. lines as deciphered by modulated growth, antioxidant defense, and nutrient acquisition patterns - Qasim Ali; Muhammad Zulqurnain Haider; Wasif Iftikhar; Sidra Jamil; M. Tariq Javed; Ali Noman; Muhammad Iqbal; Rashida Perveen (Brazilian Journal of Botany, 2016)

Differential Effects of Plant Growth-Promoting Rhizobacteria on Maize Growth and Cadmium Uptake - Iftikhar Ahmad; Muhammad Javed Akhtar; Hafiz Naeem Asghar; Umber Ghafoor; Muhammad Shahid (Journal of Plant Growth Regulation, 2016)

Health risk assessment from contaminated foodstuffs: a field study in chromite mining-affected areas northern Pakistan - Javed Nawab; Gang Li; Sardar Khan; Hassan Sher; Muhammad Aamir; Isha Shamshad; Anwarzeb Khan; Muhammad Amjad Khan (Environmental Science and Pollution Research, 2016)

Escherichia coli as a fatty acid and biodiesel factory: current challenges and future directions - Ziaur Rahman; Naim Rashid; Javed Nawab; Muhammad Ilyas; Bong Hyun Sung; Sun Chang Kim (Environmental Science and Pollution Research, 2016)

Quantitative trait locus mapping for salt tolerance at maturity stage in indica rice using replicated F2 population - Md. Shah Kamal Khan; Muhammad Saeed; Javed Iqbal (Brazilian Journal of Botany, 2016)

Flood modeling and simulations using hydrodynamic model and ASTER DEM—A case study of Kalpani River - Sana Ullah; Muhammad Farooq; Tahir Sarwar; Mohammad Javed Tareen; Mirza Abdul Wahid (Arabian Journal of Geosciences, 2016)

Aflatoxins in composite spices collected from local markets of Karachi, Pakistan - Muhammad Asif Asghar; Erum Zahir; Summan Rantilal; Aftab Ahmed; Javed Iqbal (Food Additives & Contaminants Part B-Surveillance, 2016)

Towards Co-PPGIS—a collaborative public participatory GIS-based measure for transparency in housing schemes: a case of Lahore, Pakistan - Muhammad A. Butt; Songnian Li; Nasir Javed (Applied Geomatics, 2016)

Correlation studies on nitrogen for sunflower crop across the agroclimatic variability - Wajid Nasim; Hatem Belhouchette; Muhammad Tariq; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Mubeen; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary; Imran Khan; Faisal Mahmood; Tauqeer Abbas; Fahd Rasul; et al. (Environmental Science and Pollution Research, 2016)

Organic amendments impact the availability of heavy metal(loid)s in mine-impacted soil and their phytoremediation by Penisitum americanum and Sorghum bicolor - Javed Nawab; Sardar Khan; Muhammad Aamir; Isha Shamshad; Zahir Qamar; Islamud Din; Qing Huang (Environmental Science and Pollution Research, 2016)

Aflatoxins and ochratoxin A in export quality raisins collected from different areas of Pakistan - Muhammad Asif Asghar; Aftab Ahmed; Javed Iqbal (Food Additives & Contaminants Part B-Surveillance, 2016)

Identification of QTL influencing seed oil content, fatty acid profile and days to flowering in Brassica napus L. - Nasir Javed; Jianfeng Geng; Muhammad Tahir; P. B. E. McVetty; Genyi Li; Robert W. Duncan (Euphytica, 2016)

Spatial distribution of pollutant emissions from crop residue burning in the Punjab and Sindh provinces of Pakistan: uncertainties and challenges - Muhammad Irfan; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Sabir Hussain; Muhammad Javed Akhtar; Leon van den Berg; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Inoculation of Nicotiana tabacum with recombinant potato virus X induces RNA interference in the solenopsis mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Arif Muhammad Khan; Muhammad Ashfaq; Azhar Abbas Khan; Akhtar Rasool; Javed Iqbal; Shahid Mansoor (Biotechnology Letters, 2015)

Efficacy of silicon priming and fertigation to modulate seedling’s vigor and ion homeostasis of wheat (Triticum aestivum L.) under saline environment - Muhammad Azeem; Naeem Iqbal; Shakila Kausar; M. Tariq Javed; M. Sohail Akram; M. Asim Sajid (Environmental Science and Pollution Research, 2015)

Modulations in plant water relations and tissue-specific osmoregulation by foliar-applied ascorbic acid and the induction of salt tolerance in maize plants - Sidra Jamil; Qasim Ali; Muhammad Iqbal; Muhammad Tariq Javed; Wasif Iftikhar; Faisal Shahzad; Rashida Perveen (Brazilian Journal of Botany, 2015)

Identification of quantitative trait loci for Na+, K+ and Ca++ accumulation traits in rice grown under saline conditions using F2 mapping population - Md. Shah Kamal Khan; Muhammad Saeed; Javed Iqbal (Brazilian Journal of Botany, 2015)

The effect of gestational diabetes on proliferation capacity and viability of human umbilical cord-derived stromal cells - Nadia Wajid; Rashida Naseem; Sanam Saiqa Anwar; Sana Javaid Awan; Muhammad Ali; Sara Javed; Fatima Ali (Cell and Tissue Banking, 2015)

The use of PCR technique in the identification of Mycobacterium species responsible for bovine tuberculosis in cattle and buffaloes in Pakistan - Farah Akhtar; Muhammad Tariq Javed; Aziz-ur-Rehman; Muhammad Nisar Khan; Pervez Akhtar; Sayed Misdaq Hussain; Muhammad Sohaib Aslam; Razia Kausar; Mehwish Qamar; Monica Cagiola (Tropical Animal Health and Production, 2015)

Differential effects of cadmium and chromium on growth, photosynthetic activity, and metal uptake of Linum usitatissimum in association with Glomus intraradices - Amna; Naeem Ali; Sajid Masood; Tehmeena Mukhtar; Muhammad Aqeel Kamran; Mazhar Rafique; M. Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Monitoring and Assessment, 2015)

Effect of plant growth-promoting rhizobacteria inoculation on cadmium (Cd) uptake by Eruca sativa - Muhammad Aqeel Kamran; Jabir Hussain Syed; Syed Ali Musstjab Akber Shah Eqani; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2015)

An appraisal on the occurrence of foot-and-mouth disease virus serotypes in cattle and buffaloes, Pakistan - Muhammad Abubakar; Ehtisham-ul-Haq Khan; Muhammad Javed Arshed; Jose Gonzales; Giancarlo Ferrari; Manzoor Hussain; Qurban Ali (Archives of Virology, 2015)

Geochemical assessment of metal pollution and ecotoxicology in sediment cores along Karachi Coast, Pakistan - Azhar Mashiatullah; Muhammad Zaman Chaudhary; Nasir Ahmad; Nisar Ahmad; Tariq Javed; Abdul Ghaffar (Environmental Monitoring and Assessment, 2015)

Diazotrophs-assisted phytoremediation of heavy metals: a novel approach - Abid Ullah; Hafsa Mushtaq; Hazrat Ali; Muhammad Farooq Hussain Munis; Muhammad Tariq Javed; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2015)

Genetic analysis of post-weaning growth traits of Thalli sheep under tropical conditions - Asghar Hussain; Pervez Akhtar; Safdar Ali; Khalid Javed; Muhammad Younas; Abdul Shakoor; Usman Waheed (Tropical Animal Health and Production, 2014)

Cadmium-tolerant bacteria induce metal stress tolerance in cereals - Iftikhar Ahmad; Muhammad Javed Akhtar; Zahir Ahmad Zahir; Muhammad Naveed; Birgit Mitter; Angela Sessitsch (Environmental Science and Pollution Research, 2014)

Aflatoxin B 1 in betel nuts ( Areca catechu L . ) imported to Pakistan from different regions of South Asia - Muhammad Asif Asghar; Javed Iqbal; Aftab Ahmed; Mobeen Ahmed Khan; Zuzzer Ali Shamsuddin (Food Additives & Contaminants Part B-Surveillance, 2014)

Erratum to: Current and future therapies for hepatitis C virus infection: from viral proteins to host targets - Muhammad Imran; Sobia Manzoor; Nasir Mahmood Khattak; Madiha Khalid; Qazi Laeeque Ahmed; Fahed Parvaiz; Muqddas Tariq; Javed Ashraf; Waseem Ashraf; Sikandar Azam; Muhammad Ashraf (Archives of Virology, 2014)

Current and future therapies for hepatitis C virus infection: from viral proteins to host targets - Muhammad Imran; Sobia Manzoor; Nasir Mahmood Khattak; Madiha Khalid; Qazi Laeeque Ahmed; Fahed Parvaiz; Muqddas Tariq; Javed Ashraf; Waseem Ashraf; Sikandar Azam; Muhammad Ashraf (Archives of Virology, 2014)

Potential of Bacillus species against Meloidogyne javanica parasitizing eggplant (Solanum melongena L.) and induced biochemical changes - Muhammad Waseem Abbasi; Naeem Ahmed; Muhammad Javed Zaki; S. Shahid Shuakat; D. Khan (Plant and Soil, 2014)

Aflatoxins contamination and prevention in red chillies ( Capsicum annuum L. ) in Pakistan - Mobeen Ahmed Khan; Muhammad Asif Asghar; Javed Iqbal; Aftab Ahmed; Zuzzer Ali Shamsuddin (Food Additives & Contaminants Part B-Surveillance, 2014)

Erratum to: Effect of varying dietary energy levels during the last trimester of pregnancy on subsequent first lactation performance in Sahiwal heifers - Muhammad Fiaz; Muhammad Abdullah; Muhammad Nasir; Khalid Javed; Masroor Ellahi Babar; Talat Naseer Pasha; Makhdoom Abdul Jabbar (Tropical Animal Health and Production, 2014)

The potential of the flora from different regions of Pakistan in phytoremediation: a review - Muhammad Aqeel Kamran; Amna; Rabia Mufti; Nadia Mubariz; Jabir Hussain Syed; Asghari Bano; Muhammad Tariq Javed; Muhammad Farooq Hussain Munis; Zhiyuan Tan; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2014)

A suggested classification for two groups of Campylobacter myoviruses - Muhammad Afzal Javed; Hans-Wolfgang Ackermann; Joana Azeredo; Carla M. Carvalho; Ian Connerton; Stephane Evoy; Jens André Hammerl; Stefan Hertwig; Rob Lavigne; Amit Singh; Christine M. Szymanski; Andrew Timms; et al. (Archives of Virology, 2014)

Risks factors associated with subclinical mastitis in water buffaloes in Pakistan - Riaz Hussain; Muhammad Tariq Javed; Ahrar Khan; Ghulam Muhammad (Tropical Animal Health and Production, 2013)

Nitrous Oxide Emissions from Yellow Brown Soil as Affected by Incorporation of Crop Residues With Different Carbon-to-Nitrogen Ratios: A Case Study in Central China - Shan Lin; Javed Iqbal; Ronggui Hu; Muhammad Shaaban; Jianbo Cai; Xi Chen (Archives of Environmental Contamination and Toxicology, 2013)

Metal pollution and ecological risk assessment in marine sediments of Karachi Coast, Pakistan - Azhar Mashiatullah; Muhammad Zaman Chaudhary; Nasir Ahmad; Tariq Javed; Abdul Ghaffar (Environmental Monitoring and Assessment, 2013)

Breast Cancer Proteome Takes More Than Two to Tango on TRAIL: Beat Them at Their Own Game - Ammad Ahmad Farooqi; Sundas Fayyaz; Muhammad Tahir; Muhammed Javed Iqbal; Shahzad Bhatti (The Journal of Membrane Biology, 2012)

Cloning, characterization and molecular docking of a highly thermostable β-1,4-glucosidase from Thermotoga petrophila - Ikram Ul Haq; Mahmood Ali Khan; Bushra Muneer; Zahid Hussain; Sumra Afzal; Sana Majeed; Naeem Rashid; Muhammad Mohsin Javed; Ishtiaq Ahmad (Biotechnology Letters, 2012)

Population structure and linkage disequilibrium in Lupinus albus L. germplasm and its implication for association mapping - Muhammad Javed Iqbal; Sujan Mamidi; Rubina Ahsan; Shahryar F. Kianian; Clarice J. Coyne; Anwar A. Hamama; Satya S. Narina; Harbans L. Bhardwaj (Theoretical and Applied Genetics, 2012)

Effects of Vitamins, Probiotics, and Protein Level on Semen Traits and Some Seminal Plasma Macro- and Microminerals of Male Broiler Breeders After Zinc-Induced Molting - Rifat Ullah Khan; Zia-ur-Rahman; Ijaz Javed; Faqir Muhammad (Biological Trace Element Research, 2012)

Effect of varying dietary energy levels during the last trimester of pregnancy on subsequent first lactation performance in Sahiwal heifers - Muhammad Fiaz; Muhammad Abdullah; Muhammad Nasir; Khalid Javed; Masroor Ellahi Babar; Talat Naseer Pasha; Makhdoom Abdul Jabbar (Tropical Animal Health and Production, 2012)

NutriTRAILomics in prostate cancer: time to have two strings to one’s bow - Ammad Ahmad Farooqi; Aamir Rana; Asma M. Riaz; Ammara Khan; Muhammad Ali; Sara Javed; Shahzeray Mukhtar; Sehrish Minhaj; Javeria Rafique Rao; Javairia Rajpoot; Rafia Amber; Fiza Asif Javed; et al. (Molecular Biology Reports, 2012)

Assessment of background levels of trace metals in water and soil from a remote region of Himalaya - Munir H. Shah; Javed Iqbal; Nazia Shaheen; Nadeem Khan; Muhammad Aziz Choudhary; Gulraiz Akhter (Environmental Monitoring and Assessment, 2012)

A molecular evaluation of dengue virus pathogenesis and its latest vaccine strategies - Muhammad Faheem; Ummar Raheel; Muhammad Nasir Riaz; Naghmana Kanwal; Farakh Javed; Najam us Sahar Sadaf Zaidi; Ishtiaq Qadri (Molecular Biology Reports, 2011)

Evidence of peste des petits ruminants virus (PPRV) infection in Sindh Ibex (Capra aegagrus blythi) in Pakistan as confirmed by detection of antigen and antibody - Muhammad Abubakar; Zahid Iqbal Rajput; Muhammad Javed Arshed; Ghulam Sarwar; Qurban Ali (Tropical Animal Health and Production, 2011)

Developmental and photosynthetic regulation of δ-endotoxin reveals that engineered sugarcane conferring resistance to ‘dead heart’ contains no toxins in cane juice - Muhammad Sarwar Khan; Safdar Ali; Javed Iqbal (Molecular Biology Reports, 2011)

Cloning and expression of β-glucosidase gene from Bacillus licheniformis into E. coli BL 21 (DE3) - Sana Zahoor; Muhammad M. Javed; Muhammad N. Aftab; Ikram-ul-Haq (Biologia, 2011)

Nutrient digestibility and feedlot performance of lambs fed diets varying protein and energy contents - Javed I. Sultan; Asif Javaid; Muhammad Aslam (Tropical Animal Health and Production, 2010)

Effect of induced pyrexia on the disposition kinetics of ciprofloxacin in dogs - Faqir Muhammad; Masood Akhtar; M. Irfan Anwar; M. Javed Arshed (Veterinary Research Communications, 2009)

Peste des petits ruminants virus (PPRV) infection; Its association with species, seasonal variations and geography - Muhammad Abubakar; Syed Muhammad Jamal; Muhammad Javed Arshed; Manzoor Hussain; Qurban Ali (Tropical Animal Health and Production, 2009)

Investigating the concurrent presence of HCV in serum, oral fluid and urine samples from chronic HCV patients in Faisalabad, Pakistan - Muhammad Shafique; Nasir Ahmad; Fazli R. Awan; Tanveer Mustafa; Mujib Ullah; Javed A. Qureshi (Archives of Virology, 2009)

Heavy Metal Residues in the Milk of Cattle and Goats During Winter Season - Ijaz Javed; Ibadullah Jan; Faqir Muhammad; Zia-ur-Rahman; M. Zargham Khan; Bilal Aslam; Javed Iqbal Sultan (Bulletin of Environmental Contamination and Toxicology, 2009)

Improvement of Aspergillus oryzae for hyperproduction of endoglucanase: expression cloning of cmc-1 gene of Aspergillus aculeatus - Muhammad Hamid Rashid; Muhammad Rizwan Javed; Takashi Kawaguchi; Jun-ichi Sumitani; Motoo Arai (Biotechnology Letters, 2008)

Expression and identification of folate-sensitive fragile sites in British Suffolk sheep (Ovis aries) - Ahmad Ali; Muhammad Abdullah; Masroor Ellahi Babar; Khalid Javed; Asif Nadeem (Journal of Genetics, 2008)

Some new prospects in the understanding of the molecular basis of the pathogenesis of stroke - Sheikh Arshad Saeed; Kaneez Fatima Shad; Taimur Saleem; Faisal Javed; Muhammad Umair Khan (Experimental Brain Research, 2007)

Characterization of fusarium wilt-resistant and fusarium wilt-susceptible somaclones of banana cultivar rastali (Musa AAB) by random amplified polymorphic DNA and retrotransposon markers - Asif Javed Muhammad; Fofina Yasmin Othman (Plant Molecular Biology Reporter, 2005)

Morpho-anatomical responses ofTrigonella foenum graecum Linn. to induced cadmium and lead stress - Syed Hilal Ahmad; Zafar Reshi; Javed Ahmad; Muhammad Iqbal (Journal of Plant Biology, 2005)